Dietary selenium nanoparticles alleviate heat stress-induced reproductive impairment in Onychostoma macrolepis, with MeSeCys as a key bioactive selenium species - Chao Zhu; Weiping Pan; Jianbo Zheng; Shili Liu; Meili Chi; Wenping Jiang; Shun Cheng; Junzhi Luo; Wuzi Dong; Zhilong Chen; Fei Li (Theriogenology, 2026)

Tandem biocatalysis in synthetic microbial consortium: efficient polybutylene adipate terephthalate degradation coupled to polyhydroxybutyrate synthesis - Jiali Liu; Jie Yang; Xin Wang; Zhenglin Xia; Zhinan Jiang; Xiao Zhang; Fei Li (Bioresource Technology, 2026)

Cloud parameter retrieval based on satellite data: A review of methods, advances, and challenges - Zhihui Li; Weihua Ai; Zhuohan Jiang; Zhonghui Tan; Fei Zhang; Zia Ahmed (Atmospheric Research, 2026)

Columnar optical properties of locally emitted light-absorbing carbonaceous aerosols - Kang Hu; Hong Liao; Dantong Liu; Jianbing Jin; Siyuan Li; Yangzhou Wu; Yuxing Gao; Xiaotong Jiang; Shitong Zhao; Ping Tian; Fei Wang; Na Kang; et al. (Journal of Environmental Sciences, 2026)

Depth-dependent microbial succession and interspecies hydrogen transfer drive pit mud maturation in Chinese strong-flavor baijiu fermentation - Shanshan Xu; Jingwen Li; Fei Wang; Huixi Bian; Wenjia Yan; Hao Wang; Chao Jiang; Jinyuan Sun; Zhuochen Wang; Xingjiang Li (Food Research International, 2026)

PoGPx-7, a glutathione peroxidase homolog from teleosts, exhibits bactericidal activity and activates host immune cells against bacterial infection - Xin-yi Jiang; Xue-pin Han; Jia-hang Zhang; Mo-fei Li (Fish & Shellfish Immunology, 2026)

From prediction to decision: A review of multi-dimensional spatiotemporal load forecasting for building and district energy systems - Zhongyu Xia; Libo Wang; Liutao Zhu; Yao Tang; Liang Ma; Huiling Su; Ji Li; Fei Lu; Zhu Jiang; Xukai Yang; Xiaosong Zhang; Shifang Huang (Energy and Buildings, 2026)

Self-supporting, binder-free NiCoAl-LTH/NF composite electrodes for high-efficiency membrane-free capacitive deionization - Ya-Qi Jiang; Yun-Ze Qiu; Chun-Miao Zhang; Qin Li; Jing-Jing Feng; Wen-Qing Fei; Xue-Fei Sun (Desalination, 2026)

Immobilizing MIL-9 in PVDF spheres for durable and efficient peroxymonosulfate activation toward antibiotic degradation - Xing-Lin Lv; Peng Wang; Xiang-Yu Li; Fei Wang; Zi-Yu Jia; Miao Chang; Xin Jiang; Zhao-Yi Liu; Xiao-Hong Yi; Anping Wang; Jiguang Deng; Chong-Chen Wang (Chemical Engineering Journal, 2026)

Unveiling and steering Thiobacillus denitrificans metabolic network to tackle denitrification inhibition under antibiotic-heavy metal co-exposure - Xinyi Wang; Can Wang; Tianhong Bao; Kexin Zhang; Liyue Jiang; Bin Wu; Peng Bao; Fei Xu; Likai Hao; Shun Li (Bioresource Technology, 2026)

Advancing precision nutrition beverages through plant-derived extracellular vesicles nanocarriers: A critical review of engineering strategies and functional mechanisms - Mi Li; Yuanchang Cao; Yunge Zhang; Peng Fei; Yanli Ma; Qisen Xiang; Yujun Jiang; Jian Ju; Cuicui Li (Trends in Food Science & Technology, 2026)

Chitosan oligosaccharides exerted a concentration-dependent effect for inhibiting transglutaminase-induced cross-linking of whey protein isolate and enhancing its interfacial properties and bioactivities - Fei Li; Han Wang; Mingzhang Zhao; Chenyue Hou; Zhanmei Jiang; Juncai Hou (Food Research International, 2026)

Synergistic enhancement in electrochemical detection of chlorogenic acid using the accordion-like N-doped carbon nanoplate supported NiFe2O4 nanocomposite - Jiejun Li; Yurou Zhang; Caiyu Ge; Yi Jiang; Pengcheng Zhao; Junjie Fei; Yixi Xie (Food Chemistry, 2026)

A novel self-assembling peptide-based fibrous delivery system integrating physical barrier and sustained drug release for enhanced therapeutic efficacy in allergic rhinitis - Yu Liu; Ai Yang; Tingmei Lyu; Yun Hong; Xuting Zhou; Yuxia Chang; Binhao Zhao; Zhiyan Zhang; Fei Qin; Baoping Jiang; Li Wu; Gaohong Lyu; et al. (Chemical Engineering Journal, 2026)

Janus dual-nitride heterostructure on nanoporous metal for highly selective urea oxidation-assisted hydrogen production - Zhi-Lan Zhou; Jin-Peng Li; Ying Wang; Rui-Qi Yao; Xin-Ying Sun; Shu-Pei Zeng; Yun-Fei Chang; Gao-Feng Han; Tong-Hui Wang; Zi Wen; Hang Shi; Xing-You Lang; et al. (Chemical Engineering Journal, 2026)

Machine learning for spatiotemporal variability of the provenance in the Tengger Desert, Northwest China - Baofeng Li; Wenyi Liu; Han Hu; Chongwen Luo; Zaijun Li; Fei Wang; Qida Jiang; Xin Wang; Qi Feng (CATENA, 2026)

Soil macrofauna mucus bacterial community: Insights from cultured earthworms and snails - Jia-Jia Gu; Ming-Xin Li; Shuai-Fei Ye; Qiu-Yu Gan; Si-Si Chen; Cheng-Wei Tao; Jing Wen; Xin-Li An; Yu-Ling Jiang; Hong-Tao Wang (Soil Ecology Letters, 2026)

Ammonicoccus luteus sp. nov., a novel actinobacterium isolated from the intestine of Argyrosomus argentatus - Fei Yang; Haifei Liu; Jiawei Li; Caifei Li; Ding Li; Ying Sun; Lifang Yang; Mingguo Jiang (Archives of Microbiology, 2026)

Equivalent emissivity correction of the blackbody on-board MWRI-RM - Dong Ke-Song; Xing Rui-Xian; Bai Chuan; XU Jing; Meng Wan-Ting; He Jia-Kai; Jiang Li-Fei (International Journal of Remote Sensing, 2026)

Functional characterization of the Cbr1 gene in regulating alkaline tolerance in grass carp - Jianbo Zheng; Yi Xu; Qi Chen; Fei Li; Shili Liu; Chao Zhu; Shun Cheng; Wenping Jiang; Meili Chi; Junzhi Luo; Caiyan Li; Xiaohui Xu; et al. (Aquaculture, 2026)

Lactiplantibacillus plantarum 18 protects against H3N2 and H1N1 Influenza A Virus infection associated with enhanced respiratory mucosal barrier function - Jiayi Hao; Letian Li; Lingcong Deng; Zhongbo Guo; Yan Jiang; Jingyi Wang; Yaxi Guo; Dongliang Fei; Mingxiao Ma; Chang Li; Maopeng Wang (Veterinary Microbiology, 2026)

Stronger actions are needed to advance PM2.5 mitigation and its health benefits under population aging in China: Evidence from China’s Clean Air Actions - Jian Qian; Ruoyu Li; You Zou; Jiayi Chen; Junyu Wang; Sheng Li; Na Yang; Tianyue Han; Xin Wang; Chenglin Tao; Nan Wang; Menglu Jiang; et al. (Journal of Hazardous Materials, 2026)

A novel fungus Penicillium crocicola LF-2022 for high-efficiency biodegradation of brominated flame retardants: Performance, pathways, soil remediation, and transcriptomic mechanisms - Yan Li; Ruiying Wu; Zhenglin Xia; Zhinan Jiang; Haitao Wu; Chen Lin; Jiaqing Chen; Fei Li (Journal of Hazardous Materials, 2026)

High-level expression of a newly characterized collagenase in Bacillus subtilis for efficient production of collagen peptides from fish scales - Yuanhui Li; Shaoqing Yang; Qiaojuan Yan; Haiyan Wang; Fei Lu; Zhengqiang Jiang (Food Chemistry, 2026)

TBK1 associates with TRIF and TRAF3 related IRF3, IRF7, and type I IFN signaling in large yellow croaker Larimichthys crocea - Ying Li; Wen Qi Zha; Wen Feng Cui; Meng Jia Li; Yan Mi Na Chen; Qiu Ye Huang; Qiao Yun Yang; Ying Jia Shen; Yi Lei Wang; Yong Hua Jiang; Peng Fei Zou (Fish & Shellfish Immunology, 2026)

Metabolic alterations bridge exposure to urinary halogenated phenols and bisphenols to dyslipidemia: Evidence from an e-waste recycling area - Meng-Yang Li; Hong-Xuan Kuang; Tian-Hong Chen; Xiu-Fei Wang; Yin-Fei Song; Ming-Deng Xiang; Ying-Xin Yu; Yun-Jiang Yu (Environmental Pollution, 2026)

Autoimmune disease patients with comorbid cancer exhibit prominent immunometabolic crosstalk - Xu Jiang; Yangzhige He; Naixin Liang; Xiangyi Shen; Ziyue Zhou; Dan Yang; Jiana Chen; Jiaqi Xu; Mengyuan Wang; Yiyi Gong; Xiaoyan Si; Li Zhang; et al. (Science China Life Sciences, 2026)

Molecular understanding of plant pollination, fertilization, seed development and protoplast regeneration - Jiang-Guo Meng; Pu Liu; Hanxian Xiong; Wei Wang; Gang Xu; Xu Xin; Zijun Lan; Changkai Ma; Na Wang; Xuecheng Zhang; Ce Shi; Shu Chang; et al. (Science China Life Sciences, 2026)
Sexual reproduction in plants is a tightly coordinated process that underpins biodiversity, drives speciation, and serves as a foundation for modern crop improvement. Here, we synthesize recent advances in elucidating the molecular mechanisms governing major reproductive events in flowering plants, including male and female gametogenesis, pollen-pistil communication, double fertilization, embryogenesis, and endosperm-mediated seed development. We also discuss the integration of asexual propagation through protoplast regeneration, highlighting its emerging importance in plant biotechnology. Together, these insights deepen our understanding of fundamental reproductive biology and open new opportunities for the rational design of hybrid breeding systems and stress-resilient crops, with broad implications for global food security under changing climatic conditions.

Integrating neural network features into nonstationary gaussian processes for expensive optimization - Yating Wang; Sanyou Zeng; Fei Zhao; Yuhong Jiang; Changhe Li; Ruwang Jiao (Swarm and Evolutionary Computation, 2026)

Retraction notice to “Boronic acid-modified bacterial cellulose microspheres as packing materials for enveloped virus removal” [Sci. Total Environ. 859 (2023) 160341] - Zhiyang Lin; Linhan Li; Kaige Song; Bin Yang; Guoqing Zhou; Gengrong Zhang; Jiang Teng; Erlong Wang; Xiaoqiang Liu; Fei Ling; Gaoxue Wang; Tianqiang Liu (Science of The Total Environment, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Overlooked dissemination risk of resistomes in mining soil environments - Li Tian; Jia-nan Lu; Yun Zhang; Qiqing Zhang; Gengbo Jiang; Yalin Yin; Liguan Li; Ying-heng Fei; Ying Yang; Zhepu Ruan; Yongjun Guo; Shizhong Wang; et al. (Journal of Hazardous Materials, 2026)

Tin isotope fractionation in arc magmas controlled by degassing and slab input - Wei-Cheng Jiang; Jia-Xin She; Alexandra Davidson; Chun-Fei Chen; Chris Firth; Simon Turner; Wei-Qiang Li; Trevor Ireland; Paolo A. Sossi; Jing-Hua Wu; Shane Cronin (Geochimica et Cosmochimica Acta, 2026)

Transcriptomic and physiological insights into 1-MCP–mediated delay of postharvest senescence in fresh goji berries under immediate and post-transport treatments - Fei Yao; Tingting Li; Jie Shi; Yafei Li; Li Jiang; Zhicheng Yan; Caie Wu; Gongjian Fan; Xiaojing Li; Dandan Zhou; Kaiping Cong (Food Bioscience, 2026)

Functional characterization of STING in large yellow croaker (Larimichthys crocea), a pivotal regulator associated with TRIF, TRAF3, IRF3, and IRF7 in modulating antiviral signaling - Yi Lin Li; Jia Xi Zhang; Jun Chun Tang; Ying Li; Xuan Zhu; Jian Zhong Han; Yong Hua Jiang; Yi Lei Wang; Peng Fei Zou (Fish & Shellfish Immunology, 2026)

Scaling, performance, and quality: Machine-Learning evidence for how WWTP and compost processes shape microplastics - Ling Shu; Zhoujia Jiang; Yufan Fei; Yating Luo; Da Ouyang; Yuejin Zhang; Jing Li; Haibo Zhang (Environmental Research, 2026)

Ca-O coordination-enhanced spatial confinement in layer-to-cage transformation of alkaline aluminosilicate framework enables synergistic soil Cd sequestration and acidity regulation - Liping Liu; Jiaxin Tian; Yujun Wu; Jiang Tian; Fei Ge; Feng Li; Yun Liu; Shengguo Xue (Chemical Engineering Journal, 2026)

Pueraria-derived nanovesicles engineered to present CSF1 alleviate immune rejection in heart transplantation - Xingyu Lu; Peilin Shi; Jinfeng Zhao; Fei Yu; Yuhang Han; Yidan Wang; Xinrui Yang; Yiran Shi; Tian Li; Shu Jiang; Jincheng Zhang; Zhanxue Xu; et al. (Chemical Engineering Journal, 2026)

Internal expansion growth method for constructing MOF-on-MOF heterointerfaces and the derived materials applied in ultrasensitive Shikonin sensing - Jiejun Li; Yi Jiang; Yurou Zhang; Meijun Ni; Pengcheng Zhao; Junjie Fei; Yixi Xie (Chemical Engineering Journal, 2026)

Thermal resistant flexible sensor with a 3D woven structure based on core-shell triboelectric nanogenerator fibers - Hong Zhou; Chengsi Xu; Saihua Jiang; Shun Li; Fei Xie; Xiao Chen; Wan Zhang; Yang Lan; Yangchun Huang (Chemical Engineering Journal, 2026)

Formation mechanisms of a severe springtime ozone episode in the Beibu Gulf, China: The role of the marine “ozone pool” and regional transport - Runxi Pan; Fei Jiang; Shuzhuang Feng; Dewei Yang; Yuning Xie; Hang Li; Yu He; Mengwei Jia; Yanhong Xie; Bei Chen (Atmospheric Pollution Research, 2026)

Multi-resolution ozone mapping over the Yangtze River Delta (2014–2022) using a data-driven spatial weighting and downscaling framework - Na Yang; Jian Qian; Junyu Wang; Jiayi Chen; Sheng Li; Xin Wang; Chenglin Tao; Nan Wang; Menglu Jiang; Tao Zhang; Fei Yin; Yue Ma (Atmospheric Pollution Research, 2026)

Phage therapy: A novel strategy to combat drug-resistant Salmonella Pullorum infection in chickens - Hongzhe Zhao; Shilong You; Jiahao Fu; Xiaoyu Xiong; Yingying Ma; Xiaona Wang; Rongyan Li; Fei Teng; Mingze Chen; Wei Wu; Guiwei Li; Yanping Jiang; et al. (Veterinary Microbiology, 2026)

Failure characteristics and development mechanism of time-delayed rockburst in a tunnel excavated via the drilling and blasting method: A case study - Lei Hu; Wen-Fei Chang; Ben-Guo He; Wei Zhang; Jun Zhao; Zhi-Bin Yao; Meng-Fei Jiang; Hong-Pu Li; Lian-Jie Fu (Tunnelling and Underground Space Technology, 2026)

Two decades of methane budgets at the sub-national scale in China - Pengfei Zhao; Zhen Zhang; Guanghui Huang; Zhenxuan Wang; Josep G. Canadell; Philippe Ciais; Huilin Chen; Shengqian Chen; Jason Blake Cohen; Fan Dai; Peng Gong; Robert B. Jackson; et al. (Science Bulletin, 2026)

Effects of surfactants with different hydrophilic groups on the combustion and explosion characteristics of coal dust - Bo Ren; Qingman Chen; Bingyou Jiang; Chang-Fei Yu; Haoyang Li; Kunlun Lu; Mingyun Tang (Process Safety and Environmental Protection, 2026)

Effects of salinity and fermentation time on the microbial community, flavor, and metabolites of shrimp paste - Jing-ru Chen; Jia-bo Huang; Jing Li; Shi-meng Sun; Peng-fei Jiang (Food Research International, 2026)

Dual-descriptor-guided acidic electrolyte additives for ultra-stable ah-level zinc-ion batteries - Yuxin Sun; Bin Cai; Fei Yu; Xuesong Li; Wei Lü; Yi Jiang (Chemical Engineering Journal, 2026)

Enhanced leaf area index estimation in the Drip-Irrigated kiwifruit orchard based on optimized multi-source UAV-based indices - Shidan Zhu; Ningbo Cui; Li Guo; Jiujiang Wu; Zhihui Wang; Shouzheng Jiang; Liwen Xing; Zongjun Wu; Fei Chen; Quanshan Liu (Computers and Electronics in Agriculture, 2026)

In situ micro–nano bubbles for enhanced and regenerative lithium extraction from salt lake brines - Jinming Yang; Hao Jiang; Haishen Jiang; Yiran Li; Kai Zhang; Shuang Zhang; Fei Zheng; Yiming Mei; Xianping Luo; Yuhui Liu (Water Research, 2026)

Physicochemical recycling of perlite from agar extraction waste for repeated reuse and its enhancement mechanism on agar quality - Zhipeng Li; Fan Feng; Yi Liang; Danling Tang; Lifen He; Yuanfan Yang; Mingjing Zheng; Qingbiao Li; Xiping Du; Zedong Jiang; Fei Li; Yanbing Zhu; et al. (Waste Management, 2026)

Chemical composition, bioactivity, and applications of Pandanus amaryllifolius leaves: A comprehensive review - Pengyin Li; Tao Fei; Jiamu Kang; Jingtao Cui; Junxia Jiang; Enxi Fu; Weimin Zhang; Tian Li (Trends in Food Science & Technology, 2026)

Impacts of Vehicle Electrification on On-Road Energy Consumption Using Real-World Data - Yun Jiang; Dongli Meng; Fei Peng; Fanghua Chen; Xiao Li; Guohua Song (Transportation Research Part D: Transport and Environment, 2026)

Multifaceted biocontrol mechanisms of Bacillus amyloliquefaciens F028 against Botrytis cinerea in postharvest tomato fruit - Fu-Lai Han; Jin-Xiu Zhao; Ming-Yi Wang; Meng-Fei Li; Zhe Zhang; Xiao-Hang Cui; Yu-Fei Li; Hao-Jie Jiang; Qing-Xue Jiao; Jie Yang; Xin Liu; Guang-Chao Liu (International Journal of Food Microbiology, 2026)

Harnessing endogenous EcHpaBC for P450-Independent dihydroquercetin biosynthesis - Mengyu Jiang; Zefeng Li; Junjie Zhang; Fei Wang; Xun Li; Yu Zhang (Food Bioscience, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

Uranium increases toxin biosynthesis gene expression and cell toxicity in the cyanobacteria Microcystis aeruginosa - Hui Wang; Lu Xiong; Yuxuan Lu; Fengru Li; Shanshan Shen; Yan Tan; Deshuai Zhen; Tangjian Peng; Tianyi Jiang; Fei Yang (Environmental Pollution, 2026)

DOM-mediated stability of manganese in groundwater: Deciphering the antagonistic roles of humic and fulvic acids in CaO2/biochar remediation - Zijun Ye; Meiyang Jiang; Xiaohui Sun; Zhenhao Fan; Haitao Li; Benyi Cao; Fei Wang (Chemical Engineering Journal, 2026)

Transcarotid Artery Revascularization for Asymptomatic Carotid Stenosis: A Systematic Review and Meta-Analysis - Zhi-Cheng Jiang; Qi-Fei Hu; Jia-Ming Huang; Xian-Wei Wang; Tong Lin; Xi-Lin Gao; Jia-Wen Cui; Jing-Lin Zhao; Dong Chen; Shu-Peng Li (Translational Stroke Research, 2026)

Clinical efficacy of Fufang Zaofan Pills and their immunomodulatory effects on peripheral blood dendritic cells in individuals with lower-risk myelodysplastic syndrome - Fei-Fei Zhang; Xiao-Yun Gao; Li-Lai Jiang; Xiu-Wen Yu; Shu-Zhen Yu; Ya-Jun Jiang; Xiu-Hua Han (Journal of Molecular Histology, 2026)

Sex-specific responses of intestinal health, microbiota composition, and transcriptome profiles in golden pompano (Trachinotus blochii) subjected to hypoxia and reoxygenation - Xiao Kun Wang; Shan Ying Han; Ze Xin Zhong; Zeng Tan Hu; Tian Xiu Li; Yue Gu; Chun Xiu Jin; Tian Jiang; Fei Biao Song; Jian Luo; Jun Long Sun (Frontiers in Marine Science, 2026)
Introduction Driven by global climate change and coastal eutrophication, severe hypoxic events have become a primary environmental stressor in marine ecosystems, posing a critical threat to commercially vital teleosts like the golden pompano ( Trachinotus blochii ). Understanding the dimorphic physiological and microbial responses between sexes under such stress is crucial for developing targeted mitigation strategies. Methods Golden pompano were subjected to hypoxia stress (3.0 ± 0.2 mg/L) for 14 days, followed by restoration of dissolved oxygen to normoxic state (7.0 ± 0.2 mg/L) and cultivation for another 14 days. Subsequently, the histology ( n = 3), digestive enzyme activity ( n = 9), microbial composition ( n = 3), and transcriptome ( n = 3) of intestinal tissue were evaluated. Results Hypoxia induces marked physiological stress and a shift toward intestinal dysbiosis across both genders, manifested by damaged intestinal integrity, oxidative stress, and an increased abundance of opportunistic pathogens (e.g., Spirochaetes ). Although reoxygenation further deteriorates the histological condition of female intestinal tissue, it also triggers more significant molecular and enzyme activity rebound effects compared to males. Moreover, females exhibit significant upregulation of lipid metabolism, antioxidant defense mechanisms, and key signaling pathways, suggesting that they may have adopted a high-energy “compensatory recovery” strategy. Correlation analyses reveal that these microbial shifts are closely linked to host metabolic regulation: beneficial bacteria ( Pseudoalteromonas and Lactococcus ) support sterol transport and signaling homeostasis, while opportunistic taxa ( Brevinema ) negatively impact lipid synthesis. Discussion Our findings reveal a distinct gender dimorphism in the hypoxia and reoxygenation response, providing a theoretical foundation for sex-specific management and nutritional interventions in golden pompano aquaculture.

Metabarcoding analysis of eukaryotic microalgae communities in the surface sediments of an integrated multi-trophic aquaculture zone - Yongrui Pi; Fei Wang; Ke Sun; Xin Chen; Bin Li; Tao Jiang (Marine Pollution Bulletin, 2026)

Dynamics and drivers of last-resort antibiotic resistance genes during pilot-scale aerobic fermentation of municipal sludge and subsequent bok choy pot trials - Li-Tao Zhou; Da-Hai He; Jiang Li; Ruo-Xue He; Shi-Jin Ma; Guang-Yu Gong; Xiao-Shuang Zou; Sen Li; You-Fei Zhou; Wei-Jie Hu (Journal of Hazardous Materials, 2026)

Metal-organic frameworks for food safety monitoring: advances in sensing exogenous contaminants - Junhao Wang; Fei Song; Lianzhou Jiang; Hong Wang; Dongze Li; Zhaoxian Huang (Food Chemistry, 2026)

Weak-hydrogen-bond continuum via coordination-induced intramolecular strain for low-temperature Zn-ion batteries - Ruixiang Xu; Fei Yu; Liying Wang; Xijia Yang; Xuesong Li; Wei Lü; Yi Jiang (Chemical Engineering Journal, 2026)

Exposure to magnesium oxide nanoparticles induces mitochondrial dysfunction and apoptosis in fish Megalobrama amblycephala by disrupting magnesium homeostasis - Ling Zhang; Zi-Shang Liu; Si-Si Xiong; Yan-Zou Dong; Yue-Yun Guo; Ding-Dong Zhang; Guang-Zhen Jiang; Wen-Bin Liu; Xiang-Fei Li (Aquatic Toxicology, 2026)

Dynamic Variations of Agricultural Drought and its Response to Meteorological Drought Based on a Three-Dimensional Spatiotemporal Clustering Perspective - Fei Wang; Hexin Lai; Ruyi Men; Zipeng Wang; Yanbin Li; Yunzhong Jiang; Kai Feng; Wenxian Guo; Qingqing Tian; Yanping Qu (Water Resources Management, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Immunogenicity and safety of an Escherichia coli-produced 9-valent HPV vaccine in adolescents aged 9 to 17 compared with young women - Yulin Jing; Xiaowen Hu; Li Zhang; Jiangyahui Wang; Fei Yang; Rong Wang; Ying Jiang; Lingling Nie; Zhongqiang Jin; Xuecheng Liu; Sihai Li; Chao Du; et al. (Science Bulletin, 2026)

The transcription factor SlPLATZ22 negatively regulates salinity tolerance in tomato plants - Xin Li; Fei Ding; Niannian Zhou; Zheng Chen; Jiahui Huang; Fangling Jiang; Carl-Otto Ottosen; Ron Mittler; Rong Zhou; Zhen Wu (Journal of Plant Physiology, 2026)

Per-and poly-fluoroalkyl substances in lung tissues and their association with lung cancer - Xi-Ze Min; Li Ma; Fei Chen; Ying-Hua Hu; Chao Jiang; Yi-Fan Li; Yue Han; Zi-Feng Zhang; Kurunthachalam Kannan (Journal of Hazardous Materials, 2026)

Human Amniotic Mesenchymal Stromal Cells Promote Bone Regeneration via Regulating Ameloblastoma-Derived-Bone Marrow Mesenchymal Cells Crosstalk and Autophagy in Ameloblastoma Microenvironment - Yuhuan Xiao; Xiaofeng Fu; Weina Zhou; Jin Li; Bin Yan; Fei Jiang (Tissue Engineering and Regenerative Medicine, 2026)
Background: Growing evidence validates the vital function of mesenchymal stem cells (MSCs) in tumor development. Our previous findings have illustrated the role of MSCs in the invasion and recurrence of ameloblastoma. Stem cells can be transplanted to release paracrine factors in the tumor microenvironment (TME) to inhibit tumor progression and recurrence. The paracrine function of human amniotic mesenchymal stromal cells (HAMSCs) benefits bone regeneration. However, the dual function of HAMSCs in inhibiting tumor progression and promoting bone regeneration in the TME remains unknown. Methods: To analyze the role of HAMSCS in the cross-talk between mesenchymal ameloblastoma-derived cells (M-AMCs), human bone marrow mesenchymal stem cells (HBMSCs), and HAMSCs, an in vitro co-culture system of M-AMCs, HBMSCS, and HAMSCS was prepared. An in vivo ectopic transplantation model was employed further to detect the therapeutic effect of HAMSCs on bone regeneration. Results: A high-level basal autophagy was detected in the stroma of ameloblastoma. In the in vitro co-culture models, M-AMCs suppressed the proliferation, differentiation, migration, and autophagy of HBMSCs, and conversely, HBMSCs promoted the above phenotypes of M-AMCs. HAMSCs promoted the proliferation, differentiation, migration and autophagy of the co-cultured HBMSCs. Additionally, HAMSCs mediated the cross-talk between M-AMCs and HBMSCs. The in vivo ectopic transplantation model indicated that transplanted HAMSCs promoted bone regeneration by inhibiting the growth of M-AMCs and enhancing autophagy, as well as osteogenesis in bone defects of mice. Conclusions: The interaction of M-AMCs and HBMSCs may be associated with ameloblastoma recurrence. HAMSCs regulate the cross-talk between M-AMCs and HBMSCs to increase the autophagic level in the TME, thus inhibiting the progression and recurrence of ameloblastoma and promoting bone regeneration. Therefore, HAMSC-based therapy provides an alternative to facilitate bone regeneration and repair of ameloblastoma-induced bone defects.

Hydrological system and stability of loess-mudstone interface slopes under rainfall: a bidirectionally coupled model of surface runoff and subsurface seepage - Wenliang Ma; Chunhui Li; Jinfeng Li; Fei Zhang; Yaling Jiang; Xiangzhen Meng; Hairen Wang; Wen Zheng (Bulletin of Engineering Geology and the Environment, 2026)

Associations of adherence to the EAT-Lancet and plant-based diets with mortality and life expectancy: two nationwide cohort studies - Xiaoqin Xu; Jiang Li; Jie Li; Wenqi Shen; Xiao Tan; Fei Xu; Wen Zhang; Ningjian Wang; Yingli Lu; Bin Wang (GeroScience, 2026)

Development of a sex-linked PCR marker for non-invasive and early sex determination in largemouth bass (Micropterus salmoides) - Fei Li; Jianbo Zheng; Shili Liu; Shun Cheng; Wenping Jiang; Meili Chi; Chao Zhu; Miao Peng; Qinghui Meng (Conservation Genetics Resources, 2026)

Design and experiment of sowing depth control system based on forward direction surface slope - Fei Chen; Li Yang; Tao Cui; Dongxing Zhang; Xiantao He; Kailiang Zhang; Yeyuan Jiang; Xiaoshuang Zhang; Xin Wang; Jinsheng Mou (Computers and Electronics in Agriculture, 2026)

Pyocyanin induces rice benzoxazinoid synthesis to co-drive cadmium immobilization in rhizosphere microdomain: Microbial metabolite-mediated spatiotemporal communication mechanisms - Shengwei Yi; Zan Tian; Lanlan Wei; Feng Li; Lizhong Zhu; Fangbai Li; Songxiong Zhong; Fei Ge; Na Liu; Xionghui Ji; Jiang Tian; Yujun Wu (Soil Biology and Biochemistry, 2026)

Deep learning detection and analysis of eddies in the East Greenland marginal ice zone from Sentinel-1 SAR imagery - Fei Jiang; Xiaofeng Li; Yingjie Liu; Yibin Ren (Remote Sensing of Environment, 2026)

LC-MS-based non-targeted metabolomics analysis of sea urchin during frozen storage under different packaging methods - Jia-bo Huang; Yi-hui Tang; Jing Li; Jing-ru Chen; Peng-fei Jiang (Food Chemistry, 2026)

Seawater reforming of ethanol and acetic acid over Ni/SBA-15 catalysts: Salt-induced deactivation pathways - Yunyu Guo; Yueyue Song; Yangfan Zhang; Wenjian Liu; Fei Wu; Chao Li; Yuchen Jiang; Guozhu Chen; Shu Zhang; Xun Hu (Desalination, 2026)

Two new abietane diterpenoids from Salvia cavaleriei var. simplicifolia - Qian Wu; Jie Yang; Mi-Na Yang; Li-Jia Ye; Hong-Fen Jiang; Miao Zhang; Xin Wang; Yi-Nan Yang; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2026)

Neutrophil extracellular traps induce airway epithelial-mesenchymal transition in a neutrophil-dominant asthmatic murine model through Hedgehog/Gli1 pathway - Mengling Xia; Qing Wang; Yixia Jiang; Shan Lu; Fei Xu; Yinan Yao; Yuekang Li; Linying Wu; Jianya Zhou; Jianying Zhou (Inflammation Research, 2026)

Biochar application enhances soil water storage in wet periods but intensifies drought conditions during dry periods in red soils - Yuanhang Fei; Zhipeng Liu; Jun Yi; Dongli She; Weiwen Qiu; Lan Jiang; Muxing Liu; Shenglong Li; Hanjiang Nie; Qi Li; Xin Ni; Hailin Zhang (Soil and Tillage Research, 2026)

Nitrogen and phosphorus additions reshape soil microbial metabolic functions in Qinghai-Tibetan Plateau alpine meadows - Jiayi Zhao; Yuying Jiang; Fei Ren; Lanping Li; Huaihai Chen (Soil Biology and Biochemistry, 2026)

A concept-drift-driven hybrid modeling framework for high-resolution ambient surface NO2 retrieval in Beijing-Tianjin-Hebei Region, China - Junyu Wang; Jian Qian; Jiayi Chen; Caiying Luo; Sheng Li; Na Yang; Ruoyu Li; You Zou; Tao Zhang; Fei Yin; Chenglin Tao; Nan Wang; et al. (Journal of Hazardous Materials, 2026)

Patient-derived 3D bioprinted glioblastoma models with defined physicochemical ECM properties for long-term maintenance and CAR-T therapy evaluation - Xiaohui Li; Fei Zhao; Shengqiang Xu; Chunxia Ji; Zupeng Xu; Zhuoxiao Cao; Yexin Gu; Tianyi Feng; Yanbo Wang; Min Tang; Zhengyu Jiang; Yu Yao; et al. (Chemical Engineering Journal, 2026)

Manganese cycle-mediated synchronous bacteria-algae/anammox coupled denitrification system under low-temperature conditions: Performance and mechanisms - Peng-fei Yu; Dian-lin Jiang; Ding Wang; Xing-guan Ma; Jun-Li; Li-yao Han; Ao Wang; Yu-bo Fu; Xing Jin (Bioresource Technology, 2026)

CSSL-based GWAS identifies SNPs and candidate genes associated with Verticillium wilt resistance in cotton - Youzhong Li; Xiaohui Jiang; Hongyu Cao; Xinyu Zhang; Zhongxu Lin; Qian-Hao Zhu; Yanjun Li; Fei Xue; Shuaishuai Cheng; Feng Liu; Jie Sun (Theoretical and Applied Genetics, 2026)

Integrative Assessment of Interrelated Swimming Performances and their Physiological Basis in Large Yellow Croaker (Larimichthys crocea) - Wei Liu; Junjia Zeng; Jiaxing Liu; Tingsen Jiang; Yacheng Deng; Pengxin Jiang; Yin Li; Ningyuan Ding; Yichen Li; Yujia Chen; Chuan Deng; Haojie Li; et al. (Marine Biotechnology, 2026)

Ocean Heat Content Sets Another Record in 2025 - Yuying Pan; Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Juan Du; Zhankun Wang; Andrea Storto; Karina Von Schuckmann; Yujing Zhu; Michael E. Mann; Jiang Zhu; et al. (Advances in Atmospheric Sciences, 2026)
Global ocean warming continued unabated in 2025 in response to increased greenhouse gas concentrations and recent reductions in sulfate aerosols, reflecting the long-term accumulation of heat within the climate system, with conditions evolving toward La Niña during the year. In 2025, global upper 2000 m ocean heat content (OHC) increased by ∼23 ± 8 ZJ relative to 2024 according to IAP/CAS estimates. CIGAR-RT, and Copernicus Marine data confirm the continued ocean heat gain. Regionally, about 33% of the global ocean area ranked among its historical (1958–2025) top three warmest conditions, while about 57% fell within the top five, including the tropical and South Atlantic Ocean, Mediterranean Sea, North Indian Ocean, and Southern Oceans, underscoring the broad ocean warming across basins. Multiple datasets consistently indicate ocean warming, as measured by 0–2000 m OHC, increased from 0.14 ± 0.03 W m −2 (10 yr) −1 during 1960–2025 to 0.32 ± 0.14 W m −2 (10 yr) −1 during 2005–2025 (IAP/CAS), the latter being consistent with EEI (Earth’s Energy Imbalance) estimates within uncertainties. In contrast, the global annual mean sea surface temperature (SST) in 2025 was 0.49°C above the 1981–2010 baseline and 0.12 ± 0.03°C lower than in 2024 (IAP/CAS; similar in CMA-SST, FY3 MWRI SST, ERSSTv5 and Copernicus Marine data), consistent with the development of La Niña conditions, but still ranking as the third-warmest year on record.

Assimilation overwhelms nitrification in saline wastewater nitrogen removal: From heterotrophic nitrification and aerobic denitrification strains to microbiomes - Mengru Zhang; Wenhao Zhang; Qingyuan Jiang; Chuanfu Zhao; Fei Han; Hao Chen; Yuke Li; Yuping Zhuge; Weizhi Zhou (Water Research, 2026)

An improved spatiotemporal graph neural network framework for water quality assessment - Fei Ding; Haobin Yuan; Mingcen Jiang; Ziyue Luo; Miao Ge; Shilong Hao; Yang Hu; Hanjie Mao; Xin Xie; Wenpan Li; Yong Zhang (Journal of Water Process Engineering, 2026)

Corrigendum to ‘Metabolic flexibility of rhizobacteria drives soil nutrient cycling and enhances rare earth elements hyperaccumulation in ferns colonizing degraded mine ecosystems’ [J. Environ. Manag. 395 (2025) 128013] - Yong-He Han; Xi-Wen Cui; Hai-Bin Han; Yang-Long Jiang; Li-Chao Tong; Jian-Fei Chen; Hong Zhang; Yong Zhang; Zhibiao Chen (Journal of Environmental Management, 2026)

Corrigendum to “Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment” [Chem. Eng. J. Volume 515, 1 July 2025, 163509/CEJ-D-25-01484R1] - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2026)

Novel senescence inducer ICA-11c, a derivative of icaritin, YAP-dependently suppresses hepatocellular carcinoma cells - Hong-fei Chen; Shuai Shen; Shuang-li Wang; Li Ye; Ji-chong Li; Wen-li Cao; Zi-lin Hou; Jian-huan Jia; Qing-bo Liu; Guo-dong Yao; Shao-jiang Song (Chemico-Biological Interactions, 2026)

Genome-wide analysis of Zoysia japonica REVEILLE family identifies ZjRVE8-1 as a positive cold-tolerance regulator - Cuiling Liu; Liangliang He; Ming Jiang; Zhihao Wu; Jieyi Li; Chao Liu; Quanrui Su; Jingyi Sun; Fei Xu; Shu Chen (Plant Cell Reports, 2026)

Biodegradation of bioplastic polycaprolactone by marine bacterium Alteromonas sp. ghpt-2 and its adaptive responses - Guang-Feng Kan; He Lyu; Xiao-Fei Wang; Yue-Xin Li; Kai Yu; Hong Zhang; Ying-Ying Wang; Yan-Xiao Jiang; Jie Jiang (Marine Pollution Bulletin, 2025)

Corrigendum to “Biochar-amended coastal wetland soil enhances growth of Suaeda salsa and alters rhizosphere soil nutrients and microbial communities” [Sci. Total Environ. 788 (2021), 147707] - Jing-Fang Cai; Fan Jiang; Xuan-Shao Liu; Kai Sun; Wei Wang; Ming-Xiang Zhang; Hong-Li Li; Wei-Jing Kong; Fei-Hai Yu (Science of The Total Environment, 2025)

Two new 2-(2-phenylethyl)chromone dimers from agarwood of Aquilaria malaccensis - Lin Zhang; Wei Li; Hao Wang; Jun Zeng; Wen-Hua Dong; Bei Jiang; Jing-Zhe Yuan; Fei Wu; Wen-Li Mei; Hao-Fu Dai (Phytochemistry Letters, 2025)

3D reconstruction of pore throat connectivity in Shale: An SAXS-MICP integrated framework - Linhao Zhang; Shu Jiang; Jiale Fu; Fei Xie; Zhile Han; Zihao Li; Mengdi Sun (Marine and Petroleum Geology, 2025)

Genesis and developmental pattern of Middle Permian dolomite in Northwestern Sichuan, China - Zhidian Xi; Fei Huo; Huachuan Jiang; Xingzhi Wang; Huiwen Huang; Yuhan Huang; Yi Hu; Xueyan Wu; Yang Li; Wenli Xu; Anqing Chen (Marine and Petroleum Geology, 2025)

Metabolic flexibility of rhizobacteria drives soil nutrient cycling and enhances rare earth elements hyperaccumulation in ferns colonizing degraded mine ecosystems - Yong-He Han; Xi-Wen Cui; Hai-Bin Han; Yang-Long Jiang; Li-Chao Tong; Jian-Fei Chen; Hong Zhang; Yong Zhang; Zhibiao Chen (Journal of Environmental Management, 2025)

Molecular sensory basis of the smoky aroma in sesame oil elucidated by combining SAFE-GC-O-MS, σ-τ plot, and computational simulations - Tian-Pei Zhao; Tong-Yu Wang; Yi Jiang; Yi-Fei Wang; Shu-Rui Zhang; Jing-Yu Chen; Yue-Hua Li; Xue-De Wang; Hua-Min Liu; Hong-Wei Liu; Ke-Qing Liu (Food Research International, 2025)

A pH-response nano pesticide delivery system based on ZIF-8: effectiveness, delivery and safety in mustard application - Nan Fang; Jinhua Jiang; Xueping Zhao; Yanjie Li; Xiangyun Wang; Jianzhong Yu; Hongmei He; Hongying Zheng; Fei Yan; Runan Li; Changpeng Zhang (Food Chemistry, 2025)

Functional characterization of two Caspase-1 transcripts that associated with ASC and NLRC3 in apoptosis and inflammatory response in large yellow croaker Larimichthys crocea - Qiu Yu Hu; Kun Huang Han; Qiu Ye Huang; Wen Feng Cui; Qiao Yun Yang; Yi Dan Liu; Shang Qi Zhao; Xian Yuan Zeng; Ying Li; Wen Qi Zha; Yi Lei Wang; Yong Hua Jiang; et al. (Fish & Shellfish Immunology, 2025)

Engineering fast-response thermal control for dynamic gene expression design in Halomonas - Jian-Lian Wu; Ya-Ge Xiao; Bao-Wen Liu; Ling-Fan Tian; Ling-Fei Tian; Yu-Xi Li; Jia-Wen Peng; Hai-Fan Zhu; You-Yang Wang; Zhe-Yi Kuang; Jiang-Jie Tian; Shuai Zheng; et al. (Chemical Engineering Journal, 2025)

Mechanism of acorn ellagitannin regulating rodent population quantity - Yiwen Jiang; Jiaxin Li; Peijie Zhang; Xueying Huo; Fei Yu (Oecologia, 2025)

MSC-Exosomes alleviate cognitive impairment after mild traumatic brain injury by inhibiting ferroptosis via PI3K/AKT/mTOR-mediated upregulation of GPX4 - Haoyang Hu; Mao Li; Yan Wang; Yang Liu; Hong Zhao; Dengfa Zhao; Pengyu Jiang; Xiaoxuan Yang; Xianyang Chen; Fei Yang (Functional & Integrative Genomics, 2025)
Mild traumatic brain injury (mTBI) is a prevalent condition accounting for over 70% of all traumatic brain injury (TBI) cases, and it is a major cause of posttraumatic cognitive impairment. Ferroptosis, a form of regulated cell death characterized by iron-dependent lipid peroxidation, has been implicated in the pathophysiology of mTBI. However, its precise role in mTBI - induced cognitive dysfunction and potential therapeutic strategies remain unclear. This study aimed to investigate the neuroprotective effects of mesenchymal stem cell - derived exosomes (MSC - Exos) against ferroptosis and cognitive dysfunction following mTBI. We established an mTBI rat model and administered MSC - Exos at different doses. Behavioral assessments, histological and molecular biological analyses, and bioinformatics approaches were used. The results showed that mTBI rats exhibited cognitive impairments, increased lipid peroxidation, and reduced GPX4 expression. MSC - Exos treatment improved cognitive function in a dose - dependent manner, attenuated lipid peroxidation, and restored GPX4 expression. Transcriptomic and bioinformatic analyses revealed that MSC - Exos activated the PI3K/AKT/mTOR signaling pathway, which upregulated GPX4 expression and inhibited ferroptosis. In conclusion, MSC - Exos alleviate cognitive deficits after mTBI by inhibiting ferroptosis via PI3K/AKT/mTOR - mediated upregulation of GPX4, providing a novel therapeutic strategy for mTBI.

High Quality, Granular, Timely, Trustworthy and Efficient Vertebrate Species Distribution Data Across a 30,000 km 2 Protected Area Complex - Yinqiu Ji; Alex Diana; Xueyou Li; Eleni Matechou; Jim E. Griffin; Shuwei Liu; Mingjie Luo; Chunying Wu; Ru Bai; Chenyang Yao; Tingting Yin; Feng Dong; et al. (Ecology Letters, 2025)
The routine generation of species distribution data at scale remains a challenge. We used aquatic environmental DNA metabarcoding to sample vertebrate species across the 30,000 km 2 Gaoligongshan region along the China–Myanmar border. In just 56 calendar days (33 researcher‐field‐days + 69 researcher‐lab‐days), we detected 389 vertebrate species, of which 35 are Red‐Listed. We introduce the ‘eDNA‐aware’ OccPlus occupancy model, which accounts for false‐negative and false‐positive error in the field and lab. OccPlus leverages the taxonomic breadth of eDNA datasets by using ordination to estimate species occupancies. We recover known biogeographic patterns and find that native terrestrial and fish species have higher occupancies inside protected areas while domesticated species and non‐native fishes have higher occupancies outside them. Our study demonstrates how eDNA metabarcoding can obtain high‐quality, granular, timely, trustworthy and efficient species distribution data to facilitate nature conservation and restoration.

The connection between skeletal muscle and spinal canal membrane of Takifugu rubripes and its anatomical and physiological significance - Yang Song; Wen-Bin Jiang; Yu-Yu Xiong; Chun-Zhuo Shi; Hua-Xun Lai; Jing-Xian Sun; Lin-Lin Chen; Bo Liu; Yan-Yan Chi; Ji-Hang Li; Yi-Tong Sun; Xu-Hui Zhang; et al. (Frontiers in Marine Science, 2025)
Introduction The myodural bridge (MDB) is considered one of the circulatory dynamics of cerebrospinal fluid (CSF). Initially identified in the human neck, it has since been documented across diverse vertebrates, including fish with analogous “MDB-like” structures. The teleost Takifugu rubripes , which exhibits a high degree of genetic homology with humans, serves as an excellent model for such comparative studies. Investigating its MDB-like structure can therefore provide a morphological basis for elucidating the mechanism of CSF circulation and its evolution during the vertebrate land–water transition. Methods In this study, the morphology, development, and ultrastructure of MDB-like structure of Takifugu rubripes were explored. Three fresh adult T. rubripes were selected for gross anatomy. After incubation, 33 T. rubripes aged 13–120 days after hatching (dah) were fixed in 10% formalin solution. The samples aged 50–120 dah were further decalcified with EDTA for histological paraffin sectioning and Masson staining. Four cases aged 106 dah were fixed with 2.5% glutaraldehyde, two of which were observed by scanning electron microscopy, and two cases were observed by transmission electron microscopy. Results Through light microscopy and electron microscopy, the results of the current study is that there are three types of fiber connections (MDB-like) between skeletal muscle and the spinal canal membrane in T. rubripes : (1) The fibers from the myocomma attach to the spinal canal membrane; (2) The epimysium connects to the spinal canal membrane directly or connects to the spinal canal membrane through reticular, filamentous fibers, or fibers emitting from the perimysium; and (3) The fibers from the end of the muscle bundle stop at the spinal canal membrane. These connections mainly exist on the sides of each vertebral interspace and may function similarly to the MDB. Discussion Developmentally, “MDB-like” structures appeared in T. rubripes hatched at 18 dah, began to transmit force at 21 dah, and may have a positive correlation in development with the muscle and spinal canal membrane. This experiment provides developmental morphological information for comparative studies on the conservation and interspecies differences of MDB in evolution and provides informational support to explore the physiological function of MDB in humans.

Analysis of cellular and gene therapy product reviews in the United States - Cheng-Fang Weng; Jhe-Yuan Dong; Shiuan-Fei Lin; Ai-Lei Jiang; Yu-Li Cheng; Lin-Chau Chang (Regulatory Toxicology and Pharmacology, 2025)

Elucidating the impact of salt concentration on volatile flavor profiles and microbial dynamics in fermented cockle paste using GC-IMS and high-throughput 16S rDNA sequencing - Shi-meng Sun; Jia-bo Huang; Jing Li; Jing-ru Chen; Peng-fei Jiang (Food Research International, 2025)

Soil pH and temperature dominate topsoil particulate and mineral-associated organic carbon over the Yellow River Basin - Ying Ma; Jinzhao Liu; Hong Yan; Li Guo; Ji Chen; Fei Zhang; Zhiyun Jiang; Xiong Xiao; Ji Liu; Wenbo Deng; Zhisheng An (CATENA, 2025)

The recovery mechanism of granular sludge fragmentation and re-granulation caused by long-term high-concentration organic matter erosion in the SAD process: performance, sludge evolution, and metagenomic sequencing - Peng-fei Yu; Ding Wang; Yu-bo Fu; Xing-guan Ma; Hao Zheng; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Xing Jin (Bioresource Technology, 2025)

Calibration of the Edinburgh Elasto-Plastic Adhesion contact model for modelling clay-moist soil with high moisture content - Xuan Deng; Wencheng Wu; Jiawei You; Rui Jiang; Mengliang Li; Ju Li; Youfeng Tao; Hong Cheng; Wei Zhou; Fei Deng; Yong Chen; Wanjun Ren; et al. (Computers and Electronics in Agriculture, 2025)

Effects of designed species diversity on community resilience to weed invasion - Cangshuan Li; Peilu Huang; Bingrong Chen; Hanlin Chen; Zuyin Li; Fei Wang; Mingyu Jiang (Urban Forestry & Urban Greening, 2025)

The influence of water flow disturbance form on the granulation of algae sludge: Granulation property, treatment effect and algae biological structure - Peng-fei Yu; Ao Wang; Hai-wen Sun; Ding Wang; Xing-guan Ma; Yu-jia Wang; Bo-mei Hu; Li-yao Han; Yu-bo Fu; Dian-lin Jiang; Shi-gang Tu (Journal of Water Process Engineering, 2025)

Dilation of the distal convoluted tubule induced by repeated heat exposure in rats model - Zhongyou Li; Taoping Bai; Wentao Jiang; Fei Yan; Lingjun Liu; Chong Chen (Journal of Thermal Biology, 2025)

Unraveling the enrichment mechanisms of U, Re, Se and V in the Bayinqinggeli Deposit, Northern Ordos Basin through in situ mineralogical analysis - Xiao-Wen Hu; Ming-Xing Ling; Jian-Bing Xu; Fei Xia; De-Ru Xu; Ya-Lun Li; Xiao-Yong Yang; Chao Lu; Hua-Ming Li; Zhen-Cheng Li; Long-Hui Wang; Feng Zhang; et al. (Journal of Geochemical Exploration, 2025)

Separation and recovery of iron from vanadium extraction tailing slag by P204-P507 mixture collector flotation process - Yi-bo Wang; Jing-wei Li; Xiao-long Liu; Xin-fei Jiang; Yin-he Lin; Zhi Tian; Jun-jie Yin; Bing-qing Huang; Jia-xin Yang; Chen-xuan Wang; Zi-wang Wu; Shi-xing Ma; et al. (Journal of Environmental Chemical Engineering, 2025)

The investigation of phosphonate-decorated covalent organic frameworks with photo responsive effect for the effective adsorption and separation towards rare earth elements - Runhan Yan; Hongmin Cui; Jingsong Shi; Wei Jiang; Fei Gao; Nanfu Yan; Yaqing Weng; Minghui Li; Yuewei Liu; Ting Cheng (Journal of Environmental Chemical Engineering, 2025)

Shaped cross sectional fibers in oil spillage monitoring: From early stage qualitative detection to onsite quantitative assessment - Mingyu Zhao; Fei Jiang; Zheng Li; Yeqiang Lu; Guojun Jiang; Zhijuan Sun; Lixin Xue (Journal of Environmental Chemical Engineering, 2025)

Physical modification of corbicula fluminea protein hydrolysates by interacting with chlorogenic acid: Impacts on antioxidant activity and digestion behaviors - Fei Wang; Xuemei Liu; YanYan Wu; Lili Chen; Meilan Yuan; Yong Jiang; Li Zhao; Chunqing Bai (Food Chemistry, 2025)

Transcriptome analysis of medaka spermatogonial stem cell line (SG3) infected with ranaviruses in vitro - Linwen Cheng; Shiwen Zhang; Zhongyi Liu; Qiqi Jiang; Mingyou Li; Fei Ke; Lang Gui (Fish & Shellfish Immunology, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

An ingenious structural design of NiCu-MOF bar-like nanosheet array: harnessing synergistic effects to attain exceptional ammonia oxidation performance - Guang-Lan Li; Yu-Hui Shi; Ri-Yang Huang; Tian-Ge Ma; Qian Zhuo; Ling Xu; Fei Jiang; Yu-Kun Zhai; Yong-Hou Xiao; Hong-Jiang Li; Yang Yan; Yun Zhao (Chemical Engineering Journal, 2025)

Modification effects of regional temperature and humidity on the relationship between daily mortality and short-term coexposure to fine particulate matter and ozone - Jing Zeng; Jian Qian; Jiayi Chen; Sheng Li; Junyu Wang; Menghan Yao; Qianqian Du; Na Yang; Tao Zhang; Fei Yin; Chenglin Tao; Xinyin Xu; et al. (Atmospheric Environment, 2025)

Transcriptomic evidence from peripheral blood reveals nonlinear gene expression trajectories of aging in female rhesus macaques - Chong-Jun Weng; Long-Bao Lv; Li-Qin Yang; Long Zhao; Zheng-Fei Hu; Si-Yu Ma; Yi-Jiang Li; Wen-Xian Xiao; Yun Wang; Xin-Tian Hu; Gong-Hua Li; Qing-Peng Kong (Science China Life Sciences, 2025)

BDNF Alleviates Noise-Induced Cochlear Synaptopathy Through Inhibition of Autophagy - Fei Wang; Qianru Yu; Yangtuo Luo; Rui Guo; Liyuan Wu; Xinyu Song; Yang Li; Shuna Li; Ke Liu; Xuejun Jiang (Molecular Neurobiology, 2025)

Synaptotagmin-like 5 is a potential biomarker and correlates with immune infiltrates in thyroid carcinoma - Xiaohui Zhu; Xia Li; Hengfeng Cui; Haiyan Wu; Dongmei Jiang; Yuying Wang; Fei Hua (Journal of Molecular Histology, 2025)

Changes in the physiological indicators and gene expression for grass carp (Ctenopharyngodon idella) in response to alkaline stress - Qi Chen; Jianbo Zheng; Yi Xu; Fei Li; Shili Liu; Wenping Jiang; Meili Chi; Shun Cheng; Haiqi Zhang (Aquaculture International, 2025)

Targeting cuproptosis in liver cancer: Molecular mechanisms and therapeutic implications - Yun-Fei Zhou; Yi-Wen Zhu; Meng-Yuan Hao; Hong-Jie Li; Hang-Shen Han; Yan-Ge Li; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Apoptosis, 2025)

A Review of Atmospheric Micro/Nanoplastics: Insights into Source and Fate for Modelling Studies - Fei Jiang; Chengze Gao; Arthur W. H. Chan; David O. Topping; Hongliang Zhang; Weijun Li; Hugh Coe; Xiaohong Liu; Joseph Ching; Zhonghua Zheng (Current Pollution Reports, 2025)
Purpose of Review Micro/nanoplastics (MNPs), as emerging pollutants, have attracted increasing attention due to their potential adverse effects on human health, ecosystems, and climate. The rapid, turbulent, and large-scale nature of atmospheric transport facilitates both horizontal and vertical movement of MNPs over long distances within a short time, largely independent of topographical constraints, thereby accelerating their global cycle and exacerbating their impacts. Despite growing interest, our understanding of the atmospheric lifecycle of MNPs remains limited. This review aims to synthesise recent advances in understanding the atmospheric lifecycle of MNPs, including their emission sources, long-range transport characteristics, and driving mechanisms. It also evaluates the key sources of uncertainty—particularly those related to emission flux estimates—and provides corresponding recommendations for future research. Recent Findings Current research on the atmospheric processes of MNPs primarily relies on a combination of observational data and numerical modelling. Two major uncertainties in atmospheric micro/nanoplastic (AMNP) emissions persist: the wide variability in marine emission estimates, which span four orders of magnitude, and the unresolved question of whether terrestrial or marine sources are the dominant contributors to AMNP emissions. Furthermore, this review highlights critical factors driving these uncertainties, including limited data availability, inconsistencies in observational methodologies, oversimplified simulations, and gaps in understanding atmospheric cycling mechanisms. Additionally, variations in the particle size ranges targeted by different observational and modelling studies hinder cross-comparisons and model evaluations, representing another important source of uncertainty. Summary AMNP research is constrained by multiple uncertainties that hinder a comprehensive understanding of their emissions, transport, and fate. To address these issues, we call for establishing a global network of standardised observations, improving sampling and simulation practices, and incorporating artificial intelligence. These strategies will enhance our understanding of the complete atmospheric cycle of MNPs, paving the way for more effective environmental management and better-informed policy decisions.

CCP domain containing protein from complement factor H of Paralichthys olivaceus has potential effects against Edwardsiella piscicida infection - Xuan-yue Wang; Yu-ting Du; Xin-yi Jiang; Zhuo-ran Ma; Chao-ran Zhang; Xue-peng Li; Zeng-zhi Yuan; Mo-fei Li (Aquaculture, 2025)

Quaternary sedimentary evolution and source apportionment in the northwestern South China Sea: Evidence from geochemical and zircon U-Pb data - Peng-Fei Xiong; Shu Jiang; Cong Cheng; Kai Zhang; Xiao-Yu Fang; Tao Jiang; Jia-Le Fu; Hong-Ji Liu; Xin-Rui Zhou; Xu-Shen Li (Quaternary Science Reviews, 2025)

Unveiling the biogeography of ammonia-oxidizing prokaryotes (AOPs) in the South China Sea: Novel lineages and their ecological niches - Yuexi Ma; Cuihong Jiang; Jiapeng Wu; Xiaoyi Li; Fei Ye; Xiaomei Shen; Yu Wang; Yiguo Hong (Marine Environmental Research, 2025)

Corrigendum to “Enhancing Sulfate Reduction in Microbial Electrolysis Cells: The Impact of Intermittent Electric Field and Extreme Conditions on Reaction Mechanisms and Functional Genes” [Journal of Water Process Engineering, volume 71, March (2025) 107199] - Zhibin Xia; Liang Qiao; Fei Chen; Xu Jiang; Pingting Li; Xing Zong; Yihan Wang; Feihong Wang; Luyan Zhang; Xiaolong Bai; Ye Yuan; Tianming Chen; et al. (Journal of Water Process Engineering, 2025)

Revisiting the quantitative relationship between groundwater evapotranspiration and water table depth: A numerical study - Shu-Cong Tan; Xiao-Wei Jiang; Zhi-Yuan Zhang; Peng-Fei Han; Xu-Sheng Wang; Li Wan; Yi-Jian Zeng (Journal of Hydrology, 2025)

Cr(VI)-bioremediation mechanism of a novel strain Bacillus sp. Cr02 with simultaneous aerobic/anaerobic reduction for Cr(VI) from soil to groundwater - Liping Liu; Rui Liu; Fang Wang; Yujun Wu; Fei Ge; Jiang Tian; Feng Li; Shengguo Xue (Journal of Hazardous Materials, 2025)

Research on the path of atmospheric pollutants and greenhouse gas cooperative control in megacities - A case study of Chengdu - Zihang Zhou; Chengwei Lu; Ye Deng; Qinwen Tan; Xia Jiang; Bin Zhao; Fei Fang; Hefan Liu; Danlin Song; Xiaoling Zhou; Xuan Liu; Xin Zhang; et al. (Atmospheric Pollution Research, 2025)

Long-term elevated CO2 and warming alter the network complexity and composition of bacterial community in a paddy field - Jiahui Li; Jiayi Xiong; Yexin Hu; Qingsong Ba; Feng Li; Fei Zhang; Li Jiang; Yuan Liu (Applied Soil Ecology, 2025)

A Seismic Multi-Attribute Sandbody Identification Method Based on the LightGBM-RFECV Coupling Algorithm - Teng-fei Ren; Zhi-bing Feng; Ying Zhang; Xiang Zhang; Li Jiang; Yuan-li Ning; Jing-yi Wang; Jian Ding; Zeng-shuo Qi (Applied Geophysics, 2025)

Viral diversity and auxiliary metabolic genes in rare earth element mine drainage in South China - Chang Hu; Jia-nan Lu; Ziwu Chen; Li Tian; Yalin Yin; Gengbo Jiang; Ying-heng Fei; Ye-Tao Tang; Shizhong Wang; Chao Jin; Rongliang Qiu; Yuanqing Chao (Water Research, 2025)

UGPase: A novel molecule that regulates LPS synthesis, virulence, and immunogenicity of Brucella melitensis - Si Chen; Yuxin Liu; Yang Gao; Dong Zhang; Ru Zhang; Fei Tu; Nan Li; Qingkui Jiang; Linna Liu; Yanling Yang (Veterinary Microbiology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Ni nanoparticles inlaid in amorphous silicon nitride-derived nickel phyllosilicate: A highly stable and active catalyst for ammonia decomposition - Han Yang; Jing Li; Qiang Chang; Qun-chao Zhao; Meng-na Zhang; Huan-jiang Wang; Cheng-hua Zhang; Fei Wang; Xiao-dong Wen (Fuel, 2025)

High-quality Antarctic krill oil OSA starch microcapsules prepared by multi-scale immobilized enzyme nanoflowers with selective catalytic activity - Yuewei Jiang; Chen Huang; Ziyi Liu; Ziyi Shen; Hui Gong; Bo Chen; Yingying Su; Chao Shi; Jinghui Zhou; Xu Fei; Yao Li (Food Chemistry, 2025)

Lavender-like NiV-LDH@P,Se-doped VNi-MOF heterostructure as high-performance electrode material for supercapacitor - Yanqiu Xie; Xin Gao; Haoze Wang; Carlos Garcia Nuñez; Fan Jiang; Qian Li; He Bai; Fei Yao; Hongyan Yue (Chemical Engineering Journal, 2025)

Research progress of high-strength self-healing polymer materials: Balance between mechanical strength and self-healing efficiency - Zhi-Hui Yan; Hua-Xin Huang; Guo-Quan Ding; Shan-Shan Dong; Ke-Jin Jiang; Yu-Ying Li; Yang Liu; Yan Jiang; Shuang-Fei Wang; Guo-Hua Hu; Jun Du; Shi-Xian Zhang; et al. (Chemical Engineering Journal, 2025)

Recyclable flame retardant, luminescent, and transparent thermoplastic polyurethanes: applications in light conversion films for flexible solar cells - Li-Wei Su; Ming-Hao Liu; Yang Jing; Peng-Yu Huang; Bo Jiang; Rui-Guang Xing; Xin Ge; Ya-Hui Li; Jin-Xiao Bao; Gao-Fei Pan (Chemical Engineering Journal, 2025)

Chemical composition and chemotaxonomic studies on the roots of Angelica acutiloba - Zhi-Xia Sun; Fei-Fei Geng; Han-Yu Zhang; Yong-Hu Chen; Zhe Jiang; Xue-Zheng Li (Biochemical Systematics and Ecology, 2025)

GMNN mutations cause female infertility characterized by preimplantation embryo arrest through regulating DNA re-replication - Honghui Zhang; Wei Su; Xiaohong Jiang; Yang Wang; Bohan Yang; Xian Wan; Cheng Li; Shuai Zhao; Changlong Zhang; Shigang Zhao; Yuehong Bian; Mei Li; et al. (Science China Life Sciences, 2025)

P2X7 receptor is essential for ST36-attenuated cardiac fibrosis upon beta-adrenergic insult - Ting Zhang; Jing Lv; Zhong-yue Liu; Qiu-lian Lei; Ze-fei Jiang; Xiao-xiang Sun; Xing Yue; Xuan Li; Ke-li Zhu; Yun-kuan Yang; Ling Luo; Xin Cao (Purinergic Signalling, 2025)

Combined effects of multifactorial drivers on soil organic carbon retention: the underestimated role of reactive minerals in arid ecosystems - Yuanqing Tang; Fei Xie; Fengjiao Wang; Zhongli Wang; Yangzheng Liu; Xinyue Jiang; Zhiyong Li; Wenhong Ma; Cunzhu Liang; Lixin Wang; Wei Wang; Frank Yonghong Li; et al. (Plant and Soil, 2025)

Detecting Deleterious Recessive Variants in Large Yellow Croaker Using Data from 7337 Individuals - Zhou Jiang; Ji Zhao; Ning Li; Jiaying Wang; Fei Pu; Hongshu Chi; Peng Xu; Tao Zhou (Marine Biotechnology, 2025)

Recommendations of Stable Mg, Si, V, Fe, Cu, Zn, Rb, Sr, Ag, Cd, Ba, and U Isotope Compositions for Multiple Geological References - Jinting Kang; Xuqi Chen; Xi Deng; Yuan Fang; Haichuan Jiang; Chengyihong Liu; Cuihua Luo; Xing Li; Yuchao Lin; Zhaoqi Ren; Jiaru Sheng; Xue Tang; et al. (Journal of Earth Science, 2025)

Isoptericola rhizosphaerae sp. nov. and Isoptericola aurantiacus sp. nov. two novel bacteria isolated from rhizosphere soil - Haifei Liu; Quan Yang; Jiawei Li; Fei Yang; Caifei Li; Ding Li; Ying Sun; Lifang Yang; Mingguo Jiang (Antonie van Leeuwenhoek, 2025)

Effect of wave height on seismic fragility of subsea tunnels in sandy seabed - Ling-Yu Xu; Ju-Ping Xi; Jia-Wei Jiang; Fei Cai; Yong-Yi Li; Guo-Xing Chen (Ocean Engineering, 2025)

Boosting virus enrichment with macroporous magnetic sorbent based on ketoenamine covalent organic framework - Bo'ou Li; Fei Wang; Xiaonan Dong; Yuchang Li; Tao Jiang; Xiaojie Ma; Xiaoping Kang; Bo Wang (Journal of Hazardous Materials, 2025)

SEBS-amended in-situ mixed wall material for diesel-contaminated groundwater management - Zhe-Yuan Jiang; Xian-Lei Fu; Fei Jin; Chi Che; Zhong-Yuan Li; Guojun Cai; Yan-Jun Du (Journal of Hazardous Materials, 2025)

Fluid and mineral inclusions of charoitite deposit in the Murun alkaline-carbonatite complex, Eastern Siberia, Russia - Emilia Yu. Dokuchits; Shao-Yong Jiang; Suo-Fei Xiong; Aleksandr Stepanov; Irina Zhukova; Wen-Tian Li (Journal of Geochemical Exploration, 2025)

Association between serum elementomics of 48 elements and female fecundity: evidence from a nested case-control study in China - Tian Tian; Fang Liu; Li Li; Jing Wei; Kailibinuer Kayimu; Yu Fu; Huahua Jiang; Fei Kong; Rui Yang; Yuanyuan Wang; Xiaoyu Long; Jie Qiao (International Journal of Hygiene and Environmental Health, 2025)

Correction for calcium interference in the 40Ar/39Ar dating method - Wan-Feng Zhang; Jun-Jie Wang; De-Wen Zheng; Ming Xiao; Jia Zhang; Jun-Jie Li; Yu-Lian Zhang; Ying-De Jiang; Fei Su; Li Li; Yi-Gang Xu (Icarus, 2025)

Effect of air frying on in vitro digestion and transport properties of scallop (Patinopecten yessoensis) adductor muscles: Insights from peptidomics analyses - Zi-Ye Wang; Qian Wang; De-Yang Li; Yu-Xin Liu; Lei Qin; Peng-Fei Jiang; Da-Yong Zhou (Food Chemistry, 2025)

Tentative characterization of three novel coumaroyl glucoside β-carboline alkaloids and discovery of hypoglycemic compounds from Nitraria tangutorum Bobr. Fruit - Huilan Yue; Jiaxin Li; Li Wu; Fei Wang; Zhen Li; Sirong Jiang; Xiaohui Zhao (Food Chemistry, 2025)

NLRC3 regulates RIP2, STING, TBK1, and TRAF6 mediated type I IFN signaling and inflammatory response in large yellow croaker Larimichthys crocea - Yu Qing Xu; Ying Li; Kun Huang Han; Jia Xi Zhang; Kai Qing Li; Jing Jiang; Zhao Han Sun; Yi Lei Wang; Yong Hua Jiang; Peng Fei Zou (Fish & Shellfish Immunology, 2025)

Alveolar surfactant-mimicking inhaled biomimetic nanovaccine with alveolar macrophage-targeting property potentiates anti-mpox immunity - Bin Li; Jiamei Wang; Judun Zheng; Wei Wang; Lingjie He; Yan Yan; Xinting Fu; Xingjie You; Man Gu; Han Duan; Yue Jia; Qin Gu; et al. (Chemical Engineering Journal, 2025)

Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia-bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2025)

Ratiometric fluorescent nanoprobes based on lanthanide coordination polymers for visual intelligent detection of phosphate - Yongxin Li; Rongrong Zhou; Fei Xue; Ning Bi; Lina Zhang; Qianyang Li; Kai Shi; Jiang Wu; Lei Jia; Jun Xu (Chemical Engineering Journal, 2025)

In situ monitoring of HCO3−, CO32− and NO3− dynamics during microalgae culture by UV resonance raman spectroscopy - Fei Zhang; Xun Wang; Yu Zhang; Zhen Zhu; Yiming Jiang; Guoqing Jia; Xupeng Cao; Fengtao Fan; Can Li (Algal Research, 2025)

Cytotoxicity phenylpropanoid amides from the seed of Cannabis sativa L - Ao-Fei Wang; Juan Pan; Xiang Liu; Xin-yuan Li; Peng Jiang; Meng-Meng Li; Wei Guan; Qing-Shan Chen; Li-li Zhang; Hai-Xue Kuang; Yan Liu; Bing-You Yang (Natural Product Research, 2025)

Advances in surface water and ocean topography for fine-scale eddy identification from altimeter sea surface height merging maps in the South China Sea - Xiaoya Zhang; Lei Liu; Jianfang Fei; Zhijin Li; Zexun Wei; Zhiwei Zhang; Xingliang Jiang; Zexin Dong; Feng Xu (Ocean Science, 2025)
The recently launched Surface Water and Ocean Topography (SWOT) satellite mission has reduced the noise levels and increased resolution, thereby improving the ability to detect previously unobserved fine-scale signals. We employed a method to utilize the unique and advanced abilities of SWOT to validate the accuracy of identified eddies in merged maps of a widely used Archiving, Validation, and Interpretation of Satellite Oceanographic (AVISO) data product and a newly implemented two-dimensional variational method (2DVAR), which uses a 1/12° grid and reduces decorrelation of spatial length scales. SWOT data are more likely to provide detailed comparisons of eddy boundaries for fine-scale to mesoscale structures compared with conventional in situ data (e.g., drifting buoys). The validation results demonstrate that, compared with AVISO, the 2DVAR method exhibited greater consistency with the SWOT observations, especially at small scales, confirming the accuracy and ability of the 2DVAR method in the reconstruction and resolution of fine-scale oceanic dynamical structures.

Curcumin activates the JAK-STAT signaling pathway to enhance the innate immune response against porcine epidemic diarrhea virus infection in vivo and in vitro - Qiancheng Jiang; Xiangyang Liu; Jianbo Yuan; Shujuan Zhang; Yiling Zhang; Zifei Kan; Zheng Niu; Li Zhang; Xia Hu; Yang Zhou; Jing Wang; Fei Li; et al. (Veterinary Microbiology, 2025)

Discovery of structurally intriguing diterpenoids as anti-neuroinflammatory agents from mangrove plant Excoecaria agallocha L. via inhibiting macrophage polarization and inflammasome - Jun-Yi Li; Ming-Bin Chen; Ting-Ting Fu; Fei-Fei Liu; Jin Liu; Cong-Jun Xu; Jing Zhou; Yong Rao; Zhong-Ping Jiang; Ling Huang (Phytochemistry, 2025)

Pan-genome and haplotype map of cassava cultivars and wild ancestors provide insights into its adaptive evolution and domestication - Zhiqiang Xia; Zhenglin Du; Xincheng Zhou; Sirong Jiang; Tingting Zhu; Le Wang; Fei Chen; Luiz Carvalho; Meiling Zou; Luis Augusto Becerra Lopez-Lavalle; Xiaofei Zhang; Liangye Xu; et al. (Molecular Plant, 2025)

Optimization of graph wavenet model for dissolved oxygen prediction using self-distillation and whale optimization algorithm - Fei Ding; Haobin Yuan; Mingcen Jiang; Zhiyuan Yang; Hongfei Liu; Shilong Hao; Liangyao Chen; Bing Hao; Xin Xie; Wenpan Li; Yong Zhang (Journal of Water Process Engineering, 2025)

Nanospecific effect rather than dissolved Cu2+ dominates the impact of CuO nanoparticles on soil microbiota - Yiguang Qian; Weixin Jiang; Ruhan Li; Fan Liu; Siyue Li; Fei Wang (Journal of Hazardous Materials, 2025)

A “three-in-one” detection platform based on cerium-coated metal-organic framework for multimodal glyphosate detection - Fei Tong; Wanqi Jiang; Hui Li; Xiyao Liang; Chuang Jiang; Yaqing Xiao; Xinying Sheng; Ruyan Hou; Xiaochun Wan; Yingnan Liu (Journal of Hazardous Materials, 2025)

Microbial agents assisted aerobic co-composting of sheep manure and furfural residue: Maturation enhancement and microbial dynamic - Mao Li; Lingwei Jiang; Fei Li; Xuejun Zhang; huanjun Zhao; Na Duan (Journal of Environmental Chemical Engineering, 2025)

Occurrence, molecular characterization and tolerance of Cronobacter spp. isolated from fermented corn products in China - Biqi Liu; Peng Fei; Nuo Xu; Yajing Chang; Mingwei Qiao; Zhe Li; Yujun Jiang; Ling Guo; Stephen J. Forsythe; Xiaofang Tong (Food Microbiology, 2025)

Gas permeability and microscopic mechanisms of Xanthan gum-amended compacted lean clay as a gas barrier material - Ying-Zhen Li; Jia-Lei Wan; Fei Jin; Krishna R. Reddy; Ning-Jun Jiang; Yan-Jun Du (Engineering Geology, 2025)

Computational design and efficacy assessment of Bufalin-Dendrimer nanoformulation for enhanced cancer therapy - Yurong Sun; Yinhua Lin; Huaitao Sun; Junfa Yang; Hui Cheng; Jia Yi; Wenqiang Li; Gen Lu; Cheng Zhao; Yuge Jiang; Xinyu Zhao; Qinglin Li; et al. (Chemical Engineering Journal, 2025)

Record High Temperatures in the Ocean in 2024 - Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Huai-Min Zhang; Andrea Storto; Karina Von Schuckmann; Yuying Pan; Yujing Zhu; Michael E. Mann; Jiang Zhu; Fan Wang; et al. (Advances in Atmospheric Sciences, 2025)
Heating in the ocean has continued in 2024 in response to increased greenhouse gas concentrations in the atmosphere, despite the transition from an El Niño to neutral conditions. In 2024, both global sea surface temperature (SST) and upper 2000 m ocean heat content (OHC) reached unprecedented highs in the historical record. The 0–2000 m OHC in 2024 exceeded that of 2023 by 16 ± 8 ZJ (1 Zetta Joules = 10 21 Joules, with a 95% confidence interval) (IAP/CAS data), which is confirmed by two other data products: 18 ± 7 ZJ (CIGAR-RT reanalysis data) and 40 ± 31 ZJ (Copernicus Marine data, updated to November 2024). The Indian Ocean, tropical Atlantic, Mediterranean Sea, North Atlantic, North Pacific, and Southern Ocean also experienced record-high OHC values in 2024. The global SST continued its record-high values from 2023 into the first half of 2024, and declined slightly in the second half of 2024, resulting in an annual mean of 0.61°C ± 0.02°C (IAP/CAS data) above the 1981–2010 baseline, slightly higher than the 2023 annual-mean value (by 0.07°C ± 0.02°C for IAP/CAS, 0.05°C ± 0.02°C for NOAA/NCEI, and 0.06°C ± 0.11°C for Copernicus Marine). The record-high values of 2024 SST and OHC continue to indicate unabated trends of global heating.

Self-assembled nanoparticle vaccine based on the grass carp ferritin remarkably enhance the protective immune responses against GCRV type II infection - Fei-Fan Xu; Zhu-Yang Deng; Jing-Kai Li; Le-Yang Chen; Yong-Qi Liu; Hai-Feng Jiang; Bin Zhu (Aquaculture, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Psychedelics for treating psychiatric disorders: from circuit mechanisms to applications - Jie Li; Yuting Jiang; Dan Cheng; Jianjun Cheng; Ji Hu; Xiaohui Wang; Ti-Fei Yuan (Science Bulletin, 2025)

Differentiation of Citri Reticulatae Pericarpium varieties via HPLC fingerprinting of polysaccharides combined with machine learning - Min-yong Zhong; Meng-ning Li; Wen-shu Zou; Si-qi Hu; Jiang-nan Luo; Qing-xiang Jiang; Qiu-fang Cao; Long-fei Lin; Zhi-xin Wang; Hui Li; Wen-wen Deng (Food Chemistry, 2025)

The importance of interface interactions in flexible sensing materials: classification, effect, and application - Fei Chen; Fangcheng Qiu; Xiucun Li; Yufeng Song; Xiao Liu; Hong Jiang; Hongbin Liu; Yonghao Xiao; Meng Gao; Yang Liu; Bowen Cheng (Chemical Engineering Journal, 2025)

Exosome-loaded methacrylated silk fibroin hydrogel delays intervertebral disc degeneration by DKK2-mediated mitochondrial unfolded protein response - Xiao Lu; Zhidi Lin; Liujingzhou Li; Guangyu Xu; Dachuan Li; Zhaoyang Gong; Jiongdong Wu; Tian Gao; Xingyu Guo; Chenpei Xu; Xinlei Xia; Feizhou Lyu; et al. (Chemical Engineering Journal, 2025)

Co-precipitation enrichment of Pb2+ in water by ball-milling-enhanced diatomite: synergistic effects of crystal structure and surface activity - Fei Jiang; Licheng Ji; Zhongpu Yu; Chengcheng Wei; Feiyue Li (Environmental Geochemistry and Health, 2025)

Organic fertilizer application reduce ammonia volatilization in an acidic soil - Cai Gan; Yanbin Jiang; Yan Wang; Shan Lin; Yue Luo; Huabin Li; Yunwei Li; Niannian Tang; Yang Fei; Ronggui Hu (Agriculture, Ecosystems & Environment, 2025)

Chemical constituents of Pedicularis rex C. B. Clarke and their hepatoprotective activities - Yang Fei-Yu; Liu Huai-Qin; Fu-Rui Wang; Zhang Li-Jie; Liao Xing-Jiang; Guo-Bo Xu; Qin-Feng Zhu; Shang-Gao Liao (Natural Product Research, 2025)

Physiological and molecular evidence for phycobilisome degradation in maintaining carbon and nitrogen balance of cyanobacteria - Zhen Luo; Shuangqing Li; Muhammad Zain Ul Arifeen; Fei‑xue Fu; Huayang Gao; Taoran Sun; Lingmei Liu; Xumei Sun; Xinwei Wang; Hai-Bo Jiang (Marine Life Science & Technology, 2025)
Phycobilisomes (PBS), the primary light-harvesting complexes in cyanobacteria, are degraded under nitrogen starvation to provide nitrogen for cell growth. This study reveals that carbon supply is a critical prerequisite for PBS degradation under nitrogen deficiency in Synechococcus sp. PCC 7002. Even under nitrogen-deficient conditions, PBS degradation is inhibited in the absence of sufficient carbon. We demonstrate that both the nblAB -mediated PBS-degradation pathway and the ccmLMNK operon-mediated CO 2 -concentrating mechanism are essential for PBS degradation. Furthermore, our findings highlight the critical role of PBS degradation in cyanobacterial adaptation to high C/N conditions. Mutant strains (Mut- nblA and Mut- nblB) deficient in PBS degradation exhibited impaired adaptation to high C/N conditions, as evidenced by their inability to thrive in high NaHCO 3 (nitrogen-free) or CO 2 (low-nitrogen) environments. While these mutants displayed a greener phenotype under high C/N conditions compared to the wild type, they exhibited extensive cellular damage, and significant downregulation of photosynthesis-related genes. These results provide novel insights into the carbon-dependent regulation of PBS degradation and its essential role in cyanobacterial C/N balance, highlighting its significance for their adaptation to fluctuating environmental conditions.

High urea promotes mitochondrial fission and functional impairments in astrocytes inducing anxiety-like behavior in chronic kidney disease mice - Xi Zhao; Shengyao Zhang; Mengna Wu; Binyun Zhang; Guoran Wan; Meng Zhang; Jing Li; Zhuo Fei; Guoqi Zhu; Shaoqiu Jiang; Mohan Xiao; Wanjia Liu; et al. (Metabolic Brain Disease, 2025)

Identification and fungicide sensitivity of Fusarium oxysporum, the cause of Fusarium wilt on Codonopsis pilosula in Shanxi Province (Lu Dangshen), China - Yan Wang; Dainan Hao; Haozhe Jiang; Zhaoxiong Fei; Rui Zhao; Jiaxin Gao; Guangxin Li; Chunwei Wang (Crop Protection, 2025)

A chemiluminescence immunoassay for detection of Toxoplasma gondii antibody in porcine based on GRA6 and SAG1 - Ran Wu; Ya-Fei Song; Yanlong Gu; Jiang Li; Zhipeng Niu; Dong-Hui Zhou (Veterinary Parasitology, 2025)

Exosomes secreted from M2-polarized macrophages inhibit osteoclast differentiation via CYLD - Zi-yan Guo; Nan-nan Yin; Xiao-fei Li; Meng-meng Wang; Xiao-na Sui; Cai-di Jiang; Ming-hua Xu; Xiao-e Jia; Chong-jian Fu; Tie-lou Chen; Xin Liu (Tissue and Cell, 2025)

Depositional systems constraining the distribution of hydrothermal dolostone geobodies: A case study of Permian Guadalupian dolostone in the eastern Sichuan Basin - Lu Shi; Ziye Lu; Fei Li; Hairuo Qing; Wenzhuo Jiang; Wei Li; Zenghua Li; Ning Ye; Bei Zhu; Qi Tang; Haizhou Qu; Yang Xiao; et al. (Sedimentary Geology, 2025)

The combined microplastics and heavy metals contamination between the soil and aquatic media: A review - Yifan Zhang; Dan Li; Kunlong Hui; Hui Wang; Ying Yuan; Fei Fang; Yu Jiang; Beidou Xi; Wenbing Tan (Journal of Environmental Chemical Engineering, 2025)

Observed seasonal evolution and origins of the western Yellow Sea Cold Water Mass - Chuanjie Wei; Xiaohui Tang; Kai Ge; Anqi Xu; Yuanlong Li; Yong Jiang; Zengrui Rong; Fei Yu (Frontiers in Marine Science, 2025)
The Yellow Sea Cold Water Mass (YSCWM) is one of the most prominent hydrological features of the Yellow Sea. As a low-temperature, nutrient-rich subsurface water mass, the YSCWM fundamentally regulates biogeochemical cycles, functions of marine ecosystems, and fishery resources of the YS. In boreal summer, the YSCWM shows a robust triple-core structure, in which the western component, dubbed the “western YSCWM”, is revisited in this study. Through analyzing in-situ observational data collected by research cruises of the Institute of Oceanology, Chinese Academy of Sciences (IOCAS) and Lagrangian tracing experiments based on a high-resolution ocean model, we provide a thorough investigation for seasonal evolution and origins of the western YSCWM. In-situ observations during 2006-2007 and 2014-2015 suggest that the western YSCWM bears a tight connection to the colder coastal waters near the Shandong Peninsula and achieves the coldest temperature in summer. Analysis of model simulations confirms that the cooling of the western YSCWM in spring and summer is caused mainly by southward cold-water transport of the Shandong Coastal Current (SDCC) from the Shandong coasts and the northern Yellow Sea. We also reveal a contribution of the Subei Shoal water via the Subei Coastal Current (SCC) in summer, which plays a critical role in the quick vanishing of the western YSCMW in early autumn. These findings contribute to our understanding of the formation, seasonal evolution, and heat budgets of the YSCWM.

NAT10 primes a post-transcriptional repertoire essential for the maintenance of spermatogonial homeostasis - Xiaoli Zhu; Caoling Xu; Xue Jiang; Jiaqi Zou; Wenqing Li; Xuemei Xing; Xiaoxiao Gao; Jiao Lei; Fei Meng; Xin Wang; Yuzhang Zhu; Yu Cheng; et al. (Science Bulletin, 2025)

Enhancing sulfate reduction in microbial electrolysis cells: The impact of intermittent electric field and extreme conditions on reaction mechanisms and functional genes - Zhibin Xia; Liang Qiao; Fei Chen; Xu Jiang; Pingting Li; Xing Zong; Yihan Wang; Feihong Wang; Luyan Zhang; Xiaolong Bai; Ye Yuan; Tianming Chen; et al. (Journal of Water Process Engineering, 2025)

A Gln alteration influences leaf morphogenesis by mediating gibberellin levels in tobacco - Qi-Li Mi; Hong-Tao Lv; Fei-Fei Huang; Li Xu; Zi-Ying Huang; Wen-Wu Yang; Mei-Yun Zou; Hai-Tao Huang; Wan-Li Zeng; Jia-Yin Zhao; Qing-Xian Chen; Yong-En Si-Tu; et al. (Journal of Plant Physiology, 2025)

Immune regulation differences in Large yellow croaker with varied resistance to Cryptocaryon irritans infection - Zhou Jiang; Ji Zhao; Rui Li; Qiaozhen Ke; Jiaying Wang; Yin Li; Shuimu Hu; Junjia Zeng; Fei Pu; Ning Li; Peng Xu; Tao Zhou (Fish & Shellfish Immunology, 2025)

Mitigating LPS-induced stress in Chinese mitten crab (Eriocheir sinensis) with P4’ peptide-bearing Bacillus subtilis - Chao-Fan He; Ye Yang; Yong Liu; Xiang Liu; Xiang-Fei Li; Guang-Zhen Jiang; Wen-Bin Liu (Fish & Shellfish Immunology, 2025)

Impact of polyethylene terephthalate microfibers on histopathological and molecular responses induced by cadmium in the polychaete Perinereis aibuhitensis - Yi Cong; Yisong Jiang; Mingxing Zhang; Shuo Cao; Qi Li; Zhaochuan Li; Fei Jin; Yadi Lou; Ying Wang; Huahong Shi; Juying Wang (Environmental Pollution, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Broad-spectrum anti-inflammatory and antioxidant therapy of inflammatory-storm actuated diseases via programmable self-derived cryo-dead neutrophils - Bin Li; Qiuxia Gao; Yunxia Wu; Hongyi Lei; Shengchao Ma; Wei Wang; Hang Sun; Weifeng Ma; Judun Zheng; Chenchen Yuan; Yunlong Zhang; Yue Jia; et al. (Chemical Engineering Journal, 2025)

Numerical prediction of oceanic mesoscale circulation and satellite altimetry data assimilation in the Western Pacific - Zhijin Li; Jianfang Fei; Renhe Zhang; Xingliang Jiang; Wenlong Ma; Xiaoping Cheng; Lei Liu; Guihua Wang; Changlin Chen (Science China Earth Sciences, 2025)

Vertical Distribution Characteristics and Formation/Dissipation Mechanisms of Air Pollutants in Xingtai, China Based on Multi-source Data: A Case Study - Qi Jiang; Fei Wang; Zhanqing Li; Yuan You; Yuchen Jin; Siteng Li; Yele Sun; Yingjie Zhang; Xinrong Ren; Hao He; Russell R. Dickerson (Boundary-Layer Meteorology, 2025)

Multi-habitat utilization and diverse life history of the endangered Sea Carp (Cyprinus acutidorsalis) in the Wanquan Estuary, Hainan island, China: Evidence from otolith microchemistry - Yisi Luo; Zubing Yao; Lichuan Hong; Zheng Li; Xianning Wang; Xingwei Cai; Tao Jiang; Yuan Gu; Fangyuan Li; Yang Dong; Fei Cheng; Jian Yang; et al. (Marine Environmental Research, 2025)

Agricultural Drought Vulnerability in the Middle Reaches of Yangtze River Basin under Environmental Change - Peng Yang; Fei Xu; Jun Xia; Jiang Li; Libo Zhou; Cai Fu (Journal of Earth Science, 2025)

Novel Diagnostic Biomarker BST2 Identified by Integrated Transcriptomics Promotes the Development of Endometriosis via the TNF-α/NF-κB Signaling Pathway - Li Jiang; Sixue Wang; Xiaomeng Xia; Tingting Zhang; Xi Wang; Fei Zeng; Jiezhi Ma; Xiaoling Fang (Biochemical Genetics, 2025)

Research on the source of cinnabar excavated from Sanxingdui site in China based on sulphur and mercury isotope analyses - Qinxin Jiang; Guangyi Sun; Honglin Ran; Yu Lei; Chong Wang; Zhenbin Xie; Fei Tang; Jian Yu; Bisu Zhou; Min Shi; Wan Peng; Chenghui Li; et al. (Archaeological and Anthropological Sciences, 2025)

Structural Response Prediction of Floating Offshore Wind Turbines Based on Force-to-Motion Transfer Functions and State-Space Models - Jie Xu; Changjie Li; Wei Jiang; Fei Lin; Shi Liu; Hongchao Lu; Hongbo Wang (Journal of Marine Science and Engineering, 2025)
This paper proposes an innovative algorithm for forecasting the motion response of floating offshore wind turbines by employing force-to-motion transfer functions and state-space models. Traditional numerical integration techniques, such as the Newmark-β method, frequently struggle with inefficiencies due to the heavy computational demands of convolution integrals in the Cummins equation. Our new method tackles these challenges by converting the problem into a system output calculation, thereby eliminating convolutions and potentially enhancing computational efficiency. The procedure begins with the estimation of force-to-motion transfer functions derived from the hydrostatic and hydrodynamic characteristics of the wind turbine. These transfer functions are then utilized to construct state-space models, which compactly represent the system dynamics. Motion responses resulting from initial conditions and wave forces are calculated using these state-space models, leveraging their poles and residues. We validated the proposed method by comparing its calculated responses to those obtained via the Newmark-β method. Initial tests on a single-degree-of-freedom (SDOF) system demonstrated that our algorithm accurately predicts motion responses. Further validation involved a numerical model of a spar-type floating offshore wind turbine, showing high accuracy in predicting responses to both regular and irregular wave conditions, closely aligning with results from conventional methods. Additionally, we assessed the efficiency of our algorithm over various simulation durations, confirming its superior performance compared to traditional time-domain methods. This efficiency is particularly advantageous for long-duration simulations. The proposed approach provides a robust and efficient alternative for predicting motion responses in floating offshore wind turbines, combining high accuracy with improved computational performance. It represents a promising tool for enhancing the development and evaluation of offshore wind energy systems.

Distribution and fluxes of trimethylamine in the Northwest Pacific marginal seas - Fei Jiang; Zhen Zhou; Jinyan Wang; Wen-Jia Guan; Qiao Liu; Shi-Hai Mao; Xiao-Jun Li; Ni Meng; Gui-Peng Yang; Guang-Chao Zhuang (Global and Planetary Change, 2025)

Controllable development of a novel MXene-based reactive electrochemical ceramic membrane for efficient treatment of reverse osmosis concentrate - Chen Li; Xiaomeng Shang; Zhenbei Wang; Yatao Liu; Fan Li; Zonglin Jiang; Ruijun Ren; Fei Qi; Amir Ikhlaq; Oksana Ismailova; Zukhra Kadirova (Chemical Engineering Journal, 2025)

Rapid gelation of mechanical robust, conductive, and self-healing lignocellulosic nanofibrils hydrogel toward flexible sensor over a broad temperature spectrum - Zhi-Chao Xu; Yu-Qin Yang; Xiao-Wen Pang; Baiyu Jiang; Peng-Fei Mao; Li-Xiu Gong; Binghao Wang; Li Peng; Long-Cheng Tang; Shi-Neng Li (Chemical Engineering Journal, 2025)

Prenatal exposure to di-n-butyl phthalate promotes RIPK1-regulated necroptosis of uroepithelial cells and induces hypospadias through the epithelial-mesenchymal transition process in newborn male rats - Lei Wu; Zhiwen Xie; Tiewen Li; Xincan Chen; Juntao Jiang; Fei Shi; Yongqing Zhang; Xinyu Xu; Shujie Xia; Wenlan Sun (Toxicology, 2024)

Faulted karst reservoir spaces in Middle-Lower Triassic carbonates, Qingjiang Region, Yangtze block, China - Shixi Liao; Fei Cao; Lin Jiang; Yan Wang; Peijin Li; Chaohua Guo; Lin Pan; Xiao Wang (Journal of Structural Geology, 2024)

High-resolution full-coverage ozone (O3) estimates using a data-driven spatial random forest model in Beijing-Tianjin-Hebei region, China - Junyu Wang; Jian Qian; Jiayi Chen; Sheng Li; Menghan Yao; Qianqian Du; Na Yang; Tao Zhang; Fei Yin; Ying Deng; Jing Zeng; Chenglin Tao; et al. (Journal of Hazardous Materials, 2024)

Metabolomic profiling reveals taste development in tomatoes during cold storage with vacuum packaging - Wen-qiang Cai; Jia-bo Huang; Jing Li; Peng-fei Jiang (Food Research International, 2024)

Dynamic high pressure microfluidization modified oat dietary fiber: Texture modulation and its mechanistic in whole grain oat milk - Ziyue Kang; Ning Meng; Ming Liu; Yanxiang Liu; Ping Jiang; Xiaotong Zhai; Yanan Fei; Li Wang; Juanli Shen; Bin Tan (Food Hydrocolloids, 2024)

Exposure to environmentally relevant levels of GenX affects placental and offspring development in mice - Yuhan Dai; Junlin He; Fei He; Zhuxiu Chen; Yu Jiang; Yanqing Geng; Jianwei Geng; Yongrui Zhou; Xuemei Chen; Fangfang Li; Yingxiong Wang; Xinyi Mu (Environmental Pollution, 2024)

DNA-stable isotope probing and metagenomics reveal Fe(II) oxidation by core microflora in microoxic rhizospheric habitats to mitigate the accumulation of cadmium and phenanthrene in rice - Chen Wu; Sicheng Hang; Feng Li; Yujun Wu; Shengwei Yi; Xingang Liu; Mingjie Chen; Fei Ge; Jiang Tian; Ming Zhang; Dayi Zhang (Environmental Pollution, 2024)

Effective Treatment and Biodegradation Mechanism Analysis of Petroleum Hydrocarbon Wastewater by Immobilized Ochrobactrum sp. WY-4 on Iron-modified Biochar - Hengyu Chen; Chuan Yin; Fei Su; Jiancong He; Songling Wu; Menghan Jiang; Huanfang Gao; Cong Li (Water, Air, & Soil Pollution, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

High-resolution satellite estimates of coal mine methane emissions from local to regional scales in Shanxi, China - Shengxi Bai; Yongguang Zhang; Fei Li; Yingqi Yan; Huilin Chen; Shuzhuang Feng; Fei Jiang; Shiwei Sun; Zhongting Wang; Chunyan Zhou; Wei Zhou; Shaohua Zhao (Science of The Total Environment, 2024)

Composition and temporal dynamics of the phytoplankton community in Laizhou Bay revealed by microscopic observation and rbcL gene sequencing - Huihui Zhang; Nan Wang; Di Zhang; Fei Wang; Shiji Xu; Xiaokun Ding; Yixuan Xie; Jinghuan Tian; Bin Li; Zhengguo Cui; Tao Jiang (Marine Environmental Research, 2024)

Improved method for quantitative fault sealing evaluation in sand-clay sequences: A case study from the west subsag of Bozhong Sag in the Bohai Bay basin, China - Xianqiang Song; Xiaofei Fu; Huiyong Li; Haixue Wang; Zhida Liu; Peng Xu; Fei Jiang; Zhaohan Xie (Marine and Petroleum Geology, 2024)

Effect of climate warming on subsurface temperature in basins with topography-driven groundwater flow - Yi-Peng Zhang; Xiao-Wei Jiang; Shemin Ge; Zhi-Yuan Zhang; Peng-Fei Han; Xu-Sheng Wang; Lizhi Wang; Qing Liu; Li Wan (Journal of Hydrology, 2024)

“Cocktail-like” double-layered polyimide/alumina composite aerogels via side-direction freezing method as designable high-temperature thermal insulations - Linyan Wang; Wenjie Li; Chen Wang; Yuncong Jiang; Hang Liu; Tianliang Pang; Xiaodong He; Mingwei Li; Fei He (Chemical Engineering Journal, 2024)

Multiscale simulation of water/oil displacement with dissolved CO 2 : Implications for geological carbon storage and CO 2 -enhanced oil recovery - Sheng Li; Yunfeng Liang; Fei Jiang; Takeshi Tsuji; Haihu Liu; Keishi Usui; Tomohiro Taniguchi; Gyuhwan Jo (Chemical Engineering Journal, 2024)

Link Brain-Wide Projectome to Neuronal Dynamics in the Mouse Brain - Xiang Li; Yun Du; Jiang-Feng Huang; Wen-Wei Li; Wei Song; Ruo-Nan Fan; Hua Zhou; Tao Jiang; Chang-Geng Lu; Zhuang Guan; Xiao-Fei Wang; Hui Gong; et al. (Neuroscience Bulletin, 2024)
Knowledge about the neuronal dynamics and the projectome are both essential for understanding how the neuronal network functions in concert. However, it remains challenging to obtain the neural activity and the brain-wide projectome for the same neurons, especially for neurons in subcortical brain regions. Here, by combining in vivo microscopy and high-definition fluorescence micro-optical sectioning tomography, we have developed strategies for mapping the brain-wide projectome of functionally relevant neurons in the somatosensory cortex, the dorsal hippocampus, and the substantia nigra pars compacta. More importantly, we also developed a strategy to achieve acquiring the neural dynamic and brain-wide projectome of the molecularly defined neuronal subtype. The strategies developed in this study solved the essential problem of linking brain-wide projectome to neuronal dynamics for neurons in subcortical structures and provided valuable approaches for understanding how the brain is functionally organized via intricate connectivity patterns.

Population pharmacokinetics of fluconazole for prevention or treatment of invasive candidiasis in Chinese young infants - Honghong Wang; Dandan Li; Yongjiang Jiang; Jing Liang; Qiaoai Yu; Linghong Kuang; Yuling Huang; Dongjie Qin; Ping Li; Jing He; Feng Xu; Xueli Li; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Comprehensive analysis of hyperspectral features for monitoring canopy maize leaf spot disease - Yali Bai; Chenwei Nie; Xun Yu; Mingyue Gou; Shuaibing Liu; Yanqin Zhu; Tiantian Jiang; Xiao Jia; Yadong Liu; Fei Nan; Liming Li; Bedir Tekinerdogan; et al. (Computers and Electronics in Agriculture, 2024)

Treatment of swine manure by hydrothermal carbonization: The influential effect and preliminary mechanism of surfactants - Zhen-tian Feng; Jiang-bo Xiong; Guo-feng Wang; Lin Li; Chun-fei Zhou; Chun-huo Zhou; Hua-jun Huang (Science of The Total Environment, 2024)

An innovative enhanced flotation approach of non-metallic components in waste printed circuit boards: Application of pyrolysis oil as self-generated collector - Chun-chen Nie; Qian-yun Sun; Xi-guang Li; Shuo Yang; Fei-fei Wang; Gang Hu; Si-qi Jiang; Xiang-nan Zhu; Lin Li; Xiao-fang You (Process Safety and Environmental Protection, 2024)

Interpreting the removal behaviours of aniline and 3,4-diaminotoluene on aromatic carbon-rich magnetic polymer: Statistical modelling, DFT quantitative calculations and new perspectives - Zhengwen Wei; Liuqing Li; Wei Wang; Wankui Ni; Xiang-fei Lü; Giuseppe Mele; Zhen-Yi Jiang (Chemical Engineering Journal, 2024)

Current status and impact of the Young Scientist Foundation of the National Natural Science Foundation on Chinese young scholars in cardiovascular research - Fei Gao; Zhenzhen Chen; Wendong Li; Hujun Jiang; Rui Wang (Science China Life Sciences, 2024)

TUG1 exacerbates cerebral ischemia-reperfusion injury through miR-340-5p-mediated PTEN - Fei Li; Hui-Kai Zhang; Hong-Xiang Jiang; Xin-Yuan Zhang; Qian-Xue Chen (Journal of Molecular Histology, 2024)

Advances in Biomedical Applications of Hydrogels from Seaweed-Derived Sulfated Polysaccharides: Carrageenan, Fucoidan, and Ulvan - Zhiyong Cui; Fei Jiang; Luxi Li; Zhe Chi; Chenguang Liu (Journal of Ocean University of China, 2024)

Microbial regulatory mechanisms of disease-resistant tobacco varieties in the prevention and control of bacterial wilt disease - Hao Xia; Jia Shen; Muhammad Riaz; Huaying Yang; Qing Dong; Chaolong Zu; Fei Yu; Yifeng Yan; Jiaxin Li; Bo Liu; Chaoqiang Jiang (Applied Soil Ecology, 2024)

Rhizosphere microorganisms from the soil around the roots of Lycium barbarum L. - Zhi-bo Jiang; Ya-fei Ren; Yun-qi Hu; Jing-ling Yang; Ji-yuan Wei; Xiao-li Ma (Acta Physiologiae Plantarum, 2024)

Fiddler crabs (Tubuca arcuata) as bioindicators of microplastic pollution in mangrove sediments - Xiaohan Xu; Lei He; Fei Huang; Shiqi Jiang; Zhenqing Dai; Ruikun Sun; Chengyong Li (Chemosphere, 2024)

High-intensity exercise training in large yellow croaker is a compromise between disease resistance and fish welfare - Junjia Zeng; Ang Qu; Yacheng Deng; Pengxin Jiang; Ji Zhao; Jiaying Wang; Yue Liu; Wei Liu; Qiaozhen Ke; Fei Pu; Yaxian Li; Peng Xu (Aquaculture, 2024)

Dynamic relationships and propagation characteristics between meteorological drought and vegetation drought based on a three-dimensional identification algorithm - Fei Wang; Hexin Lai; Zipeng Wang; Ruyi Men; Yanbin Li; Yunzhong Jiang; Kai Feng; Qingqing Tian; Xuefang Du; Yanping Qu (Global and Planetary Change, 2024)

Shallow-water redox evolution from the Ediacaran to the early Cambrian: Linkages to the early animal innovations - Guang-Yi Wei; Da Li; Zunli Lu; Ganqing Jiang; Hong-Fei Ling (Global and Planetary Change, 2024)

A systematic review of the physiological and environmental impacts of coal dust and its control technologies - Stephen Nyabire Akanyange; Wen Nie; Felicie Ilele Mwabaima; Fei Liu; Wenjin Niu; Si-qi Jiang; Yan Zhang; Gifty Adom-Asamoah; Martin Luther Yeboah; Bao Qiu; Haoming Li (Fuel, 2024)

Nitrogen application increased yield sensitivity of indica hybrid rice to climate resource - Bo Lu; Ziyu Li; Fei Yang; Congshan Xu; Xinao Tang; Jianwei Zhang; Chao Ding; Deze Xu; Guofu Zhu; Jing Zhang; Weiwei Li; Haoyu Qian; et al. (European Journal of Agronomy, 2024)

New approach for raw biogas: Production of single cell protein by sulfide-tolerant methane-oxidizing bacteria consortia - Hai-Ming Huang; Zhi-Xin Xue; Yu-Feng Jiang; Rui Li; Rong-Bo Guo; Xiao-Lei Fan; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Important role of Bacillus subtilis as a probiotic and vaccine carrier in animal health maintenance - Chunmei Yuan; Xiang Ji; Yuyu Zhang; Xinli Liu; Luogang Ding; Jianda Li; Sufang Ren; Fei Liu; Zhi Chen; Lin Zhang; Wenxing Zhu; Jiang Yu; et al. (World Journal of Microbiology and Biotechnology, 2024)

Synthesis, structure-activity relationship and evaluation of antifungal activity of tryptanthrin derivatives against drug-resistant Candida albicans - Yandan Wu; Luyi Jiang; Ruina Liu; Lijiao Yang; Fei Zou; Tianyu Zhang; Zefei Fan; Tianbao Zhang; Huan Yang; Shuyun Yin; Ruirui Wang; Ganpeng Li; et al. (Medicinal Chemistry Research, 2024)

Study on Strain Field Reconstruction Method of Long-Span Hull Box Girder Based on iFEM - Guocai Chen; Xueliang Wang; Nan Zhao; Zhentao Jiang; Fei Li; Haozheng Chen; Pengyu Wei; Tao Zhang (Journal of Marine Science and Engineering, 2024)
The box girder’s condition significantly impacts the safety and overall performance of the entire ship because it is the primary stress component of the hull construction. This work used experimental research on the long-span hull box girder based on IFEM (Inverse Finite Element Method) technology to ensure the structural safety of the hull box girder. Due to the limitations of conventional experiments in this technical field, such as their reliance on finite element data and lack of input from physical tests, numerous research methods combining the strain sensing data from physical tests with the strain data from virtual sensors were conducted. The strain fields of the top plate, side plate, and bottom plate were each reconstructed in turn, and the verifier measuring points in the physical model test were used to assess the accuracy of the reconstruction results. The findings demonstrate that the top plate, side plate, and bottom plate reconstructions had relative errors of 0.24–7.86%, 0.75–8.13%, and 3.31–2.52%, respectively. This enables the reconstruction of the strain field of the long-span hull box girder using physical test data and promotes the use of iFEM technology in the field of structural health monitoring of large marine structures.

Genetic and Pathogenic Characterization of an Iridovirus from the Cultured Largemouth Bass Micropterus salmoides - Yi-Fan Zhang; Ying Li; Peng-Tian Li; Jing Jiang; Wei-Hang Zeng; Kun Ye; Yi-Lei Wang; Peng-Fei Zou (Fishes, 2024)
The largemouth bass is a freshwater aquacultured fish species of great economic importance in China. With the rapid development of aquaculture industry and the increase in the aquaculture density of the fish, various infectious pathogens, including parasites, bacteria, and viruses, have been widely spread, which have caused huge losses to the aquaculture industry. Among them, largemouth bass iridovirus (LMBV) is one of the most harmful pathogens. In the present study, a virus strain named LMBV-GDSD was isolated from cultured largemouth bass and was successfully proliferated in FHM and EPC cells, with numerous viral particles observed in the infected cells under transmission electron microscopy analysis. The annotated complete genome of LMBV-GDSD was 99,285 bp and contained 102 ORFs. Based on genomic sequence alignment and phylogenetic analysis, the identified LMBV-GDSD belonged to the genus Ranavirus of Iridoviridae and was pathogenic to largemouth bass under regression infection experiments. In addition, the infection of LMBV-GDSD in largemouth bass could significantly up-regulate the expression of antiviral immune-related genes such as IRF3, IRF7, and Mx. It is thus providing valuable genetic data for a deeper understanding of the pathogenic mechanism of iridovirus in largemouth bass.

Variation in Chongqing finger citron components and antioxidant activity from essential oils in several organs - Shang Fang-Hong; Chen Yu; Du Hong-Fei; He Jiang; Wu Zhen; Song Xu-Hong; Li Long-Yun (South African Journal of Botany, 2024)

The complete genome sequence of the planctomycetotal bacterium Bremerella sp. P1 with abundant genes involved in polysaccharide degradation - Jia-Xuan Wang; Jing Wang; Ji-Qing Liu; Jian Li; Wen-Xin Jiang; Fei Xu; Ping-Yi Li; Qi-Long Qin; Xiu-Lan Chen; Xi-Ying Zhang (Marine Genomics, 2024)

Effects of different curing concentrations and drying times on the microbial community structure and metabolites of dried Spanish mackerel - Jing Li; Yang Liu; Cai-yan Jiang; Xiao-qing Miao; Xiu-ping Dong; Ming Du; Peng-fei Jiang (Food Chemistry, 2024)

Effects of air frying on protein digestive properties in scallop (Patinopecten yessoensis) adductor muscles and the mechanisms involved - Zi-Ye Wang; Ying Luo; Rui Zheng; Shuo Lv; De-Yang Li; Yu-Xin Liu; Lei Qin; Peng-Fei Jiang; Da-Yong Zhou (Food Bioscience, 2024)

Molecular mechanism of a coastal cyanobacterium Synechococcus sp. PCC 7002 adapting to changing phosphate concentrations - Qiao-Wei Sun; Yu Gao; Jordan Wang; Fei-xue Fu; Cheng-Wen Yong; Shuang-Qing Li; Hai-Long Huang; Wei-Zhong Chen; Xin-Wei Wang; Hai-Bo Jiang (Marine Life Science & Technology, 2024)
Phosphorus concentration on the surface of seawater varies greatly with different environments, especially in coastal. The molecular mechanism by which cyanobacteria adapt to fluctuating phosphorus bioavailability is still unclear. In this study, transcriptomes and gene knockouts were used to investigate the adaptive molecular mechanism of a model coastal cyanobacterium Synechococcus sp. PCC 7002 during periods of phosphorus starvation and phosphorus recovery (adding sufficient phosphorus after phosphorus starvation). The findings indicated that phosphorus deficiency affected the photosynthesis, ribosome synthesis, and bacterial motility pathways, which recommenced after phosphorus was resupplied. Even more, most of the metabolic pathways of cyanobacteria were enhanced after phosphorus recovery compared to the control which was kept in continuous phosphorus replete conditions. Based on transcriptome, 54 genes potentially related to phosphorus-deficiency adaptation were selected and knocked out individually or in combination. It was found that five mutants showed weak growth phenotype under phosphorus deficiency, indicating the importance of the genes ( A0076 , A0549-50 , A1094 , A1320 , A1895 ) in the adaptation of phosphorus deficiency. Three mutants were found to grow better than the wild type under phosphorus deficiency, suggesting that the products of these genes ( A0079 , A0340 , A2284–86 ) might influence the adaptation to phosphorus deficiency. Bioinformatics analysis revealed that cyanobacteria exposed to highly fluctuating phosphorus concentrations have more sophisticated phosphorus acquisition strategies. These results elucidated that Synechococcus sp. PCC 7002 have variable phosphorus response mechanisms to adapt to fluctuating phosphorus concentration, providing a novel perspective of how cyanobacteria may respond to the complex and dynamic environments.

Two new alkaloids from the endophytic fungus Schizophyllum sp. HM230 isolated from Vincetoxicum mongolicum Maxim - Zhuang Li; Bing-Wen Zhang; Li Jiang; He Wang; Qing-Yun Ma; Hong-Fei Wang; Jun Zhang; Feng-Li Chen; You-Xing Zhao; Du-Qiang Luo (Natural Product Research, 2024)

New insights into the influences of firework combustion on molecular composition and formation of sulfur- and halogen-containing organic compounds - Caiqing Yan; Haibiao Chen; Fei Xu; Qinglong Fu; Ying Zhou; Ruizhi Zhou; Ruiyu Li; Mei Zheng; Mingjie Xie; Bin Jiang; Zhisheng Zhang; He Meng; et al. (Science of The Total Environment, 2024)

Ent-eudesmane sesquiterpenoids with anti-neuroinflammatory activity from the marine-derived fungus Eutypella sp. F0219 - Zhong-Ping Jiang; Rui Su; Meng-Ting Chen; Jun-Yi Li; Han-Yu Chen; Lu Yang; Fei-Fei Liu; Jin Liu; Cong-Jun Xu; Wan-Shan Li; Yong Rao; Ling Huang (Phytochemistry, 2024)

Global daily mask use estimation in the pandemic and its post environmental health risks: Analysis based on a validated dynamic mathematical model - Ying Zhang; Fei Jiang; Fengmin Li; Shaoyong Lu; Zihao Liu; Yuwen Wang; Yiming Chi; Chenchen Jiang; Ling Zhang; Qingfeng Chen; Zhipeng He; Xiaoli Zhao; et al. (Journal of Hazardous Materials, 2024)

Contamination characteristics of uncultivated arable lands and health risk warning based on the predicted heavy metal content in rice—Dongting Lake Basin, China - Chen Wu; Feng Li; Shengwei Yi; Xiangxi Ding; Yujun Wu; Fei Ge; Xionghui Ji; Yun Liu; Jiang Tian (Journal of Geochemical Exploration, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Plastome structure, phylogeny and evolution of plastid genes in Reevesia (Helicteroideae, Malvaceae) - Li-Yang Geng; Tian-Yi Jiang; Xin Chen; Qiang Li; Jian-Hui Ma; Wen-Xiang Hou; Chen-Qian Tang; Qin Wang; Yun-Fei Deng (Journal of Plant Research, 2024)

Enhancing precision of root-zone soil moisture content prediction in a kiwifruit orchard using UAV multi-spectral image features and ensemble learning - Shidan Zhu; Ningbo Cui; Li Guo; Huaan Jin; Xiuliang Jin; Shouzheng Jiang; Zongjun Wu; Min Lv; Fei Chen; Quanshan Liu; Mingjun Wang (Computers and Electronics in Agriculture, 2024)

Cysteine and glycine-rich protein 2 is crucial for maintaining the malignant phenotypes of gliomas through its action on Notch signalling cascade - Lingtong Liu; Fei Li; Lingxue Zhang; Yingying Cheng; Lin Wu; Ru Tie; Xiaobing Jiang; Wenwen Gao; Bochuan Liu; Yao Wei; Pan Chang; Jun Xu; et al. (Toxicology and Applied Pharmacology, 2024)

Dissecting the long-term neurobehavioral impact of embryonic benz[a]anthracene exposure on zebrafish: Social dysfunction and molecular pathway activation - Haichu Zhao; Weiran Chen; Fei Li; Xiaoyang Wang; Xin Pan; Yang Liu; Liting Wang; Wei Sun; Fei Li; Shan Jiang (Science of The Total Environment, 2024)

Evolutionary genomics of climatic adaptation and resilience to climate change in alfalfa - Fan Zhang; Ruicai Long; Zhiyao Ma; Hua Xiao; Xiaodong Xu; Zhongjie Liu; Chunxue Wei; Yiwen Wang; Yanling Peng; Xuanwen Yang; Xiaoya Shi; Shuo Cao; et al. (Molecular Plant, 2024)

Enhanced Fenton-like catalysis through in-situ bismuth defection in Bi/CuBi2O4: Vacancy mechanisms - Chenglin Zhang; Fei Liu; Qiuchen He; Jiangpeng Li; Wenjun Jiang; Su Zhan; Feng Zhou (Journal of Environmental Chemical Engineering, 2024)

Study on flame properties and molecular dynamics of MAP suppression for polyethylene dust explosion - Bingyou Jiang; Jing-Jing Li; Mingqing Su; Kunlun Lu; Chang-Fei Yu; Tun Yang; Qi Yao; Dawei Ding (Fuel, 2024)

High-temperature energy storage with a new tri-layers polymer composites via hybrid assembly engineering - Fei Wen; Hongbin Yuan; Mengquan Jiang; Pingan Yang; Jian Wang; Lin Zhang; Lili Li; Gaofeng Wang; Wenjun Li; Wei Wu; Zhonghui Shen; Shujun Zhang (Chemical Engineering Journal, 2024)

MOFs-derived carbon-covered nickel phosphide for catalytic transfer hydrodeoxygenation of lignin-derived vanillin - Fei Ge; Hui Li; Bingquan Wu; Xiaohui Yang; Jianchun Jiang; Yidong Zhang; Minghao Zhou (Chemical Engineering Journal, 2024)

Retraction Note: Ensemble learning-based gene signature and risk model for predicting prognosis of triple-negative breast cancer - Tiancheng Li; Siqi Chen; Yuqi Zhang; Qianqian Zhao; Kai Ma; Xiwei Jiang; Rongwu Xiang; Fei Zhai; Guixia Ling (Functional & Integrative Genomics, 2024)

New Record Ocean Temperatures and Related Climate Indicators in 2023 - Lijing Cheng; John Abraham; Kevin E. Trenberth; Tim Boyer; Michael E. Mann; Jiang Zhu; Fan Wang; Fujiang Yu; Ricardo Locarnini; John Fasullo; Fei Zheng; Yuanlong Li; et al. (Advances in Atmospheric Sciences, 2024)
The global physical and biogeochemical environment has been substantially altered in response to increased atmospheric greenhouse gases from human activities. In 2023, the sea surface temperature (SST) and upper 2000 m ocean heat content (OHC) reached record highs. The 0–2000 m OHC in 2023 exceeded that of 2022 by 15 ± 10 ZJ (1 Zetta Joules = 10 21 Joules) (updated IAP/CAS data); 9 ± 5 ZJ (NCEI/NOAA data). The Tropical Atlantic Ocean, the Mediterranean Sea, and southern oceans recorded their highest OHC observed since the 1950s. Associated with the onset of a strong El Niño, the global SST reached its record high in 2023 with an annual mean of ∼0.23°C higher than 2022 and an astounding > 0.3°C above 2022 values for the second half of 2023. The density stratification and spatial temperature inhomogeneity indexes reached their highest values in 2023.

El Niño and the AMO Sparked the Astonishingly Large Margin of Warming in the Global Mean Surface Temperature in 2023 - Kexin Li; Fei Zheng; Jiang Zhu; Qing-Cun Zeng (Advances in Atmospheric Sciences, 2024)

Penicillium oxalicum induced phosphate precipitation enhanced cadmium (Cd) immobilization by simultaneously accelerating Cd biosorption and biomineralization - Jiaru Yue; Ting Li; Jiang Tian; Fei Ge; Feng Li; Yun Liu; Dayi Zhang; Jingwei Li (Journal of Hazardous Materials, 2024)

Transcriptome analysis reveals vanadium reduction mechanisms in a bacterium of Pseudomonas balearica - Chun-dan Gan; Jin-yan Yang; Jiang-fei Li; Meng-qi Yang; Xin-yue Du; Aleksander Nikitin (Journal of Cleaner Production, 2024)

Uptake, translocation, and metabolism of organophosphate esters (OPEs) in plants and health perspective for human: A review - Zhi-Lang Lao; Dan Wu; Hui-Ru Li; Yu-Fei Feng; Long-Wei Zhang; Xue-Yi Jiang; Yi-Shan Liu; Dong-Wei Wu; Jun-Jie Hu (Environmental Research, 2024)

Prolonged blood circulation and enhanced tumor penetration of biomimetic magnetic nanoemulsion for improved magnetic hyperthermia in combination with immunotherapy - Siyu Wang; Yishuo Jiang; Zhuoping Qian; Lili Ren; Jiahui Wang; Yewei Liu; Yichong Li; Jie Li; Kuiming Qu; Fei Wang; Haoan Wu; Fang Yang; et al. (Chemical Engineering Journal, 2024)

Optimizing the development and field application of calcium stabilizing agents for preventing calcium leaching in tunnels - Yueping Tong; Fei Ye; Chongming Tian; Junyuan Zhang; Yin Jiang; Xingbo Han; Yongjian Li (Journal of Cleaner Production, 2024)

Influence of the temperature during grain filling stage and nitrogen application rate on yield and quality of indica hybrid rice - Bo Lu; Congshan Xu; Ziyu Li; Xinao Tang; Fei Yang; Deze Xu; Guofu Zhu; Jing Zhang; Yu Jiang; Weiwei Li; Zhenghui Liu; Yanfeng Ding; et al. (Field Crops Research, 2024)

Enhanced performance of oxygen vacancy-rich In-TiO2 materials for electrocatalytic urea synthesis via a relay catalysis strategy - Yini Mao; Fei Ren; Qiao Gou; Yong Jiang; Lan Tang; Yimin Jiang; Wei Shen; Ming Li; Rongxing He (Chemical Engineering Journal, 2024)

Will the Globe Encounter the Warmest Winter after the Hottest Summer in 2023? - Fei Zheng; Shuai Hu; Jiehua Ma; Lin Wang; Kexin Li; Bo Wu; Qing Bao; Jingbei Peng; Chaofan Li; Haifeng Zong; Yao Yao; Baoqiang Tian; et al. (Advances in Atmospheric Sciences, 2024)

Risk of papillary thyroid carcinoma and nodular goiter associated with exposure to semi-volatile organic compounds: A multi-pollutant assessment based on machine learning algorithms - Fei Wang; Yuanxin Lin; Jianing Xu; Fugui Wei; Simei Huang; Shifeng Wen; Huijiao Zhou; Yuwei Jiang; Haoyu Wang; Wenlong Ling; Xiangzhi Li; Xiaobo Yang (Science of The Total Environment, 2024)

Halogenated aliphatic and phenolic disinfection byproducts in chlorinated and chloraminated dairy wastewater: Occurrence and ecological risk evaluation - You-Wei Jiang; Gui-Jing Wang; Shuang Zang; Yue Qiao; Hong-Fei Tao; Qiao Li; Han Zhang; Xian-Shi Wang; Jun Ma (Journal of Hazardous Materials, 2024)

αExtractor: a system for automatic extraction of chemical information from biomedical literature - Jiacheng Xiong; Xiaohong Liu; Zhaojun Li; Hongzhong Xiao; Guangchao Wang; Zhenjiang Niu; Chaoyuan Fei; Feisheng Zhong; Gang Wang; Wei Zhang; Zunyun Fu; Zhiguo Liu; et al. (Science China Life Sciences, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Deciphering the effects of crop rotation on tobacco bacterial wilt through general and specific disease suppression - Hai-kun Ma; Zhi-jiang Wang; Meng-jiao Li; Qing-lin Rao; Jun Cai; Xiao-fei Gu (European Journal of Plant Pathology, 2024)

Metal-polyphenol microgels for oral delivery of puerarin to alleviate the onset of diabetes - Si-hui Li; Yan-fei Li; Di Wu; Yu Xu; Hui-jia Yan; Jiang-Ning Hu (Drug Delivery and Translational Research, 2024)

Mechanistic insights into the effects of diuron exposure on Alexandrium pacificum - Dan Huang; Cai-Qin Cheng; Jiang-Bing Qiu; Yun Huang; Hao-Yun Zhang; Zhen-Hao Xu; Si-Wei Wu; Yi-Tong Huang; Jian Chen; Li-Gong Zou; Wei-Dong Yang; Xiao-Fei Zheng; et al. (Water Research, 2024)

Improved estimation of CO2 emissions from thermal power plants based on OCO-2 XCO2 retrieval using inline plume simulation - Yingsong Li; Fei Jiang; Mengwei Jia; Shuzhuang Feng; Yong Lai; Junnan Ding; Wei He; Hengmao Wang; Mousong Wu; Jun Wang; Fanhui Shen; Lingyu Zhang (Science of The Total Environment, 2024)

Spatially explicit estimation of freshwater fish stock biomass with limited data: A case study of an endangered endemic fish on the Tibetan Plateau, China - Kunyuan Wanghe; Shahid Ahmad; Xin Zhou; Fei Tian; Sijia Liu; Bingzheng Zhou; Ghulam Nabi; Guojie Wang; Kemao Li; Shenglong Jian; Huamin Jiang; Shengxue Chen; et al. (Science of The Total Environment, 2024)

Rational design of a cross-type HPV vaccine through immunodominance shift guided by a cross-neutralizing antibody - Zhiping Wang; Daning Wang; Jie Chen; Fei Gao; Yanan Jiang; Chengyu Yang; Ciying Qian; Xin Chi; Shuyue Zhang; Yujie Xu; Yihan Lu; Jingjia Shen; et al. (Science Bulletin, 2024)

Three-dimensional inter-basin groundwater flow toward a groundwater-fed stream: Identification, partition, and quantification - Peng-Fei Han; Xu-Sheng Wang; Yangxiao Zhou; Zhi Yang; Li Wan; Jinsong Chen; Xiao-Wei Jiang (Journal of Hydrology, 2024)

Geographical origin identification of camellia oil based on fatty acid profiles combined with one-class classification - Xinjing Dou; Xuefang Wang; Fei Ma; Li Yu; Jin Mao; Jun Jiang; Liangxiao Zhang; Peiwu Li (Food Chemistry, 2024)

Highly effective synthesis of novel structured phospholipid emulsifiers using magnetically recyclable Fe3O4@SiO2/M (M = Zn or Al) composite - Jia Ma; Jiang-Hua Zhang; Hua-Wei Zhang; Qian-Qian Du; Zi-Xuan Li; Zhi-Fei Yang; Sha-Sha Yang; Da-Yong Zhou (Food Chemistry, 2024)

Functional characterization of RIP2 in large yellow croaker (Larimichthys crocea), a protein involved in the host antiviral responses via NF-κΒ, IRF3/7 related signaling - Jing Jiang; Ying Li; Kai Qing Li; Ying Jia Shen; Fang Li; Yi Lei Wang; Yong Hua Jiang; Peng Fei Zou (Fish & Shellfish Immunology, 2024)

Interactive effects of dietary leucine and isoleucine affect amino acid profile and metabolism through AKT/TOR signaling pathways in blunt snout bream (Megalobrama amblycephala) - Mang-mang Wang; Yang-yang Huang; Wen-bin Liu; Kang Xiao; Xi Wang; Hui-xing Guo; Yi-lin Zhang; Jing-Wei Fan; Xiang-fei Li; Guang-zhen Jiang (Fish Physiology and Biochemistry, 2024)

Effect of conscious conflict on the subliminal perception of table tennis players: from the electrophysiological evidence of ERP - Ruichen Jiang; Fei Xie; Anmin Li (Cognitive Neurodynamics, 2024)

Prenatal exposures to phthalates and bisphenols in relation to oxidative stress: single pollutant and mixtures analyses - Jia-Yue Zeng; Min Zhang; Xu-Hui Chen; Chong Liu; Yan-Ling Deng; Pan-Pan Chen; Yu Miao; Fei-Peng Cui; Tian Shi; Ting-Ting Lu; Xiao-Ying Liu; Yang Wu; et al. (Environmental Science and Pollution Research, 2024)

MiRNAs enabled Golden pompano (Trachinotus blochii) in response to different reoxygenation patterns after hypoxic stress - Tian Jiang; Jun Long Sun; Chun Xiu Jin; Yu Zhang; Zai Hui Tong; Yue Gu; Fu Cheng Yao; Li Ping Shi; Fei Biao Song; Jian Luo (Aquaculture, 2024)

Impacts of electric field-magnetic powder coupled membrane bioreactor on phenol wastewater treatment: Performance, synergistic mechanism, antibiotic resistance genes, and eco-environmental benefit evaluation - Bei Jiang; Qianzhi Zeng; Qiangwei Liu; Huiying Chai; Jinxun Xiang; Hongxin Li; Shengnan Shi; Aifu Yang; Zhaobo Chen; Yubo Cui; Dongxue Hu; Hui Ge; et al. (Science of The Total Environment, 2024)

Mechanism insight into highly efficient stabilization of Cd contaminated soils by steam flash heating - Xiaolu Fan; Xue Wu; Xueyan Li; Tianyun Wu; Bo Jiang; Jing Xiong; Fei Li; Shupeng Li; Lei Zheng; Xinzi Wang; Linying Yao; Fang Zhang; et al. (Journal of Cleaner Production, 2024)

Uptake mechanism, translocation, and transformation of organophosphate esters in water hyacinth (Eichhornia crassipes): A hydroponic study - Zhi-Lang Lao; Dan Wu; Hui-Ru Li; Yi-Shan Liu; Long-Wei Zhang; Yu-Fei Feng; Xue-Yi Jiang; Dong-Wei Wu; Jun-Jie Hu; Guang-Guo Ying (Environmental Pollution, 2024)

A transformer-based neural network for ignition location prediction from the final wildfire perimeter - Yuming Qiao; Wenyu Jiang; Guofeng Su; Juncai Jiang; Xin Li; Fei Wang (Environmental Modelling & Software, 2024)

A pleiotropic SIS-based hydrogel with immunomodulation via NLRP3 inflammasome inhibition for diabetic bone regeneration - Ning Sheng; Fei Xing; Qing-Yi Zhang; Jie Tan; Rong Nie; Kai Huang; He-Xi Li; Yan-Lin Jiang; Bo Tan; Zhou Xiang; Hui-Qi Xie (Chemical Engineering Journal, 2024)

The swelling induced choline alkali-urea (SICAU) process for sustainable crop straw upgrading - Yuehan Jiang; Feiyue Shen; Baiheng Jiang; Yuheng Hu; Jinguang Hu; Mei Huang; Li Zhao; Hejun Wu; Dong Tian; Fei Shen (Chemical Engineering Journal, 2024)

Fructooligosaccharides and fructans from Platycodon grandiflorum: Structural characterization, lung-oriented guidance and targetability - Jun Liang; Wen-Fei Wang; Yi Zhang; Yan-Qun Chai; Ya-Ge Li; Si-Liang Jiang; Xin-Hua Zhu; Yu-Li Guo; Zhen Wei; Xi-Zhe Sun; Hai-Xue Kuang; Yong-Gang Xia (Carbohydrate Polymers, 2024)

Extraction of super high-yield lignin-carbohydrate complexes from rice straw without compromising cellulose hydrolysis - Baiheng Jiang; Feiyue Shen; Yuehan Jiang; Mei Huang; Li Zhao; Yongjia Lei; Jinguang Hu; Dong Tian; Fei Shen (Carbohydrate Polymers, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Metagenomic and proteomic insights into the self‐adaptive cell surface hydrophobicity of Sphingomonas sp. strain PAH02 reducing the migration of cadmium‐phenanthrene co‐pollutant in rice - Shengwei Yi; Zhongnan Zhu; Feng Li; Lizhong Zhu; Chen Wu; Fei Ge; Xionghui Ji; Jiang Tian (Environmental Microbiology, 2024)
Cell surface hydrophobicity ( CSH ) dominates the interactions between rhizobacteria and pollutants at the soil‐water interface, which is critical for understanding the dissipation of pollutants in the rhizosphere microzone of rice. Herein, we explored the effects of self‐adaptive CSH of Sphingomonas sp. strain PAH02 on the translocation and biotransformation behaviour of cadmium‐phenanthrene (Cd‐Phe) co‐pollutant in rice and rhizosphere microbiome. We evidenced that strain PAH02 reduced the adsorption of Cd‐Phe co‐pollutant on the rice root surface while enhancing the degradation of Phe and adsorption of Cd via its self‐adaptive CSH in the hydroponic experiment. The significant upregulation of key protein expression levels such as MerR, ARHDs and enoyl‐CoA hydratase/isomerase, ensures self‐adaptive CSH to cope with the stress of Cd‐Phe co‐pollutant. Consistently, the bioaugmentation of strain PAH02 promoted the formation of core microbiota in the rhizosphere soil of rice ( Oryza sativa L.), such as Bradyrhizobium and Streptomyces and induced gene enrichment of CusA and PobA that are strongly associated with pollutant transformation. Consequently, the contents of Cd and Phe in rice grains at maturity decreased by 17.2% ± 0.2% and 65.7% ± 0.3%, respectively, after the bioaugmentation of strain PAH02. These findings present new opportunities for the implementation of rhizosphere bioremediation strategies of co‐contaminants in paddy fields.

Short-term exposure to gaseous pollutants is neglected factors for knee osteoarthritis: evidence from a humid subtropical region of China - Yi-Fei Zhang; Li-Feng Zhang; Han-Yuan Zhang; Wei Jiang; Guang-Yu Li; Tian-Ping Zhang (Environmental Science and Pollution Research, 2023)

Strontium alleviated the growth inhibition and toxicity caused by cadmium in rice seedlings - Jun Liu; Xinting Fan; Yuanyuan Jiang; Juan Ni; Aili Mo; Meihan Cai; Tong Li; Yaqi Wang; Peishuang He; Shiyu Hu; Tangjian Peng; Cuiying Peng; et al. (Science of The Total Environment, 2023)

Dynamic human exposure to airborne bacteria-associated antibiotic resistomes revealed by longitudinal personal monitoring data - Rong-min Zhang; Xin-lei Lian; Li-wei Shi; Liuyiqi Jiang; Shan-shan Chen; Wen-qing Haung; Jia-en Wu; Fei-jing Wu; Jian Sun; Xiao-ping Liao; Yun-xiao Chong; Ya-hong Liu; et al. (Science of The Total Environment, 2023)

WFNet: A hierarchical convolutional neural network for wildfire spread prediction - Wenyu Jiang; Yuming Qiao; Guofeng Su; Xin Li; Qingxiang Meng; Hongying Wu; Wei Quan; Jing Wang; Fei Wang (Environmental Modelling & Software, 2023)

Heteropolyacids promoted MOF-derived high-performance Co(H4)@C-HPW0.25 catalysts for catalytic transfer hydrogenation of vanillin in mild condition - Yaqi Xue; Haihong Xia; Jing Li; Jiantao Su; Fei Ge; Xiaohui Yang; Jianchun Jiang; Minghao Zhou (Chemical Engineering Journal, 2023)

Self-catalyst degradation of amoxicillin in alkaline condition driven by superoxide radical - Chengyi Sun; Yaling Wang; Bao Jiang; Shanshan Hu; Yiqi Wang; Chong Zhang; Fei Liu; Yan Zhang; Guoao Li (Chemical Engineering Journal, 2023)

AuNP-Loaded Electrospinning Membrane Cooperated with CDs for Periodontal Tissue Engineering - Jie Wang; Hang Zhang; Yan Wang; Xiang Liu; Weiwen Zhu; Fei Jiang; Size Li; Laikui Liu (Tissue Engineering and Regenerative Medicine, 2023)

High-fat diet alters intestinal microbiota and induces endoplasmic reticulum stress via the activation of apoptosis and inflammation in blunt snout bream - Kenneth Prudence Abasubong; Guang-Zhen Jiang; Hui-xing Guo; Xi Wang; Xiang-Fei Li; Dong Yan-zou; Wen-bin Liu; Hesham Eed. Desouky (Fish Physiology and Biochemistry, 2023)

Deformation characteristics and mechanism of an impoundment-induced toppling landslide in Baihetan Reservoir based on multi-source remote sensing - Zhen-kai Zhou; Xin Yao; Ren-jiang Li; Shu Jiang; Xiao-ming Zhao; Kai-yu Ren; Yi-fei Zhu (Journal of Mountain Science, 2023)

Modeling China's terrestrial ecosystem gross primary productivity with BEPS model: Parameter sensitivity analysis and model calibration - Xiuli Xing; Mousong Wu; Wenxin Zhang; Weimin Ju; Torbern Tagesson; Wei He; Songhan Wang; Jun Wang; Lu Hu; Shu Yuan; Tingting Zhu; Xiaorong Wang; et al. (Agricultural and Forest Meteorology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Arsenic exposure and lung function decline in chronic obstructive pulmonary disease patients: The mediating influence of systematic inflammation and oxidative stress - Yun-Feng Liu; Min-Min Tang; Jing Sun; Jia-Fei Li; Ya-Lin Jiang; Hui Zhao; Lin Fu (Food and Chemical Toxicology, 2023)

Slow release of attapulgite based nano-enabled glyphosate improves soil phosphatase activity, organic P-pool and proliferation of dominant bacterial community - Xuejuan Hou; Hui Nan; Xin Chen; Fei Ge; Yun Liu; Feng Li; Dayi Zhang; Jiang Tian (Environmental Pollution, 2023)

Ångstrom-scale silver particles ameliorate collagen-induced and K/BxN-transfer arthritis in mice via the suppression of inflammation and osteoclastogenesis - Ze-Hui He; Jing-Tao Zou; Xia Chen; Jiang-Shan Gong; Ya Chen; Ling Jin; Yi-Wei Liu; Shan-Shan Rao; Hao Yin; Yi-Juan Tan; Zun Wang; Wei Du; et al. (Inflammation Research, 2023)

Coarse woody debris and litter layer exert differential roles in nursing soil fungal communities across a subalpine forest successional series - Zhihui Wang; Fei Li; Jianfeng Hou; Xuqing Li; Rui Cao; Yurui Jiang; Yuchen Lu; Shuning Ma; Wanqin Yang (Acta Oecologica, 2023)

Short-term effect of meteorological factors and extreme weather events on daily outpatient visits for dry eye disease between 2013 and 2020: a time-series study in Urumqi, China - Si-Yu Gui; Fei Wang; Jian-Chao Qiao; Xin-Chen Wang; Zhi-Hao Huang; Fan Yang; Cheng-Yang Hu; Fang-Biao Tao; Li-Ming Tao; Dong-Wei Liu; Xiang-Long Yi; Zheng-Xuan Jiang (Environmental Science and Pollution Research, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Genome analysis of Tepidibacter sp. SWIR-1, an anaerobic endospore-forming bacterium isolated from a deep-sea hydrothermal vent - Xue-Gong Li; Jie Dai; Wei-Jia Zhang; Ai-Jun Jiang; Deng-Hui Li; Long-Fei Wu (Marine Genomics, 2023)

The microbial degradation of AAOO based cutting fluid wastewater - Bao-Hua Li; Jiang-Hua Huang; Xiao-Lei Li; Qian Ma; Peng-Fei Zhao; Wen Huang (Journal of Water Process Engineering, 2023)

In situ reaction enabled surface segregation toward dual-heterogeneous antifouling membranes for oil-water separation - Hui Wang; Fei Wang; Zhichao Li; Yu Zheng; Tianrun Gu; Runnan Zhang; Zhongyi Jiang (Journal of Hazardous Materials, 2023)

Switchable organocatalysts: Highly efficient reductive functionalization of CO2 to benzimidazoles under mild conditions - Leizhi Zheng; Fei Chen; Jia Liu; Bowen Jiang; Ying Liu; Guangzhi Xu; Xinyao Li; Chengbao Liu (Journal of Environmental Chemical Engineering, 2023)

Oral bovine serum albumin administration alleviates inflammatory signals and improves antioxidant capacity and immune response under thioacetamide stress in blunt snout bream fed a high-calorie diet - Kenneth Prudence Abasubong; Guang-Zhen Jiang; Hui-xing Guo; Xi Wang; Yang-yang Huang; Yong-Jun Dai; Xiang-Fei Li; Yan-zou Dong; Ndakalimwe Naftal Gabriel; Wen-bin Liu (Fish & Shellfish Immunology, 2023)

Semiconductors modified gourd-shaped hollow PtNi and their directional electron and mass transfer effects - Fu-Fei Pu; Yu-Xuan Xiao; Xiong Yang; Fei Yu; Lei Xia; Jiang-Bo Chen; Lu Wu; Jing-Jing Xie; Wen-Ying Zhao; Yu Liu; Li-Ying Wang; Jie Ying; et al. (Chemical Engineering Journal, 2023)

Lignin meets MOFs: Lignin derived metal carbon material for the catalytic hydrotreatment of guaiacol to cyclohexanol - Fei Ge; Haihong Xia; Jing Li; Yaqi Xue; Jiantao Su; Xiaohui Yang; Jianchun Jiang; Minghao Zhou (Chemical Engineering Journal, 2023)

The coupling effects between acid-catalyzed hydrothermal pretreatment and acidic/alkaline deep eutectic solvent extraction for wheat straw fractionation - Na Pan; Baiheng Jiang; Jinguang Hu; Mei Huang; Jinsong He; Qin Jiang; Li Zhao; Fei Shen; Dong Tian (Bioresource Technology, 2023)

Coordination effect enhanced visualization of latent fingerprint with Eu (TTA)3phen-SiO2 microspheres - Kang Zhang; Meng-Jiao Zhu; Yi-Wen Zhou; Xiao Liu; Feng Chen; Yu-Yang Zhou; Wan-Fei Li; Sheng Liu; Yun Jiang; Shou-Qing Liu (Analytica Chimica Acta, 2023)

Optimization of water quality index models using machine learning approaches - Fei Ding; Wenjie Zhang; Shaohua Cao; Shilong Hao; Liangyao Chen; Xin Xie; Wenpan Li; Mingcen Jiang (Water Research, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Microplastics cause reproductive toxicity in male mice through inducing apoptosis of spermatogenic cells via p53 signaling - Chunsheng Lu; Yuehui Liang; Ya Cheng; Chan Peng; Yuanyuan Sun; Kangle Liu; Yingqing Li; Yixia Lou; Xiao Jiang; Aihua Zhang; Jinyi Liu; Jia Cao; et al. (Food and Chemical Toxicology, 2023)

Benzo[b]fluoranthene induces male reproductive toxicity and apoptosis via Akt-Mdm2-p53 signaling axis in mouse Leydig cells: Integrating computational toxicology and experimental approaches - Chao-feng Shi; Fei Han; Xiao Jiang; Zhonghao Zhang; Yingqing Li; Jiankang Wang; Shengqi Sun; Jin-yi Liu; Jia Cao (Food and Chemical Toxicology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Aflatoxins degradation and quality evaluation in naturally contaminated rice by dielectric barrier discharge cold plasma - Ai Zhi; Shanshan Shi; Qi Li; Fei Shen; Xueming He; Yong Fang; Qiuhui Hu; Xuesong Jiang (Innovative Food Science & Emerging Technologies, 2023)

Optimization of enrichment and pretreatment of low-activity radium isotopes in the open ocean - Guiyuan Dai; Guizhi Wang; Qing Li; Weizhen Jiang; Fei Zhang (Acta Oceanologica Sinica, 2023)

Long-term hypoxia and reoxygenation induced oxidative stress lead to immunosuppression and apoptosis in golden pompano (Trachinotus blochii) - Yue Gu; Jun Long Sun; Fu Cheng Yao; Tian Jiang; Chun Xiu Jin; Li Ping Shi; Shu Kui Sun; Fei Biao Song; Jian Luo (Frontiers in Marine Science, 2023)
The fluctuations of dissolved oxygen (DO) often lead to hypoxia in aquaculture, which has a huge adverse impact on fish. This study mainly investigated the effects of long-term hypoxia on oxidative stress, immune response, and cell apoptosis in the liver of golden pompano ( Trachinotus blochii ), which is not tolerant to hypoxia. So we conducted a 14 day low oxygen stress experiment on the golden pompano with a DO of 3.0 ± 0.2 mg/L, then restore the DO to normal levels and continue the 14 day reoxygenation experiment. Results showed that hypoxia and reoxygenation led to significant changes in liver structure. During hypoxia and reoxygenation, the expression of oxidative stress related genes ( SOD1 , SOD2 , GSH-Px , and CAT ) and levels of antioxidant enzymes (CAT and MDA) in the liver were increased. Liver lysozyme activity and the relative expression of the pro-inflammatory factors interleukin ( IL)-1β were significantly increased, but the expression of IL-34 was down-regulated during hypoxia. The expression of IL-12β was significantly increased during reoxygenation. The expression of anti-inflammatory factor IL -11 was decreased duringreoxygenation. The expression of toll like receptors ( TLRs ) -7, -8, and -9 increases after hypoxia and decreases after reoxygenation, indicating that both hypoxia and reoxygenation affect the immune response. In addition, during hypoxia and reoxygenation, TUNEL-positive signals increased, the bcl2/bax ratio decreased, the expression levels of caspases-3 and -8 were significantly up-regulated during hypoxia, and expression levels of caspases-9 was up-regulated during reoxygenation. In summary, hypoxia and reoxygenation can cause oxidative stress, induce inflammatory reactions, inhibit immune processes, activate apoptosis, and lead to liver damage of the golden pompano, which may be irreversible.

An online intelligent management method for wastewater treatment supported by coupling data-driven and mechanism models - Jian-Hui Wang; Du-Jiang Zhao; Wan-Shan Liao; Mohamed S. Mahmoud; Zhi-Wei Guo; Hui-Min Li; Xu Gao; Dong Feng; Long-Fei Shi; You-Peng Chen; Yu Shen (Journal of Water Process Engineering, 2023)

Effect of boiling on texture of scallop adductor muscles and its mechanism based on label-free quantitative proteomic technique - Zi-Xuan Wu; Yan-Hong Bai; Zi-Ye Wang; Ying-Chen Fan; Liang Song; Yu-Xin Liu; De-Yang Li; Peng-Fei Jiang; Da-Yong Zhou (Food Chemistry, 2023)

Thermophysical and molecular mechanisms of a novel and cost-efficient Cr-contaminated soil stabilization by steam flash heating - Xiaolu Fan; Tianyun Wu; Xue Wu; Bo Jiang; Jing Xiong; Fei Li; Shupeng Li; Lei Zheng; Yunpeng Liu; Dayi Zhang (Chemical Engineering Journal, 2023)

Comparison of the cross-protection of PPRSV sublineage 8.7 MLV vaccines against the recombinant NADC30-like strain - Jianda Li; Kai Meng; Yu Wang; Zhao Wang; Jun Peng; Sufang Ren; Yuyu Zhang; Lihui Guo; Fei Liu; Tingting Lv; Jian Jiao; Yanyan Liu; et al. (Veterinary Microbiology, 2023)

C-shaped porous polypropylene fibers for rapid oil absorption and effective on-line oil spillage monitoring - Zheng Li; Fei Jiang; Guojun Jiang; Fuyou Chen; Hui Ma; Yawen Zhao; Zhijuan Sun; Xiangyu Ye; Congjie Gao; Lixin Xue (Journal of Hazardous Materials, 2023)

Dynamics of dominant rhizospheric microbial communities responsible for trichlorfon absorption and translocation in maize seedlings - Qiqiang Li; Peiying Wang; Caihua Zou; Fei Ge; Feng Li; Yun Liu; Dayi Zhang; Jiang Tian (Journal of Hazardous Materials, 2023)

Plasma-reconstructed LaMnO3 nanonetwork supported palladium catalyst for methane catalytic combustion - Jinlin Jiang; Cuicui Wang; Shuai Zhao; Fan Xue; Lei Li; Mifen Cui; Xu Qiao; Zhaoyang Fei (Journal of Environmental Chemical Engineering, 2023)

Effects of dietary oat supplementation on carcass traits, muscle metabolites, amino acid profiles, and its association with meat quality of Small-tail Han sheep - Li-wei Wang; Shao-feng Su; Jie Zhao; Xiao-long He; Shao-yin Fu; Biao Wang; Yun-fei Wang; Da-qing Wang; Na-na Yun; Xin Chen; Damien P Belobrajdic; Terigele; et al. (Food Chemistry, 2023)

Reinforcing supramolecular hyaluronan hydrogels via kinetically interlocking multiple-units strategy - Ruofan Chen; Yujie Li; Yu Jin; Yawei Sun; Zhiyong Zhao; Yun Xu; Jiang-Fei Xu; Yuanchen Dong; Dongsheng Liu (Carbohydrate Polymers, 2023)

The mechanisms of rapid seed germination in Caragana species adapted to low mean annual precipitation - Shi-Hua Qi; Guang-Qian Yao; Md. Mahadi Hasan; Hui Jiang; Xu-Dong Liu; Zheng-Fei Nie; Xia-Yi Zhang; Ya-Xian Du; Xue-Qian Tian; Feng-Ping Li; Xue-Rong Li; Xiang-Wen Fang (Trees, 2023)

CBX7 Rejuvenates Late Passage Dental Pulp Stem Cells by Maintaining Stemness and Pro-angiogenic Ability - Yu Wu; Bing Li; Dandan Yu; Zhixuan Zhou; Ming Shen; Fei Jiang (Tissue Engineering and Regenerative Medicine, 2023)

Impact history and origin of lunar meteorite Northwest Africa 15528 - Runchuan Liu; Huaiyu He; Thomas Smith; Hanqing Ye; Huapei Wang; Xuhang Zhang; Fei Su; Ziheng Liu; Wei Guo; Peng Yang; Chuantong Zhang; Dingshuai Xue; et al. (Science China Earth Sciences, 2023)

Correction to: HYOU1 promotes cell proliferation, migration, and invasion via the PI3K/AKT/FOXO1 feedback loop in bladder cancer - Weiguo Wang; Xinjie Jiang; Fei Xia; Xudong Chen; Guojun Li; Lizhuan Liu; Qiang Xu; Min Zhu; Cheng Chen (Molecular Biology Reports, 2023)

Effects of Surface Mulching on Soil Water Temperature, Physiological Characteristics and Yield of Maize - Lihua Zhang; Chen Xu; Weiping Yan; Guobo Tan; Ning Sun; Hongxiang Zhao; Fei Li; Jiang Yu; Xiangmeng Meng; Shaofeng Bian (International Journal of Plant Production, 2023)

RETRACTED ARTICLE: Ensemble learning-based gene signature and risk model for predicting prognosis of triple-negative breast cancer - Tiancheng Li; Siqi Chen; Yuqi Zhang; Qianqian Zhao; Kai Ma; Xiwei Jiang; Rongwu Xiang; Fei Zhai; Guixia Ling (Functional & Integrative Genomics, 2023)

Effects of disinfectants, sponge densities, water circulation rates, and vibration frequency on the artificial incubation of redclaw crayfish embryos - Cheng Shun; Jiang Wen-ping; Liu Shi-li; Chi Mei-li; Zheng Jian-bo; Liu Yi-nuo; Hang Xiao-ying; Peng Miao; Li Fei; Wang Dan-li (Aquaculture, 2023)

The Philippines’ hedging strategy against China in the South China Sea dispute: Based on the human-ocean regional system - Zenglin Han; Kaiping Jiang; Fei Peng; Shuqin Li (Marine Policy, 2023)

PM2.5 caused ferroptosis in spermatocyte via overloading iron and disrupting redox homeostasis - Jiankang Wang; Zhonghao Zhang; Fuquan Shi; Yingqing Li; Ying Tang; Chang Liu; Yimeng Wang; Jianping Chen; Xiao Jiang; Huan Yang; Lei Sun; Qing Chen; et al. (Science of The Total Environment, 2023)

Effects of transglutaminase and glucose oxidase on the properties of frozen dough: Water distribution, rheological properties, and microstructure - Wen-Tao Guo; Xue-Fei Yang; Yi-Shun Ji; Bin Hu; Wan-Guang Li; Xi-Yang Zhong; Shao-Tong Jiang; Zhi Zheng (Journal of Cereal Science, 2023)

Evaluating the performance of a novel ventilated embankment structure in warm permafrost regions by numerical simulation - Zhanyuan Zhu; Zonghang He; Fei Luo; Bin Luo; Chenxuan Tang; Zuyin Zou; Zihong Guo; Weimin Xiao; Xiangang Jiang; Lin Li (Cold Regions Science and Technology, 2023)

Metabolomics analysis reveals cytotoxic effects of ouabain towards psoriatic keratinocytes via impairment of glutathione metabolism - Xuan Zhou; Fei Fei; Wei Song; Hehua Ma; Zhenzhen Xu; Jing Yue; Bei Cao; Runbin Sun; Yu Zhao; Yuanxun Yang; Junyi Jiang; Yan Geng; et al. (Molecular Genetics and Genomics, 2023)
Ouabain is a cardiac glycoside long studied for treating heart diseases, but the attempts to evaluate its anti-psoriatic activity have not been reported. We aimed to explore the effects of ouabain on proliferation and metabolism towards psoriatic keratinocytes. In human HaCaT keratinocytes, ouabain potently decreased viability, promoted apoptosis and caused G2/M cycle arrest. Metabolomics analysis indicated that ouabain markedly impaired glutathione metabolism. The solute carrier family 7 member 11 (SLC7A11) is an amino acid transporter highly specific to cysteine, which is critical for glutathione synthesis. Ouabain downregulated SLC7A11, reduced cysteine uptake and subsequently inhibited glutathione synthesis, probably through inhibiting Akt/mTOR/beclin axis that regulate protein activity of SLC7A11. The impaired glutathione synthesis and oxidative stress caused by ouabain may contribute to its cytotoxicity towards psoriatic keratinocytes. Our results provide experimental evidence supporting further study of ouabain as a potential anti-psoriatic agent.

Insight into tetrahydrofuran lignans from Isatis indigotica fortune with neuroprotective and acetylcholinesterase inhibitor activity - Yu-Fei Xi; Ming Bai; Xin Zhang; Zi-Lin Hou; Bin Lin; Guo-Dong Yao; Li-Li Lou; Xiao-Bo Wang; Shao-Jiang Song; Xiao-Xiao Huang (Phytochemistry, 2023)

Corrigendum to “SVR-based weighted processing method for electrical imaging logging in oil-based mud” [Journal of Applied Geophysics 209 (2023) 104911] - Jianshen Gao; Dan Li; Liming Jiang; Chunli Lu; Kairan Zhu; Fei Xue (Journal of Applied Geophysics, 2023)

Devonian subduction retreat recorded in the Chinese Altai Orogen: Petro-structural and geochronological constraints from orogenic lower crust migmatite-granite complexes - Ling-Zhu Kong; Ying-De Jiang; Peng-Fei Li; Stephen Collett; Ming Xiao (Journal of Asian Earth Sciences, 2023)

Effect of air frying and baking on physicochemical properties and digestive properties of scallop (Patinopecten yessoensis) adductor muscle - Zi-Ye Wang; Zi-Xuan Wu; Guan-Hua Zhao; De-Yang Li; Yu-Xin Liu; Lei Qin; Peng-Fei Jiang; Da-Yong Zhou (Food Bioscience, 2023)

Corrigendum to “Fire resistance of post-earthquake steel beams insulated with a novel fire-resistive coating- FR-ECC” [Eng. Struct. 246 (2021) 112887] - Zi-wei Cai; Jiang-tao Yu; Li-kang Tian; Fei-chi Liu; Ke-quan Yu (Engineering Structures, 2023)

Fiber-reinforced alumina-carbon core-shell aerogel composite with heat-induced gradient structure for thermal protection up to 1800 °C - Fengqi Liu; Yonggang Jiang; Fei Peng; Junzong Feng; Liangjun Li; Jian Feng (Chemical Engineering Journal, 2023)

Removal of Tetracycline Hydrochloride by Ball-Milled Mulberry Biochar - Zhongpu Yu; Licheng Ji; Yihan Zuo; Feiyan Zhang; Chengcheng Wei; Fei Jiang; Xianju Fu; Wenge Wu; Jian Du; Chengxia Chen; Feiyue Li (Water, Air, & Soil Pollution, 2023)

Submarine groundwater discharge in Dongshan Bay, China: A master regulator of nutrients in spring and potential national significance of small bays - Yafei Sun; Guizhi Wang; Yubin Weng; Qing Li; Fei Zhang; Weizhen Jiang; Guiyuan Dai; Wen Lin; Shengyao Sun; Yiyong Jiang; Yuanjing Zhang (Frontiers in Marine Science, 2023)
Despite over 90% of China’s coastal bays have an area less than 500 km 2 , the geochemical effects of SGD on those ecosystems are ambiguous. Based on mapping and time-series observations of Ra isotopes and nutrients, a case study of small bays (<500 km 2 ), we revealed that submarine groundwater discharge (SGD) predominately regulated the distribution of nutrients and fueled algal growth in Dongshan Bay, China. On the bay-wide scale, the SGD rate was estimated to be 0.048 ± 0.022 m day −1 and contributed over 95% of the nutrients. At the time-series site where the bay-wide highest Ra activities in the bottom water marked an SGD hotspot with an average rate an order of magnitude greater, the maximum chlorophyll concentration co-occurred, suggesting that SGD may support the algal bloom. The ever-most significant positive correlations between 228 Ra and nutrients throughout the water column (P< 0.01, R 2 > 0.90 except for soluble reactive phosphorus in the surface) suggested the predominance of SGD in controlling nutrient distribution in the bay. Extrapolated to a national scale, the SGD-carried dissolved inorganic nitrogen flux in small bays was twice as much as those in large bays (>2,000 km 2 ). Thus, the SGD-carried nutrients in small bays merit immediate attention in environmental monitoring and management.

Assessment of toxic mechanisms and mode of action to three different levels of species for 14 antibiotics based on interspecies correlation, excess toxicity, and QSAR - Jin J. Li; Ya X. Yue; Jie F. Jiang; Sheng J. Shi; Hui X. Wu; Yuan H. Zhao; Fei F. Che (Chemosphere, 2023)

Rapid detection of sesame oil multiple adulteration using a portable Raman spectrometer - Xue Li; Du Wang; Fei Ma; Li Yu; Jin Mao; Wen Zhang; Jun Jiang; Liangxiao Zhang; Peiwu Li (Food Chemistry, 2023)

Room-temperature synthesis of nitrogen-rich conjugated microporous polymers for solid-phase extraction of trace synthetic musks - Ye-Fei Fan; Hai-Long Jiang; Xiang-Feng Chen; Na Li; Xiao-Li Wang; Jin-Ming Lin; Ru-Song Zhao (Food Chemistry, 2023)

Differences in texture and digestive properties of different parts in boiled abalone muscles - Man-Man Yu; Ying-Chen Fan; De-Yang Li; Yu-Xin Liu; Peng-Fei Jiang; Da-Yong Zhou; Bei-Wei Zhu (Food Chemistry, 2023)

Inhibition of phosphorylated calcium/calmodulin-dependent protein kinase IIα relieves streptozotocin-induced diabetic neuropathic pain through regulation of P2X3 receptor in dorsal root ganglia - Xiao-fen He; Yu-rong Kang; Xue-yu Fei; Lu-hang Chen; Xiang Li; Yi-qi Ma; Qun-qi Hu; Si-ying Qu; Han-zhi Wang; Xiao-mei Shao; Bo-yi Liu; Yi-Liang; et al. (Purinergic Signalling, 2023)
Diabetic neuropathic pain (DNP) is frequent among patients with diabetes. We previously showed that P2X3 upregulation in dorsal root ganglia (DRG) plays a role in streptozotocin (STZ)-induced DNP but the underlying mechanism is unclear. Here, a rat model of DNP was established by a single injection of STZ (65 mg/kg). Fasting blood glucose was significantly elevated from the 1 st to 3 rd week. Paw withdrawal thresholds (PWTs) and paw withdrawal latencies (PWLs) in diabetic rats significantly reduced from the 2 nd to 3 rd week. Western blot analysis revealed that elevated p-CaMKIIα levels in the DRG of DNP rats were accompanied by pain-associated behaviors while CaMKIIα levels were unchanged. Immunofluorescence revealed significant increase in the proportion of p-CaMKIIα immune positive DRG neurons (stained with NeuN) in the 2 nd and 3 rd week and p-CaMKIIα was co-expressed with P2X3 in DNP rats. KN93, a CaMKII antagonist, significantly reduce mechanical hyperalgesia and thermal hyperalgesia and these effects varied dose-dependently, and suppressed p-CaMKIIα and P2X3 upregulation in the DRGs of DNP rats. These results revealed that the p-CaMKIIα upregulation in DRG is involved in DNP, which possibly mediated P2X3 upregulation, indicating CaMKIIα may be an effective pharmacological target for DNP management.

Teleost TRAF7, a protein functions in the host antiviral responses via NF-κB and IRF3/7 mediated signaling - Peng Tian Li; Ying Li; Ying Chen; Jia Xi Zhang; Zi Hao Luo; Yi Fan Zhang; Jing Jiang; Yi Lei Wang; Zi Ping Zhang; Yong Hua Jiang; Peng Fei Zou (Frontiers in Marine Science, 2023)
Tumor necrosis factor receptor-associated factors (TRAFs) play vital roles in tumor necrosis factor receptor (TNF-R) and interleukin-1 receptor/Toll-like receptor (IL-1R/TLR) mediated signaling pathway. However, the role that TRAF7 plays in the host immune responses is largely unknown in comparison to the extensive and in-depth research that has been conducted on other members of the TRAF family. Notably, Lc -TRAF7, a cloned TRAF7 ortholog, was discovered in the large yellow croaker ( Larimichthys crocea ) in the current study, which has an open reading frame (ORF) of 1,962 base pairs and encodes a protein of 653 amino acids (aa). Lc -TRAF7 is consisted of a RING finger domain, a coiled-coil domain, and seven WD40 domains, with the genomic organization consisted of 20 exons and 19 introns. According to the expression analysis, Lc-TRAF7 was presented in a wide range of detected organs and tissues of the healthy fish, and was able to significantly induced by stimulations of poly I:C, LPS, PGN, and Pseudomonas plecoglossicida infection. Subcellular distribution analysis revealed that Lc- TRAF7 was a cytoplasmic protein, with the RING finger and coiled-coil domain function importantly in its subcellular localization. Luciferase assays demonstrated that Lc -TRAF7 overexpression significantly induced the activation of NF-κB, IRF3, IRF7, and IFN1 promoters. In addition, the WD40 domains play a pivotal role in the NF-κB promoter activation, whereas the RING finger and coiled-coil domain were essential in the IRF3, IRF7, and IFN1 promoter activation. Notably, Lc -TRAF7 overexpression could suppress SVCV proliferation in EPC cells, and the expression levels of IRF3 , IRF7 , ISG15, ISG56 , RSAD2 , and TNF-α were up-regulated under Lc -TRAF7 overexpression in LYCMS cells. These findings collectively implied that Lc -TRAF7 may function as an important regulator in the host antiviral responses via the NF-κB as well as IRF3/7 involved signaling pathways.

Maternal exposure to 4-vinylcyclohexene diepoxide during pregnancy induces subfertility and birth defects of offspring in mice - Wei Song; Ang Li; Qian-Qian Sha; Shao-Yuan Liu; Yong Zhou; Chang-Yin Zhou; Xue Zhang; Xiao-Zhen Li; Jia-Xin Jiang; Fei Li; Chao Li; Heide Schatten; et al. (Science of The Total Environment, 2023)

RETRACTED: Boronic acid-modified bacterial cellulose microspheres as packing materials for enveloped virus removal - Zhiyang Lin; Linhan Li; Kaige Song; Bin Yang; Guoqing Zhou; Gengrong Zhang; Jiang Teng; Erlong Wang; Xiaoqiang Liu; Fei Ling; Gaoxue Wang; Tianqiang Liu (Science of The Total Environment, 2023)

SVR-based weighted processing method for electrical imaging logging in oil-based mud - Jianshen Gao; Dan Li; Liming Jiang; Chunli Lu; Kairan Zhu; Fei Xue (Journal of Applied Geophysics, 2023)

LDH derived Co-Al nanosheet for lipid hydrotreatment to produce green diesel - Zeng Zhang; Fei Wang; Jianchun Jiang; Hao Zhu; Yuchan Du; Junfeng Feng; Hui Li; Xiaoxiang Jiang (Fuel, 2023)

Penicillium oxalicum augments soil lead immobilization by affecting indigenous microbial community structure and inorganic phosphate solubilization potential during microbial-induced phosphate precipitation - Fei Tang; Qiqiang Li; Jiaru Yue; Fei Ge; Feng Li; Yun Liu; Dayi Zhang; Jiang Tian (Environmental Pollution, 2023)

Improving the regional deployment of carbon mitigation efforts by incorporating air-quality co-benefits: A multi-provincial analysis of China - Hong-Dian Jiang; Pallav Purohit; Qiao-Mei Liang; Li-Jing Liu; Yu-Fei Zhang (Ecological Economics, 2023)

Porous N-doped C/VB-group VS2 composites derived from perishable garbage to synergistically solve the environmental and electromagnetic pollution - Jie Cheng; Haojie Jiang; Lei Cai; Fei Pan; Yuyang Shi; Xiao Wang; Xiang Zhang; Shunda Lu; Yang Yang; Lixin Li; Zheng Xiu; Jingli Wang; et al. (Chemical Engineering Journal, 2023)

Rapid, linear, and highly reliable structural-color switching enabled by thermal regulation of chiral nematic mesophases - Dong Li; Rong-Rong Jiang; Si-Kai Chen; Jia-Min Wu; Xiu Dong; Xiu-Li Wang; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2023)

Chemical constituents from the roots of Angelica acutiloba and their chemotaxonomic significance - Fei-Fei Geng; Zhe Jiang; Yong-Hu Chen; Ning Li; Xue-Zheng Li (Biochemical Systematics and Ecology, 2023)

Roles of Multisourced Fluids in the Formation of Sandstone-Hosted Uranium Deposits in the SW Songliao Basin, NE China - Zhibing Feng; Fengjun Nie; Li Jiang; Fei Xia; Jianfang Cai; Bocheng Zhang; Yayun Lu; Liangliang Zhang (Journal of Earth Science, 2023)

Evaluation of dietary Haematococcus pluvialis in pilot-scale farming of Litopenaeus vannamei: Effects on production performance, physiological health, bacterial communities, and eukaryotic plankton - Fei Huang; Dengfeng Xue; Ze Li; Sheng Dong; Fajun Jiang; Zhangli Hu; Yihong Zheng (Aquaculture, 2023)

Hypoxia mediates Hif-1α to affect myofiber development and Vc regulates the influence by activating Shh-Gli pathway in channel catfish (Ictalurus punctatus) - Kang Xiao; Xi Wang; Yong-jun Dai; Yang-yang Huang; Mang-mang Wang; Hui-Xing Guo; Wen-Bin Liu; Xiang-fei Li; Kenneth Prudence Abasubong; Guang-Zhen Jiang (Aquaculture, 2023)

Effects of light color, photoperiod, and growth-related gene interference or overexpression on the survival, growth, or physiological and biochemical indices of red claw crayfish juveniles - Shun Cheng; Jian-bo Zheng; Yong-yi Jia; Mei-li Chi; Wen-ping Jiang; Shi-li Liu; Fei Li; Yi-nuo Liu; Zhi-min Gu; Dan-li Wang (Aquaculture, 2023)

Hypoxia alters glucose and lipid metabolisms in golden pompano (Trachinotus blochii) - Tian Jiang; Jun Long Sun; Yue Gu; Fu Cheng Yao; Ye Song Liang; Yi Fan Liu; Kai Xi Zhang; Fei Biao Song; Li Zhou; Zhong Wei Wang; Jian Fang Gui; Jian Luo (Aquaculture, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Fe-N-C single-atom nanozyme for ultrasensitive, on-site and multiplex detection of mycotoxins using lateral flow immunoassay - Xinfa Cai; Fei Ma; Jun Jiang; Xianglong Yang; Zhaowei Zhang; Zelang Jian; Meijuan Liang; Peiwu Li; Li Yu (Journal of Hazardous Materials, 2023)

Changes in the gene expression and gut microbiome to the infection of decapod iridescent virus 1 in Cherax quadricarinatus - Jianbo Zheng; Yongyi Jia; Fei Li; Meili Chi; Shun Cheng; Shili Liu; Wenping Jiang; Yinuo Liu (Fish & Shellfish Immunology, 2023)

Association between ambient carbon monoxide levels and hospitalization costs of patients with myocardial infarction: Potential effect modification by ABO blood group - Qing-Song Huang; Lai-Xin Zhou; Li-Li Yang; Yue-Xu Jiang; Hua Xiao; Da-Wei Li; Yu-Meng Zhou; Yue-Gu Hu; Na Li; Ya-Fei Li; Ai-Ling Ji; Peng Luo; et al. (Environmental Research, 2023)

Carbon layer encapsulation strategy for designing multifunctional core-shell nanorod aerogels as high-temperature thermal superinsulators - Fengqi Liu; Chenbo He; Yonggang Jiang; Yaping Yang; Fei Peng; Lanfang Liu; Jing Men; Junzong Feng; Liangjun Li; Guihua Tang; Jian Feng (Chemical Engineering Journal, 2023)

Revelation of Mn4+-Osur-Mn3+ active site and combined Langmuir-Hinshelwood mechanism in propane total oxidation at low temperature over MnO2 - Chao Feng; Fei Jiang; Gaoyan Xiong; Chong Chen; Zhong Wang; Yuan Pan; Zhaoyang Fei; Yukun Lu; Xuebing Li; Runduo Zhang; Yunqi Liu (Chemical Engineering Journal, 2023)

HYOU1 promotes cell proliferation, migration, and invasion via the PI3K/AKT/FOXO1 feedback loop in bladder cancer - Weiguo Wang; Xinjie Jiang; Fei Xia; Xudong Chen; Guojun Li; Lizhuan Liu; Qiang Xu; Min Zhu; Cheng Chen (Molecular Biology Reports, 2023)

Will the Historic Southeasterly Wind over the Equatorial Pacific in March 2022 Trigger a Third-year La Niña Event? - Xianghui Fang; Fei Zheng; Kexin Li; Zeng-Zhen Hu; Hongli Ren; Jie Wu; Xingrong Chen; Weiren Lan; Yuan Yuan; Licheng Feng; Qifa Cai; Jiang Zhu (Advances in Atmospheric Sciences, 2023)

Darwin's naturalization conundrum reconciled by changes of species interactions - Jiang Wang; Shao‐Peng Li; Yuan Ge; Xiao‐Yan Wang; Song Gao; Tong Chen; Fei‐Hai Yu (Ecology, 2023)
Although phylogenetic distance between native and exotic species has a close link with their interactions, it is still unclear how environmental stresses and species interactions influence the relationship between phylogenetic distance and biological invasions. Here we assessed the effect of invader–native phylogenetic distance on the growth of the invader ( Symphyotrichum subulatum ) under three levels of drought (no, moderate, or intense drought). Under no drought, interspecific competition between close relatives was the dominant process and native communities more closely related to the invader showed higher resistance to invasion, supporting Darwin's naturalization hypothesis. In contrast, under intense drought, facilitation between close relatives by mutualism with arbuscular mycorrhizal fungi (AMF) became more important, and the invader became more successful in their more closely related native communities, supporting the preadaptation hypothesis. The colonization rate of AMF of the invader was higher in more closely related native communities regardless of the drought treatment, but it was only positively related to invader biomass under intense drought. Therefore, the shift of species interactions from competition to facilitation may be ascribed to the promotion of AMF to invasion occurring under intense drought, which leads to the effect of closely related natives on the invader shifting from negative to positive. Our results provide a new angle to resolve Darwin's naturalization conundrum from the change of species interactions along a stress gradient, and provide important clues for invasion management when species interactions change in response to global climatic change.

Acute transcriptomic changes in murine RAW 264.7 cells following pseudorabies virus infection - Chao Tong; Peng-Fei Fu; Sheng-Li Ming; Lei Zeng; He-Shui Zhu; Jiang Wang (Archives of Virology, 2022)

The association between short-term ambient sulfur dioxide exposure and hospitalization costs of ischemic stroke: a hospital-based study in Chongqing, China - En-Jie Tang; Yu-Meng Zhou; Li-Li Yang; Nan Wang; Yue-Xu Jiang; Hua Xiao; Yue-Gu Hu; Da-Wei Li; Na Li; Qing-Song Huang; Ning Du; Ya-Fei Li; et al. (Environmental Science and Pollution Research, 2022)

Enhanced Adsorption of Methylene Blue Using H2O2-Modified Hydrochar - Chengcheng Wei; Feiyue Li; Zhongpu Yu; Licheng Ji; Fei Jiang; Chengxia Chen; Jing Yang (Water, Air, & Soil Pollution, 2022)

Genome-wide association study reveals a NAC transcription factor TaNAC074 linked to pre-harvest sprouting tolerance in wheat - Hao Jiang; Yu Fang; Dong Yan; Si-tong Liu; Jun Wei; Fei-long Guo; Xing-ting Wu; Hong Cao; Chang-bin Yin; Fei Lu; Li-feng Gao; Yong-xiu Liu (Theoretical and Applied Genetics, 2022)

Plant hormone signals regulate trehalose accumulation against osmotic stress in watermelon cells - Fangming Zhu; Mingyan Li; Mengli Sun; Xuefei Jiang; Fei Qiao (Protoplasma, 2022)

Effects of straw returning on soil moisture and maize yield in semi-humid area - Lihua Zhang; Hongxiang Zhao; Chen Xu; Weiping Yan; Ning Sun; Guobo Tan; Jiang Yu; Xiangmeng Meng; Fei Li; Shaofeng Bian (Cereal Research Communications, 2022)

Comparative transcriptome analysis of the differentiating gonads in Scatophagus argus - Umar Farouk Mustapha; You-Xing Peng; Yuan-Qing Huang; Daniel Assan; Fei Zhi; Gang Shi; Yang Huang; Guang-Li Li; Dong-Neng Jiang (Frontiers in Marine Science, 2022)
The reproductive-related studies, including genetic and genomic such as gonadal transcriptome analyses, have previously focused on the adult spotted scat, with little information on juvenile fish. Transcriptomics is a powerful tool that allows for massive parallel analysis to identify differential expression and the patterns of gene expression holistically at a particular stage in a cell or tissue development. This study presents the first report on gonadal transcriptome analysis of the differentiating (juvenile; 4 months after hatch; stage I ovary and testis) spotted scat gonads. The study revealed potential reproduction and gonadal development-related genes. A total of 25936 genes were identified, of which 16248 were co-expressed, 17893 and 17258 expressed in males and females, respectively, from sequence data of testis I (n = 3) and ovary I (n = 2). A total of 6549 differentially expressed genes (DEGs) were identified between males and females. Genes attributable to male gonad development pathway such as dmrt1 , gsdf , and amh are significantly expressed in differentiating testes, while female-related genes such as foxl2, cyp19a1a, 42sp50 and sox3 were expressed considerably in differentiating ovaries. In addition, dmrt1/dmrt1y was not expressed in the female (FPKM=0.00), while its paralog dmrt1b was expressed in both males and females. In the male pathway, dmrt1y and gsdf are critical for sex determination and maintenance while foxl2/foxl3 and cyp19a1a are critical in the female development pathway. The current studies provide an insight into the expression patterns of sex and gonadal-related genes in differentiating gonads of spotted scat.

First account of a transient intersex in spotted scat, Scatophagus argus: a marine gonochoristic fish - Umar Farouk Mustapha; Fei Zhi; Yuang-Qing Huang; Daniel Assan; Guang-Li Li; Dong-Neng Jiang (Fish Physiology and Biochemistry, 2022)

Feed types affect the growth, nutrient utilization, digestive capabilities, and endocrine functions of Megalobrama amblycephala: a comparative study between pelleted and extruded feed - Chao-Fan He; Xiang-Fei Li; Guang-Zhen Jiang; Ling Zhang; Miao Sun; Ya-Ping Ge; Wei-Liang Chen; Wen-Bin Liu (Fish Physiology and Biochemistry, 2022)

Sphingopyxis yananensis sp. nov., a novel 2-nitropropane degrading bacterium isolated from a microbial fermentation bed substrate - Chao-chao Zheng; Ying-ying Jiang; Tian-fei Yu; Jing Li; Jia-min Ai; Mai-ping Li; Xiao-dong Liu; Zhen-shan Deng (Archives of Microbiology, 2022)

The Impact of Economic Development of the Guangdong-Hongkong-Macao Greater Bay Area on Air Pollution: Investigation Based on Remote Sensing Data of Nighttime Lights and Air Pollution - Xiaole Ji; Shaoxing Li; Na Jiang; Fei Wang; Liya Fan; Xiao Niu (Frontiers in Marine Science, 2022)
Whether the Guangdong-Hongkong-Macao Greater Bay Area (GBA) can achieve the goal of environmental protection at the same time as its rapid economic development is an important issue that deserves attention. In this paper, we obtained remote sensing data on air pollution including CO, NO 2 , SO 2 , PM 10 , PM 2.5 , and nighttime light data. We combined the remote sensing data with county-level economic statistics to study economic development and air pollution in the Guangdong-Hongkong-Macao GBA. Our research showed that the economic development in the Guangdong-Hongkong-Macao GBA significantly increased the emissions of NO 2 , PM 10 , and PM 2.5 and did not have significant effects on CO and SO 2 . We constructed an emission intensity indicator of pollutants per unit of luminance. We found that the unit emission intensity of four categories of pollutants, PM 10 , PM 2.5 , SO 2 , and CO, showed a significant decreasing trend in line with economic development. The emission intensity of NO 2 showed a trend of first decreasing and then increasing. The conclusion of this research illustrates that the emission intensity of pollutants per unit of luminosity in the Guangdong-Hongkong-Macao GBA is continuously reducing. The emission of pollutants will gradually change from slow growth to zero growth. However, the emission of NO 2 pollution should be an area of focus in achieving the dual goals of economic development and environmental protection.

Metagenomic analysis reveals wide distribution of phototrophic bacteria in hydrothermal vents on the ultraslow-spreading Southwest Indian Ridge - Hong Chen; Deng Hui Li; Ai Jun Jiang; Xue Gong Li; Shi Jun Wu; Jian Wei Chen; Meng Jie Qu; Xiao Qing Qi; Jie Dai; Rui Zhao; Wei-Jia Zhang; Shan Shan Liu; et al. (Marine Life Science & Technology, 2022)

Chemical constituents of Viscum coloratum (Kom.) Nakai and their cytotoxic activities - Ying-Ying Chen; Jiang-Ping Hou; Ling Huang; Afsar Khan; Fei-Fei Xing; Xiao-Han Zhang; De-Feng Han; Shi-Li Yan; Gui-Dong Cao; Qi-Yang Jiao; Dejie Liu; Xuwei Zhu; et al. (Natural Product Research, 2022)

Crocin Alleviates Intracerebral Hemorrhage–Induced Neuronal Ferroptosis by Facilitating Nrf2 Nuclear Translocation - Fei Wang; Wu-lin Li; Li-juan Shen; Ting-ting Jiang; Jian-jun Xia; Da-li You; Shan-you Hu; Li Wang; Xiao Wu (Neurotoxicity Research, 2022)

Pyrroloquinoline quinone ameliorates liver injury in mice induced by cyclophosphamide - Li Qian; Fei Yang; Xinhui Lin; Su Jiang; Yun Zhang; Yunping Tang (Environmental Science and Pollution Research, 2022)

Analysis of complexity and dynamic functional connectivity based on resting-state EEG in early Parkinson’s disease patients with mild cognitive impairment - Guosheng Yi; Liufang Wang; Chunguang Chu; Chen Liu; Xiaodong Zhu; Xiao Shen; Zhen Li; Fei Wang; Manyi Yang; Jiang Wang (Cognitive Neurodynamics, 2022)

The Predictability of Ocean Environments that Contributed to the 2020/21 Extreme Cold Events in China: 2020/21 La Niña and 2020 Arctic Sea Ice Loss - Fei Zheng; Ji-Ping Liu; Xiang-Hui Fang; Mi-Rong Song; Chao-Yuan Yang; Yuan Yuan; Ke-Xin Li; Ji Wang; Jiang Zhu (Advances in Atmospheric Sciences, 2022)
Several consecutive extreme cold events impacted China during the first half of winter 2020/21, breaking the low-temperature records in many cities. How to make accurate climate predictions of extreme cold events is still an urgent issue. The synergistic effect of the warm Arctic and cold tropical Pacific has been demonstrated to intensify the intrusions of cold air from polar regions into middle-high latitudes, further influencing the cold conditions in China. However, climate models failed to predict these two ocean environments at expected lead times. Most seasonal climate forecasts only predicted the 2020/21 La Niña after the signal had already become apparent and significantly underestimated the observed Arctic sea ice loss in autumn 2020 with a 1–2 month advancement. In this work, the corresponding physical factors that may help improve the accuracy of seasonal climate predictions are further explored. For the 2020/21 La Niña prediction, through sensitivity experiments involving different atmospheric–oceanic initial conditions, the predominant southeasterly wind anomalies over the equatorial Pacific in spring of 2020 are diagnosed to play an irreplaceable role in triggering this cold event. A reasonable inclusion of atmospheric surface winds into the initialization will help the model predict La Niña development from the early spring of 2020. For predicting the Arctic sea ice loss in autumn 2020, an anomalously cyclonic circulation from the central Arctic Ocean predicted by the model, which swept abnormally hot air over Siberia into the Arctic Ocean, is recognized as an important contributor to successfully predicting the minimum Arctic sea ice extent.

The 2020/21 Extremely Cold Winter in China Influenced by the Synergistic Effect of La Niña and Warm Arctic - Fei Zheng; Yuan Yuan; Yihui Ding; Kexin Li; Xianghui Fang; Yuheng Zhao; Yue Sun; Jiang Zhu; Zongjian Ke; Ji Wang; Xiaolong Jia (Advances in Atmospheric Sciences, 2022)

Vermicompost Application Enhances Halophyte Suaeda salsa Performance and Improves Coastal Saline Soil Quality - Jing-Fang Cai; Xuan-Shao Liu; Kai Sun; Fan Jiang; Ming-Xiang Zhang; Hong-Li Li; Fei-Hai Yu (Journal of Soil Science and Plant Nutrition, 2022)

Litter nitrogen concentration changes mediate effects of drought and plant species richness on litter decomposition - Jiang Wang; Yuan Ge; Johannes H. C. Cornelissen; Xiao-Yan Wang; Song Gao; Yi Bai; Tong Chen; Zhong-Wang Jing; Chong-Bang Zhang; Wen-Li Liu; Jun-Min Li; Fei-Hai Yu (Oecologia, 2022)

Genesis of the Hebaoshan gold deposit in Fujian Province of Southeast China: constraints from a combined fluid inclusion, H-O-C-S-Pb-He-Ar isotope and geochronological study - Ying Ma; Shao-Yong Jiang; Hartwig E. Frimmel; Lü-Yun Zhu; Suo-Fei Xiong; Run-Sheng Chen; Xue-Xie Li (Mineralium Deposita, 2022)

Retraction Note to: Revisiting the male genetic landscape of China: a multi-center study of almost 38,000 Y-STR haplotypes - Michael Nothnagel; Guangyao Fan; Fei Guo; Yongfeng He; Yiping Hou; Shengping Hu; Jiang Huang; Xianhua Jiang; Wook Kim; Kicheol Kim; Chengtao Li; Hui Li; et al. (Human Genetics, 2022)

Review of the regional nomenclature and tectonic setting for mesozoic gold deposits in the Malanyu Anticline area of Eastern Hebei Province, North China - Leon Bagas; Frank Bierlein; Si-Hong Jiang; Yi-Fei Liu; Li-Li Zhang (International Geology Review, 2021)

Australian propolis ethanol extract exerts antibacterial activity against methicillin-resistant Staphylococcus aureus by mechanisms of disrupting cell structure, reversing resistance, and resisting biofilm - Fei Wang; Hui Liu; Junya Li; Wenwen Zhang; Bin Jiang; Hongzhuan Xuan (Brazilian Journal of Microbiology, 2021)

Thermohalobaculum xanthum gen. nov., sp. nov., a moderately thermophilic bacterium isolated from mangrove sediment - Xinli Pan; Zhe Li; Fei Li; Yuanlin Huang; Qiaozhen Wang; Shushi Huang; Wenjin Hu; Mingguo Jiang (Antonie van Leeuwenhoek, 2021)

Evaluation of the antiviral activity of naringenin, a major constituent of Typha angustifolia , against white spot syndrome virus in crayfish Procambarus clarkii - Zhong‐Chen Sun; Cheng Chen; Fei‐Fan Xu; Bing‐Ke Li; Jing‐Lei Shen; Tao Wang; Hai‐Feng Jiang; Gao‐Xue Wang (Journal of Fish Diseases, 2021)
White spot syndrome virus (WSSV) is a serious pathogen threatening global crustacean aquaculture with no commercially available drugs. Herbal medicines widely used in antiviral research offer a rich reserve for drug discovery. Here, we investigated the inhibitory activity of 13 herbal medicines against WSSV in crayfish Procambarus clarkii and discovered that naringenin (NAR) has potent anti‐WSSV activity. In the preliminary screening, the extracts of Typha angustifolia displayed the highest inhibitory activity on WSSV replication (84.62%, 100 mg/kg). Further, NAR, the main active compound of T. angustifolia, showed a much higher inhibition rate (92.85%, 50 mg/kg). NAR repressed WSSV proliferation followed a dose‐dependent manner and significantly improved the survival of WSSV‐challenged crayfish. Moreover, pre‐ or post‐treatment of NAR displayed a comparable inhibition on the viral loads. NAR decreased the transcriptional levels of vital genes in viral life cycle, particularly for the immediately early‐stage gene ie1 . Further results showed that NAR could decrease the STAT gene expression to block ie1 transcription. Besides, NAR modulated immune‐related gene Hsp70 , antioxidant ( cMnSOD, mMnSOD, CAT, GST ), anti‐inflammatory ( COX‐1 , COX‐2 ) and pro‐apoptosis‐related factors (Bax and BI‐1) to inhibit WSSV replication. Overall, these results suggest that NAR may have the potential to be developed as preventive or therapeutic agent against WSSV.

Association between large artery stenosis, cerebral small vessel disease and risk of ischemic stroke - Fei Han; Ding-Ding Zhang; Fei-Fei Zhai; Jun Xue; Jiang-Tao Zhang; Shuang Yan; Li-Xin Zhou; Jun Ni; Ming Yao; Meng Yang; Ming-Li Li; Zheng-Yu Jin; et al. (Science China Life Sciences, 2021)

Corticosterone Can Be an Essential Stress Index in Channel Catfish (Ictalurus punctatus) - Kang Xiao; Xi Wang; Wen-Bin Liu; Ding-Dong Zhang; Xiang-Fei Li; Chun-Nuan Zhang; Wei-Hua Chen; Kenneth Prudence Abasubong; Guang-Zhen Jiang (Frontiers in Marine Science, 2021)
Although cortisol is considered the main glucocorticoid involved in regulating stress in fish by elevating the serum glucose, the presence of serum corticosterone and whether its level can be used as an indicator for fish stress activation and reflect the degree of fish stress remains to be determined. To comprehensively and accurately evaluate the performance of two glucocorticoids after stress, in this study, seven of the most common stressors (ammonia nitrogen, high-temperature, acid, alkali, Aeromonas hydrophila, and salinity) in aquaculture were selected. The levels of serum corticosterone, cortisol, and glucose were detected within 48 h, and then the dynamic changes were analyzed. In addition, the kidneys were collected to detect the expression of corresponding proteins involved in corticosterone and cortisol synthesis (3 β-HSD and CYP17A1) for further exploration. From the results obtained, the content of serum corticosterone was about 100 times higher than that of cortisol, and it was found that corticosterone and cortisol showed different dynamic changes within 48 h among the seven kinds of stress. In the subsequent detection of glucose, it was found that the dynamic shift in glucose was not consistent with the dynamic changes of corticosterone or cortisol entirely but seemed to be caused by the combination of the two. In the follow-up protein expression detection, we found that corticosterone seemed to respond to stress earlier. Therefore, it is concluded that the responses of corticosterone and cortisol to stress are independent, corticosterone may be more sensitive in the current seven acute stresses, and then they regulate glucose together to resist stress. The study aimed to fill the vacancy of corticosterone in fish research and provide a reference for the complete evaluation of fish stress degree.

Different posterior hippocampus and default mode network modulation in young APOE ε4 carriers: a functional connectome-informed phenotype longitudinal study - Li Juan Zheng; Li Lin; U. Joseph Schoepf; Akos Varga-Szemes; Rock H. Savage; Han Zhang; Yun Fei Wang; Xin Yuan Zhang; Song Luo; Ya Liu; Gui Fen Yang; Guang Ming Lu; et al. (Molecular Neurobiology, 2021)

Temperature sensitivity of SOM decomposition is linked with a K‐selected microbial community - Hui Li; Shan Yang; Mikhail V. Semenov; Fei Yao; Ji Ye; Rencang Bu; Ruiao Ma; Junjie Lin; Irina Kurganova; Xugao Wang; Ye Deng; Irina Kravchenko; et al. (Global Change Biology, 2021)
Temperature sensitivity (Q 10 ) of soil organic matter (SOM) decomposition is a crucial parameter to predict the fate of soil carbon (C) under global warming. Nonetheless, the response pattern of Q 10 to continuous warming and the underlying mechanisms are still under debate, especially considering the complex interactions between Q 10 , SOM quality, and soil microorganisms. We examined the Q 10 of SOM decomposition across a mean annual temperature (MAT) gradient from −1.9 to 5.1°C in temperate mixed forest ecosystems in parallel with SOM quality and bioavailability, microbial taxonomic composition, and functional genes responsible for organic carbon decomposition. Within this temperature gradient of 7.0°C, the Q 10 values increased with MAT, but decreased with SOM bioavailability. The Q 10 values increased with the prevalence of K‐strategy of soil microbial community, which was characterized by: (i) high ratios of oligotrophic to copiotrophic taxa, (ii) ectomycorrhizal to saprotrophic fungi, (iii) functional genes responsible for degradation of recalcitrant to that of labile C, and (iv) low average 16S rRNA operon copy number. Because the recalcitrant organic matter was mainly utilized by the K‐strategists, these findings independently support the carbon quality‐temperature theory from the perspective of microbial taxonomic composition and functions. A year‐long incubation experiment was performed to determine the response of labile and recalcitrant C pools to warming based on the two‐pool model. The decomposition of recalcitrant SOM was more sensitive to increased temperature in southern warm regions, which might attribute to the dominance of K‐selected microbial communities. It implies that climate warming would mobilize the larger recalcitrant pools in warm regions, exacerbating the positive feedback between increased MAT and CO 2 efflux. This is the first attempt to link temperature sensitivity of SOM decomposition with microbial eco‐strategies by incorporating the genetic information and disentangling the complex relationship between Q 10 and soil microorganisms.

Interactions Between Ultraviolet B Radiation, Warming, and Changing Nitrogen Source May Reduce the Accumulation of Toxic Pseudo-nitzschia multiseries Biomass in Future Coastal Oceans - Kyla J. Kelly; Fei-Xue Fu; Xiaowen Jiang; He Li; Dong Xu; Nina Yang; Michelle A. DeMers; Joshua D. Kling; Kunshan Gao; Naihao Ye; David A. Hutchins (Frontiers in Marine Science, 2021)
Understanding the environmental conditions that trigger Pseudo-nitzschia bloom formation and domoic acid (DA) production is critical as the frequency and severity of these toxic blooms increases in the face of anthropogenic change. However, predicting the formation of these harmful blooms in a future ocean remains a challenge. Previous studies have examined the effects of single environmental drivers on Pseudo-nitzschia spp. growth and toxin production, but few have considered the interactions between them. In this multiple driver study with Pseudo-nitzschia multiseries , we used a full factorial matrix experimental design to examine the simultaneous effects of temperature (20 and 25°C), nitrogen source (nitrate and urea), and irradiance (photosynthetically active radiation with and without ultraviolet B radiation; UVB). This strain of P. multiseries was unable to withstand prolonged exposures (>0.5 h) to 0.06 mw⋅cm –2 UVB light, with implications for near-surface bloom formation if future shallower mixed layers increase UVB exposure. Growth rates were inhibited by UVB, but photosynthesis and carbon fixation continued at a reduced capacity. Additionally, DA synthesis continued despite UVB-induced growth inhibition. Warming by 5°C enhanced cellular DA quotas three-fold. Within these warmer treatments, urea-grown cultures exposed to UVB had the highest amount of DA per cell, suggesting that interactive effects between UVB exposure, warming, and urea can synergistically enhance toxin production. However, overall production of toxic biomass was low, as growth-integrated DA production rates were near zero. This indicates that although Pseudo-nitzschia multiseries cell-specific toxicity could worsen in an anthropogenically-altered future ocean, bloom formation may be inhibited by increased exposure to UVB. This multi-variable experimental approach revealed previously unknown interactions that could not have been predicted based on combined effects of single-variable experiments. Although P. multiseries DA production may be enhanced in a future ocean, inherent sensitivity to prolonged UVB exposure may moderate trophic transfer of toxin to coastal food webs.

Small-sized extracellular vesicles (EVs) derived from acute myeloid leukemia bone marrow mesenchymal stem cells transfer miR-26a-5p to promote acute myeloid leukemia cell proliferation, migration, and invasion - Dexiang Ji; Yue He; Wei Lu; Yanyan Rong; Fei Li; Xianbao Huang; Ruibin Huang; Yanxia Jiang; Guoan Chen (Human Cell, 2021)

Study on characteristics of waterflooding in fractured reservoirs based on discrete fracture model - Fanle Meng; Junjian Li; Hanqiao Jiang; Lin Zhao; Linkai Li; Yan Qiao; Yu Zhou; Fei Xu (Arabian Journal of Geosciences, 2021)

New biphenanthrenes with butyrylcholinesterase inhibitory activitiy from Cremastra appendiculata - Liang Liu; Qi-Meng Yin; Qian Gao; Jun Li; Yong Jiang; Peng-Fei Tu (Natural Product Research, 2021)

Thiazole-based and thiazolidine-based protein tyrosine phosphatase 1B inhibitors as potential anti-diabetes agents - Kexin Chen; Xu Yao; Ting Tang; Li-Mei Chen; Can Xiao; Jing-Yi Wang; Hong-Fei Chen; Zhong-Xing Jiang; Yi Liu; Xing Zheng (Medicinal Chemistry Research, 2021)

Hypoxia/reoxygenation-induced upregulation of miRNA-542-5p aggravated cardiomyocyte injury by repressing autophagy - Fei Wang; Xin Min; Shan-you Hu; Da-li You; Ting-ting Jiang; Li Wang; Xiao Wu (Human Cell, 2021)

SUMOylation of Pdia3 exacerbates proinsulin misfolding and ER stress in pancreatic beta cells - Na Li; Xi Luo; Qilin Yu; Ping Yang; Zhishui Chen; Xinqiang Wang; Jipin Jiang; Jing Xu; Quan Gong; Decio L. Eizirik; Zhiguang Zhou; Jiajun Zhao; et al. (Journal of Molecular Medicine, 2020)

Association of in-hospital intensive statins dosage and death in arteriosclerotic cardiovascular disease with percutaneous coronary intervention: insights of multicentre cohort from China - Peng-yuan Chen; Yuan-hui Liu; Chong-yang Duan; Hua-lin Fan; Li-huan Zeng; Wei Guo; Lei Jiang; Xue-biao Wei; Wen-fei He; Sha Tao; Zhi-qiang Guo; Ji-yan Chen; et al. (European Journal of Clinical Pharmacology, 2020)

Gut dysbiosis-influence on amygdala-based functional activity in patients with end stage renal disease: a preliminary study - Li Juan Zheng; Li Lin; Jianhui Zhong; Zhihong Zhang; Yu Bing Ye; Xin Yuan Zhang; Yun Fei Wang; Han Zhang; Ya Liu; Guang Ming Lu; Dehua Gong; Long Jiang Zhang (Brain Imaging and Behavior, 2020)

Archaeobotanical evidence reveals the human–environment interactions during the 9th–13th centuries at Turpan, Xinjiang on the ancient Silk Road - Yi-Feng Yao; Xia Wang; Wu Guo; Hong-En Jiang; Min Li; David K. Ferguson; Yu-Fei Wang; Cheng-Sen Li (Vegetation History and Archaeobotany, 2020)

An Unsymmetric Salamo-like Chemosensor for Fuorescent Recognition of Zn2+ - Yun-Dong Peng; Yu Zhang; Yuan-Li Jiang; Zong-Li Ren; Fei Wang; Li Wang (Journal of Fluorescence, 2020)

Retraction Note to: Explore on the effect of ATF6 on cell growth and apoptosis in cartilage development - Xiaofeng Han; Peng Zhang; Rong Jiang; Fei Xia; Meiling Li; Feng‑Jin Guo (Histochemistry and Cell Biology, 2020)

Effects of nitrogen source and N/P on growth and photosynthesis in the invasive marine macroalga Chaetomorpha valida - Chen Li-hong; Xing Rong-lian; Jiang Ai-li; Yao Ya-nan; Zhou Ge-fei (Environmental Science and Pollution Research, 2020)

Screening of three Chlorella mutant strains with high lipid production induced by 3 types of lasers - Kang Wang; Bin Lin; Chunxiao Meng; Zhengquan Gao; Zhe Li; Haonan Zhang; Huanmin Du; Fei Xu; Xiao Jiang (Journal of Applied Phycology, 2020)

Experimental investigation of the fracture grouting efficiency with consideration of the viscosity variation under dynamic pressure conditions - Chenghao Han; Weijie Zhang; Wenwu Zhou; Jianbin Guo; Fei Yang; Xiaoquan Man; Jigang Jiang; Chunrui Zhang; Yongjie Li; Zheng Wang; Hao Wang (Carbonates and Evaporites, 2020)

Excess DHA Induces Cell Cycle Arrest by Activating the P53/Cycling Pathway in Blunt Snout Bream (Megalobrama amblycephala) - Cong-cong Wang; Wen-bin Liu; Xiu-fei Cao; Yang-yang Huang; Xi Wang; Kang Xiao; Xiang-fei Li; Ding-dong Zhang; Guang-zhen Jiang (Frontiers in Marine Science, 2020)

Influences of glycyrrhetinic acid (GA) dietary supplementation on growth, feed utilization, and expression of lipid metabolism genes in channel catfish (Ictalurus punctatus) fed a high-fat diet - Hesham Eed Desouky; Guang-zhen Jiang; Ding-dong Zhang; Kenneth Prudence Abasubong; Xiangyang Yuan; Xiang-fei Li; Wen-bin Liu (Fish Physiology and Biochemistry, 2020)

The Arabidopsis UDP-glycosyltransferase75B1, conjugates abscisic acid and affects plant response to abiotic stresses - Ting-Ting Chen; Fang-Fei Liu; Dong-Wang Xiao; Xiao-Yi Jiang; Pan Li; Shu-Man Zhao; Bing-kai Hou; Yan-jie Li (Plant Molecular Biology, 2020)

Effect of Dietary Selenium Supplementation on Growth and Reproduction of Silkworm Bombyx mori L. - Li Jiang; Li-Li Peng; Yu-Yao Cao; Kiran Thakur; Fei Hu; Shun-Ming Tang; Zhao-Jun Wei (Biological Trace Element Research, 2020)

Research on crack propagation and rock fragmentation efficiency under spherical tooth dynamic indentation - Yong Deng; Fei Yin; Hucheng Deng; Jiang Li; Wei Liu (Arabian Journal of Geosciences, 2020)

Contribution of skeletal muscular glycine to rapid antidepressant effects of ketamine in an inflammation-induced mouse model of depression - Niannian Huang; Yue Wang; Gaofeng Zhan; Fan Yu; Shan Li; Dongyu Hua; Riyue Jiang; Shiyong Li; Yeshun Wu; Ling Yang; Bin Zhu; Fei Hua; et al. (Psychopharmacology, 2019)

Comparative transcriptome analysis of male and female gonads reveals sex-biased genes in spotted scat (Scatophagus argus) - Fei-Xiang He; Dong-Neng Jiang; Yuan-Qing Huang; Umar Farouk Mustapha; Wei Yang; Xue-Fan Cui; Chang-Xu Tian; Hua-Pu Chen; Hong-Juan Shi; Si-Ping Deng; Guang-Li Li; Chun-Hua Zhu (Fish Physiology and Biochemistry, 2019)

Major advances in studies of the physical geography and living environment of China during the past 70 years and future prospects - Fahu Chen; Bojie Fu; Jun Xia; Duo Wu; Shaohong Wu; Yili Zhang; Hang Sun; Yu Liu; Xiaomin Fang; Boqiang Qin; Xin Li; Tingjun Zhang; et al. (Science China Earth Sciences, 2019)

Scavenging activity and mechanism study of ferulic acid against reactive carbonyl species acrolein - Zhi-hao Tao; Chang Li; Xiao-fei Xu; Yuan-jiang Pan (Journal of Zhejiang University-SCIENCE B, 2019)

A novel method for sewage sludge composting using bamboo charcoal as a separating material - Yun-bei Li; Peng-fei Jin; Ting-ting Liu; Jing-hua Lv; Ji-shao Jiang (Environmental Science and Pollution Research, 2019)

Effects of dietary protein level on growth performance, digestive enzyme activity, and gene expressions of the TOR signaling pathway in fingerling Pelteobagrus fulvidraco - Qin Qin; Xiu-Fei Cao; Yong-jun Dai; Li-Na Wang; Ding-Dong Zhang; Guang-Zhen Jiang; Wen-Bin Liu (Fish Physiology and Biochemistry, 2019)

Pathological Alterations of Tau in Alzheimer’s Disease and 3xTg-AD Mouse Brains - Longfei Li; Yanli Jiang; Wen Hu; Yunn Chyn Tung; Chunling Dai; Dandan Chu; Cheng-Xin Gong; Khalid Iqbal; Fei Liu (Molecular Neurobiology, 2019)

Detection and characterization of a novel hepacivirus in long-tailed ground squirrels (Spermophilus undulatus) in China - Li-li Li; Meng-meng Liu; Shu Shen; Yu-jiang Zhang; Ya-long Xu; Hong-yan Deng; Fei Deng; Zhao-jun Duan (Archives of Virology, 2019)

A new pregnane steroid from cultures of Aspergillus versicolor - Jian-Hai Ding; Zhang-Gui Ding; Jiang-Yuan Zhao; Ming-Gang Li; Dong-Bao Hu; Xian-Jun Jiang; Dong-Sheng Zhou; Fei Wang; Meng-Liang Wen (Natural Product Research, 2019)

Improved recombinant protein production by regulation of transcription and protein transport in Chinese hamster ovary cells - Kaiming Chen; Dong Li; Hongwen Li; Bing Li; Ruiqin Wang; Lingxiao Jiang; Lei Huang; Xiaoqing Xu; Jie Li; Fei Teng; Cizhong Jiang; Hua Gu; et al. (Biotechnology Letters, 2019)

Novel hepacivirus in Asian house shrew, China - Hua Guo; Chunlin Cai; Bo Wang; Fei Zhuo; Rendi Jiang; Ning Wang; Bei Li; Wei Zhang; Yan Zhu; Yi Fan; Wushen Chen; Weihong Chen; et al. (Science China Life Sciences, 2019)

Glucose-6-phosphate dehydrogenase in blunt snout bream Megalobrama amblycephala: molecular characterization, tissue distribution, and the responsiveness to dietary carbohydrate levels - Guang-Zhen Jiang; Hua-Juan Shi; Chao Xu; Ding-Dong Zhang; Wen-Bin Liu; Xiang-Fei Li (Fish Physiology and Biochemistry, 2019)

Ferret badger rabies in Zhejiang, Jiangxi and Taiwan, China - Jing-Hui Zhao; Li-Feng Zhao; Fei Liu; Hong-Yun Jiang; Ji-Li Yang (Archives of Virology, 2019)

A new cyclohexenone from the tin mine tailings-derived fungus Aspergillus flavus YIM DT 10012 - Wei-Xun Chunyu; Jiang-Yuan Zhao; Zhang-Gui Ding; Xiu-Lin Han; Yong-Xia Wang; Jian-Hai Ding; Fei Wang; Ming-Gang Li; Meng-Liang Wen (Natural Product Research, 2019)

Occurrence and dietary exposure assessment of multiple mycotoxins in corn-based food products from Shandong, China - Dafeng Jiang; Fenghua Li; Fengjia Zheng; Jingyang Zhou; Lu Li; Fei Shen; Jindong Chen; Wei Li (Food Additives & Contaminants Part B-Surveillance, 2019)

Isolation and functional identification of an apple MdCER1 gene - Chen-Hui Qi; Xian-Yan Zhao; Han Jiang; Peng-Fei Zheng; Hai-Tao Liu; Yuan-Yuan Li; Yu-Jin Hao (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Correlation between S100A11 and the TGF-β1/SMAD4 pathway and its effects on the proliferation and apoptosis of pancreatic cancer cell line PANC-1 - Yi-Fei Ji; Tao Li; Feng Jiang; Wen-Kai Ni; Cheng-Qi Guan; Zhao-Xiu Liu; Cui-Hua Lu; Run-Zhou Ni; Wei Wu; Ming-Bing Xiao (Molecular and Cellular Biochemistry, 2019)

Clinical Application of Chromosome Microarray Analysis in Han Chinese Children with Neurodevelopmental Disorders - Mingyu Xu; Yiting Ji; Ting Zhang; Xiaodong Jiang; Yun Fan; Juan Geng; Fei Li (Neuroscience Bulletin, 2018)

A novel phenylspirodrimane dimer from cultures of the fungus Stachybotrys chartarum - Zhang-Gui Ding; Jiang-Yuan Zhao; Jian-Hai Ding; Wei-Xun Chunyu; Ming-Gang Li; Shao-Jie Gu; Fei Wang; Meng-Liang Wen (Natural Product Research, 2018)

Artificial intelligence in drug design - Feisheng Zhong; Jing Xing; Xutong Li; Xiaohong Liu; Zunyun Fu; Zhaoping Xiong; Dong Lu; Xiaolong Wu; Jihui Zhao; Xiaoqin Tan; Fei Li; Xiaomin Luo; et al. (Science China Life Sciences, 2018)

Neutrophil-to-Lymphocyte Ratio Is an Independent Predictor of 30-Day Mortality of Intracerebral Hemorrhage Patients: a Validation Cohort Study - Fei Wang; Li Wang; Ting-ting Jiang; Jian-jun Xia; Feng Xu; Li-juan Shen; Wen-hui Kang; Yong Ding; Li-xia Mei; Xue-feng Ju; Shan-you Hu; Xiao Wu (Neurotoxicity Research, 2018)

Ore genesis of the Wusihe carbonate-hosted Zn-Pb deposit in the Dadu River Valley district, Yangtze Block, SW China: evidence from ore geology, S-Pb isotopes, and sphalerite Rb-Sr dating - Suo-Fei Xiong; Yong-Jun Gong; Shao-Yong Jiang; Xiao-Jing Zhang; Qian Li; Guo-Ping Zeng (Mineralium Deposita, 2018)

Knockout of ush2a gene in zebrafish causes hearing impairment and late onset rod-cone dystrophy - Shanshan Han; Xiliang Liu; Shanglun Xie; Meng Gao; Fei Liu; Shanshan Yu; Peng Sun; Changquan Wang; Stephen Archacki; Zhaojing Lu; Xuebin Hu; Yayun Qin; et al. (Human Genetics, 2018)

Lysine supplement benefits the growth performance, protein synthesis, and muscle development of Megalobrama amblycephala fed diets with fish meal replaced by rice protein concentrate - Wan-Cun Cai; Wen-Bin Liu; Guang-Zhen Jiang; Kai-Zhou Wang; Cun-Xin Sun; Xiang-Fei Li (Fish Physiology and Biochemistry, 2018)

Molecular cloning of adipose triglyceride lipase (ATGL) gene from blunt snout bream and its expression after LPS-induced TNF-α factor - Yong-Jun Dai; Wen-Bin Liu; Xiang-Fei Li; Man Zhou; Chao Xu; Yu Qian; Guang-Zhen Jiang (Fish Physiology and Biochemistry, 2018)

Taxonomy of the family Arenaviridae and the order Bunyavirales: update 2018 - Piet Maes; Sergey V. Alkhovsky; Yīmíng Bào; Martin Beer; Monica Birkhead; Thomas Briese; Michael J. Buchmeier; Charles H. Calisher; Rémi N. Charrel; Il Ryong Choi; Christopher S. Clegg; Juan Carlos de la Torre; et al. (Archives of Virology, 2018)

P53/PUMA are potential targets that mediate the protection of brain-derived neurotrophic factor (BDNF)/TrkB from etoposide-induced cell death in neuroblastoma (NB) - Zhongyan Hua; Yue Zhan; Simeng Zhang; Yudi Dong; Min Jiang; Fei Tan; Zhihui Liu; Carol J. Thiele; Zhijie Li (Apoptosis, 2018)

A comparison of CRISPR/Cas9 and siRNA-mediated ALDH2 gene silencing in human cell lines - Fei Wang; Tao Guo; Hongmei Jiang; Ruobi Li; Ting Wang; Ni Zeng; Guanghui Dong; Xiaowen Zeng; Daochuan Li; Yongmei Xiao; Qiansheng Hu; Wen Chen; et al. (Molecular Genetics and Genomics, 2018)

Regulation of autophagy by tea polyphenols in diabetic cardiomyopathy - Hui Zhou; Yan Chen; Shu-wei Huang; Peng-fei Hu; Li-jiang Tang (Journal of Zhejiang University-SCIENCE B, 2018)

Pyr-miR171f-targeted PyrSCL6 and PyrSCL22 genes regulate shoot growth by responding to IAA signaling in pear - Shuling Jiang; Qiuju Chen; Qiulei Zhang; Yi Zhang; Ningning Hao; Chunqing Ou; Fei Wang; Tianzhong Li (Tree Genetics & Genomes, 2018)

Cell shape can be uncoupled from formononetin induction in a novel cell line from Callerya speciosa - Fei Qiao; Xue-fei Jiang; Han-qing Cong; Hua-peng Sun; Li Li; Peter Nick (Plant Cell Reports, 2018)

Different Hippocampus Functional Connectivity Patterns in Healthy Young Adults with Mutations of APP/Presenilin-1/2 and APOEε4 - Li Juan Zheng; Yun Yan Su; Yun Fei Wang; U. Joseph Schoepf; Akos Varga-Szemes; Jonathan Pannell; Xue Liang; Gang Zheng; Guang Ming Lu; Gui Fen Yang; Long Jiang Zhang (Molecular Neurobiology, 2018)

PKM2 knockdown influences SREBP activation and lipid synthesis in bovine mammary-gland epithelial MAC-T cells - Bing-Qian Su; Ying-Qian Han; Shuang-Shuang Fan; Sheng-Li Ming; Bo Wan; Wei-Fei Lu; Bei-Bei Chu; Guo-Yu Yang; Jiang Wang (Biotechnology Letters, 2018)

Chromosomes A07 and A05 associated with stable and major QTLs for pod weight and size in cultivated peanut (Arachis hypogaea L.) - Huaiyong Luo; Jianbin Guo; Xiaoping Ren; Weigang Chen; Li Huang; Xiaojing Zhou; Yuning Chen; Nian Liu; Fei Xiong; Yong Lei; Boshou Liao; Huifang Jiang (Theoretical and Applied Genetics, 2018)

The role of complementarity and selection effects in P acquisition of intercropping systems - Xiao-Fei Li; Cheng-Bao Wang; Wei-Ping Zhang; Le-Hua Wang; Xiu-Li Tian; Si-Cun Yang; Wan-Li Jiang; Jasper van Ruijven; Long Li (Plant and Soil, 2018)

Cloning and characterization of Agp1, the gene encoding the small subunit of ADP-glucose pyrophosphorylase from wheat and its relatives - Xiao-Wei Zhang; Qing Wang; Ling-Ling Zhang; Xiao-Juan Zhong; Qian-Tao Jiang; Jian Ma; Peng-Fei Qi; Wei Li; Guo-Yue Chen; Xiu-Jin Lan; Mei Deng; Zhen-Xiang Lu; et al. (Biologia, 2017)

Molecular characterization of fructose-1,6-bisphosphatase 1b in blunt snout bream Megalobrama amblycephala and the transcriptional response to glucose loading after the adaptation to high-carbohydrate diets - Xiang-Fei Li; Chao Xu; Guang-Zhen Jiang; Ding-Dong Zhang; Wen-Bin Liu (Fish Physiology and Biochemistry, 2017)

Spatial health risk assessment and hierarchical risk management for mercury in soils from a typical contaminated site, China - Fei Li; Jingdong Zhang; Wei Jiang; Chaoyang Liu; Zhongmin Zhang; Chengde Zhang; Guangming Zeng (Environmental Geochemistry and Health, 2017)

Prenylated benzoic acid derivatives from the stem of Euodia lepta - Ming-Bo Zhao; Si-Xiang Zhou; Qing-Ying Zhang; Wei-Feng Wei; Ming-Hui Li; Jian-Yong Xing; Yong Jiang; Peng-Fei Tu (Natural Product Research, 2017)

Erratum to: Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling‑Ling Zhang; Hu Chen; Mi Luo; Xiao‑Wei Zhang; Mei Deng; Jian Ma; Peng‑Fei Qi; Ji‑Rui Wang; Guo‑Yue Chen; Ya‑Xi Liu; Zhi‑En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling-Ling Zhang; Hu Chen; Mi Luo; Xiao-Wei Zhang; Mei Deng; Jian Ma; Peng-Fei Qi; Ji-Rui Wang; Guo-Yue Chen; Ya-Xi Liu; Zhi-En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Construction, Selection and Immunogenicity of Recombinant Fowlpox Candidate Vaccine Co-expressing HIV-1 gag and gp145 - Yilong Zhu; Yan Guo; Shouwen Du; Cunxia Liu; Maopeng Wang; Dayong Ren; Fei Zhao; Yanfang Zhang; Wenchao Sun; Yiquan Li; Tingting Cao; Yingyue Jiang; et al. (Indian Journal of Microbiology, 2017)

RETRACTED ARTICLE: Revisiting the male genetic landscape of China: a multi-center study of almost 38,000 Y-STR haplotypes - Michael Nothnagel; Guangyao Fan; Fei Guo; Yongfeng He; Yiping Hou; Shengping Hu; Jiang Huang; Xianhua Jiang; Wook Kim; Kicheol Kim; Chengtao Li; Hui Li; et al. (Human Genetics, 2017)

Altered Amygdala Resting-State Functional Connectivity in Maintenance Hemodialysis End-Stage Renal Disease Patients with Depressive Mood - Hui Juan Chen; Yun Fei Wang; Rongfeng Qi; U. Joseph Schoepf; Akos Varga-Szemes; B. Devon Ball; Zhe Zhang; Xiang Kong; Jiqiu Wen; Xue Li; Guang Ming Lu; Long Jiang Zhang (Molecular Neurobiology, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Hydrogen‐rich water regulates effects of ROS balance on morphology, growth and secondary metabolism via glutathione peroxidase in Ganoderma lucidum - Ang Ren; Rui Liu; Zhi‐Gang Miao; Xue Zhang; Peng‐Fei Cao; Tian‐Xi Chen; Chen‐Yang Li; Liang Shi; Ai‐Liang Jiang; Ming‐Wen Zhao (Environmental Microbiology, 2017)
Summary Ganoderma lucidum is one of the most important medicinal fungi, but the lack of basic study on the fungus has hindered the further development of its value. To investigate the roles of the redox system in G. lucidum , acetic acid (HAc) was applied as a reactive oxygen species (ROS) stress inducer, and hydrogen‐rich water (HRW) was used to relieve the ROS stress in this study. Our results demonstrate that the treatment of 5% HRW significantly decreased the ROS content, maintained biomass and polar growth morphology of mycelium, and decreased secondary metabolism under HAc‐induced oxidative stress. Furthermore, the roles of HRW were largely dependent on restoring the glutathione system under HAc stress in G. lucidum . To provide further evidence, we used two glutathione peroxidase (GPX)‐defective strains, the gpxi strain, the mercaptosuccinic acid (MS, a GPX inhibitor)‐treated wide‐type (WT) strain, and gpx overexpression strains for further research. The results show that HRW was unable to relieve the HAc‐induced ROS overproduction, decreased biomass, mycelium morphology change and increased secondary metabolism biosynthesis in the absence of GPX function. The gpx overexpression strains exhibited resistance to HAc‐induced oxidative stress. Thus, we propose that HRW regulates morphology, growth and secondary metabolism via glutathione peroxidase under HAc stress in the fungus G. lucidum . Furthermore, our research also provides a method to study the ROS system in other fungi.

Shifts of archaeal community structure in soil along an elevation gradient in a reservoir water level fluctuation zone - Fei Ye; Shengjun Wu; Yi Jiang; Huub J. M. Op den Camp; Zhe Li; Guibing Zhu; Jun Zheng; Yu Wang (Journal of Soils and Sediments, 2016)

Thrombospondin-4 Promotes Neuronal Differentiation of NG2 Cells via the ERK/MAPK Pathway - Hai Jie Yang; Shuang Ping Ma; Fei Ju; Ya Ping Zhang; Zhi Chao Li; Bin Bin Zhang; Jun Jiang Lian; Lei Wang; Bin Feng Cheng; Mian Wang; Zhi Wei Feng (Journal of Molecular Neuroscience, 2016)

A Smartphone Application Supporting Recovery from Heroin Addiction: Perspectives of Patients and Providers in China, Taiwan, and the USA - Marya Schulte; Di Liang; Fei Wu; Yu-Ching Lan; Wening Tsay; Jiang Du; Min Zhao; Xu Li; Yih -Ing Hser (Journal of Neuroimmune Pharmacology, 2016)

Characterization of the waxy gene in diploid Triticum L. and Aegilops L. species and its geographic distribution - Wei Li; Bang-Bo Fu; Zhe Li; Ya-Xi Liu; Zhi-En Pu; Peng-Fei Qi; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng (Genetic Resources and Crop Evolution, 2016)

Synthesis and potential anticonvulsant activity of new aryl sulfonyl semicarbazide derivatives - Yousong Nie; Min Zhong; Zhiyuan Jiang; Jian Sun; Yangguang Gao; Fei Ding; Hang Li; Yongmin Zhang; Xianran He (Medicinal Chemistry Research, 2016)

Biotransformation of gypenoside XVII to compound K by a recombinant β-glucosidase - Fei-Liang Zhong; Wei-Wei Dong; Songquan Wu; Jun Jiang; Deok-Chun Yang; Donghao Li; Lin-Hu Quan (Biotechnology Letters, 2016)

Alterations and correlations of the gut microbiome, metabolism and immunity in patients with primary biliary cirrhosis - Long‐Xian Lv; Dai‐Qiong Fang; Ding Shi; De‐Ying Chen; Ren Yan; Yi‐Xin Zhu; Yan‐Fei Chen; Li Shao; Fei‐Fei Guo; Wen‐Rui Wu; Ang Li; Hai‐Yan Shi; et al. (Environmental Microbiology, 2016)
Summary We selected 42 early‐stage primary biliary cirrhosis (PBC) patients and 30 healthy controls (HC). Metagenomic sequencing of the 16S rRNA gene was used to characterize the fecal microbiome. UPLC‐MS/MS assaying of small molecules was used to characterize the metabolomes of the serum, urine and feces. Liquid chip assaying of serum cytokines was used to characterize the immune profiles. The gut of PBC patients were depleted of some potentially beneficial bacteria, such as Acidobacteria, Lachnobacterium sp., Bacteroides eggerthii and Ruminococcus bromii , but were enriched in some bacterial taxa containing opportunistic pathogens, such as γ‐Proteobacteria, Enterobacteriaceae, Neisseriaceae, Spirochaetaceae , Veillonella , Streptococcus , Klebsiella , Actinobacillus pleuropneumoniae , Anaeroglobus geminatus , Enterobacter asburiae , Haemophilus parainfluenzae , Megasphaera micronuciformis and Paraprevotella clara . Several altered gut bacterial taxa exhibited potential interactions with PBC through their associations with altered metabolism, immunity and liver function indicators, such as those of Klebsiella with IL‐2A and Neisseriaceae with urinary indoleacrylate. Many gut bacteria, such as some members of Bacteroides, were altered in their associations with the immunity and metabolism of PBC patients, although their relative abundances were unchanged. Consequently, the gut microbiome is altered and may be critical for the onset or development of PBC by interacting with metabolism and immunity.

Genetic diversity, population structure and association analysis in cut chrysanthemum (Chrysanthemum morifolium Ramat.) - Pirui Li; Fei Zhang; Sumei Chen; Jiafu Jiang; Haibin Wang; Jiangshuo Su; Weimin Fang; Zhiyong Guan; Fadi Chen (Molecular Genetics and Genomics, 2016)

Elevated Expression of VEGF-C and Its Receptors, VEGFR-2 and VEGFR-3, in Patients with Mesial Temporal Lobe Epilepsy - Fei-Ji Sun; Yu-Jia Wei; Song Li; Wei Guo; Xin Chen; Shi-Yong Liu; Jiao-Jiang He; Qing Yin; Hui Yang; Chun-Qing Zhang (Journal of Molecular Neuroscience, 2016)

Structure and expression of phosphoglucan phosphatase genes of Like Sex Four1 and Like Sex Four2 in barley - Jian Ma; Shang Gao; Qian-Tao Jiang; Qiang Yang; Min Sun; Ji-Rui Wang; Peng-Fei Qi; Ya-Xi Liu; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; et al. (Genetica, 2016)

Nonlinear inversion of electrical resistivity imaging using pruning Bayesian neural networks - Fei-Bo Jiang; Qian-Wei Dai; Li Dong (Applied Geophysics, 2016)

Two new abietane diterpenoid glycosides from Clinopodium chinense - Yin-Di Zhu; Jing-Yi Zhang; Peng-Fei Li; Hai-Feng Wu; Nai-Liang Zhu; Hai Jiang; Cui-Yan Lv; Li-Li Wu; Ze-Xin Ma; Xu-Dong Xu; Guo-Xu Ma; Jun-Shan Yang (Natural Product Research, 2016)

Feeding rates affect growth, intestinal digestive and absorptive capabilities and endocrine functions of juvenile blunt snout bream Megalobrama amblycephala - Chao Xu; Xiang-Fei Li; Hong-Yan Tian; Guang-Zhen Jiang; Wen-Bin Liu (Fish Physiology and Biochemistry, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Impact of biochar produced from post-harvest residue on the adsorption behavior of diesel oil on loess soil - Yu Feng Jiang; Hang Sun; Uwamungu J. Yves; Hong Li; Xue Fei Hu (Environmental Geochemistry and Health, 2016)

Three new phenanthrenone constituents from Trigonostemon lii - Shi-Fei Li; Hong-Ping He; Xiao-Jiang Hao (Natural Product Research, 2015)

The Association Between Serum Levels of Selenium, Copper, and Magnesium with Thyroid Cancer: a Meta-analysis - Fei Shen; Wen-Song Cai; Jiang-Lin Li; Zhe Feng; Jie Cao; Bo Xu (Biological Trace Element Research, 2015)

Characterization of genes encoding Starch Branching Enzyme I from Triticum monococcum and its diploid wheat relatives - Xiu-Ying Wang; Chang-Shui Wang; Jian Ma; Ji-Rui Wang; Ya-Xi Liu; Peng-Fei Qi; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; You-Liang Zheng; Qian-Tao Jiang (Biologia, 2015)

Spatiotemporal variation of riverine nutrients in a typical hilly watershed in southeast China using multivariate statistics tools - Xiao-fei Nie; Heng-peng Li; Jia-hu Jiang; Ya-qin Diao; Peng-cheng Li (Journal of Mountain Science, 2015)

Phosphorylation of p38 MAPK mediates aquaporin 9 expression in rat brains during permanent focal cerebral ischaemia - Xiaoyu Wei; Xuxia Ren; Rong Jiang; Hui Li; Fei Gao; Yuqin Chen; Jiaojiao Hou; Xueyuan Liu; Shanquan Sun; Mei Yang (Journal of Molecular Histology, 2015)

Drug susceptibility and molecular epidemiology of Escherichia coli in bloodstream infections in Shanghai, China, 2011–2013 - Sheng-Yuan Zhao; Yan-Chun Wang; Shu-Zhen Xiao; Xiao-Fei Jiang; Xiao-Kui Guo; Yu-Xing Ni; Li-Zhong Han (Infectious Diseases, 2015)

De novo transcriptome assembly, gene annotation, marker development, and miRNA potential target genes validation under abiotic stresses in Oenanthe javanica - Qian Jiang; Feng Wang; Hua-Wei Tan; Meng-Yao Li; Zhi-Sheng Xu; Guo-Fei Tan; Ai-Sheng Xiong (Molecular Genetics and Genomics, 2015)

Prognostic Factors of Survival in Pathologic Incomplete Response Patients with Locally Advanced Breast Cancer After Neoadjuvant Chemotherapy - Ou Huang; Min Jiang; Xiao-song Chen; Jia-yi Wu; Wei-guo Chen; Ya-fei Li; Kun-wei Shen (Cell Biochemistry and Biophysics, 2015)

Effects of fructooligosaccharide on immune response, antioxidant capability and HSP70 and HSP90 expressions of blunt snout bream (Megalobrama amblycephala) under high ammonia stress - Chun-Nuan Zhang; Xiang-Fei Li; Hong-Yan Tian; Ding-Dong Zhang; Guang-Zhen Jiang; Kang-Le Lu; Guang-Xia Liu; Wen-Bin Liu (Fish Physiology and Biochemistry, 2015)

Knockdown of Akt2 Expression by ShRNA Inhibits Proliferation, Enhances Apoptosis, and Increases Chemosensitivity to Paclitaxel in Human Colorectal Cancer Cells - Zhongyang Ding; Fei Xu; Gan Li; Jiandong Tang; Zhangfeng Tang; Panqiang Jiang; Haotian Wu (Cell Biochemistry and Biophysics, 2015)

De novo assembly and transcriptome characterization: novel insights into the temperature stress in Cryptotaenia japonica Hassk - Guo-Fei Tan; Feng Wang; Meng-Yao Li; Guang-Long Wang; Qian Jiang; Ai-Sheng Xiong (Acta Physiologiae Plantarum, 2015)

RETRACTED ARTICLE: Explore on the effect of ATF6 on cell growth and apoptosis in cartilage development - Xiaofeng Han; Peng Zhang; Rong Jiang; Fei Xia; Meiling Li; Feng-Jin Guo (Histochemistry and Cell Biology, 2014)

Evidence of adult neurogenesis in non-human primates and human - Ti-Fei Yuan; Jiang Li; Fei Ding; Oscar Arias-Carrion (Cell and Tissue Research, 2014)

The methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism and tumor risk: evidence from 134 case–control studies - Min Tang; Shang-Qian Wang; Bian-Jiang Liu; Qiang Cao; Bing-Jie Li; Peng-Chao Li; Yong-Fei Li; Chao Qin; Wei Zhang (Molecular Biology Reports, 2014)

Urinary Perchlorate Exposure and Risk in Women of Reproductive Age in a Fireworks Production Area of China - Qin Li; Yun-jiang Yu; Fei-fei Wang; Shi-wu Chen; Yan Yin; Hai-peng Lin; Fei Che; Peng Sun; Juan Qin; Jie Liu; Hong-mei Wang (Archives of Environmental Contamination and Toxicology, 2014)

Efficacy of Various Combined Blood Purification Techniques for Treating Patients with Non-viral Acute Liver Failure - Mao-qin Li; Jia-qiong Li; Zai-xiang Shi; Ji-yuan Xu; Zhou Zhang; Fei Lu; Lin Li; Yan-jun Xu; Xun Mo; Bo Lu; Xiao-meng Wang; Li-li Ma; et al. (Cell Biochemistry and Biophysics, 2014)

The effect of Se-deficient diet on gene expression of inflammatory cytokines in chicken brain - Peng-fei Sheng; Yue Jiang; Zi-wei Zhang; Jiu-li Zhang; Shu Li; Zi-qun Zhang; Shi-wen Xu (BioMetals, 2014)

Investigation on semi-direct and indirect climate effects of fossil fuel black carbon aerosol over China - Bingliang Zhuang; Qian Liu; Tijian Wang; Changqin Yin; Shu Li; Min Xie; Fei Jiang; Huiting Mao (Theoretical and Applied Climatology, 2013)

Identification of differentially expressed genes in American cockroach ovaries and testes by suppression subtractive hybridization and the prediction of its miRNAs - Wan Chen; Guo-Fang Jiang; Shu-Hong Sun; Yong Lu; Fei Ma; Bin Li (Molecular Genetics and Genomics, 2013)

Design, synthesis and antidepressant activity evaluation 2′-hydroxy-4′,6′-diisoprenyloxychalcone derivatives - Li-Ping Guan; Dong-Hai Zhao; Yue Chang; Yu Sun; Xiao-Li Ding; Jing-Fei Jiang (Medicinal Chemistry Research, 2013)

Isolation, Culture, and Identification of Amniotic Fluid-Derived Mesenchymal Stem Cells - Xuetao Fei; Shan Jiang; Song Zhang; Yigang Li; Junbo Ge; Ben He; Steven Goldstein; George Ruiz (Cell Biochemistry and Biophysics, 2013)

Acceleration effect of amino acid supplementation on glycerol assimilation by Escherichia coli in minimal medium - Gang Xiang; Jiang Li; JiFu Duan; Fei Shao; Jiajie Xu; Shuilin Fu; Heng Gong (Biotechnology Letters, 2013)

Screening proteins interacting with VpPR10.1 of Chinese wild grapevine using the yeast two-hybrid system - Teng-Fei Xu; Jiang Xiang; Feng-Ju Li; Tie-Mei Li; Yi-He Yu; Yue-Jin Wang; Yan Xu (Acta Physiologiae Plantarum, 2013)

Levosimendan versus dobutamine in critically ill patients: a meta-analysis of randomized controlled trials - Xuan Huang; Shu Lei; Mei-fei Zhu; Rong-lin Jiang; Li-quan Huang; Guo-lian Xia; Yi-hui Zhi (Journal of Zhejiang University-SCIENCE B, 2013)

Loop-mediated isothermal amplification for rapid and convenient detection of Mycoplasma hyopneumoniae - Jiahe Li; F. Chris Minion; Andrew C. Petersen; Fei Jiang; Sheng Yang; Panpan Guo; Jinxiang Li; Wenxue Wu (World Journal of Microbiology and Biotechnology, 2013)

Endostatin inhibits hypertrophic scarring in a rabbit ear model - Hai-tao Ren; Hang Hu; Yuan Li; Hong-fei Jiang; Xin-lei Hu; Chun-mao Han (Journal of Zhejiang University-SCIENCE B, 2013)

Protective effect of Homer 1a on tumor necrosis factor-α with cycloheximide-induced apoptosis is mediated by mitogen-activated protein kinase pathways - Peng Luo; Yongbo Zhao; Dong Li; Tao Chen; Sanzhong Li; Xiaodong Chao; Wenbo Liu; Lei Zhang; Yan Qu; Xiaofan Jiang; Gang Lu; Waisang Poon; et al. (Apoptosis, 2012)

Recombinant human endostatin inhibits adjuvant arthritis by down-regulating VEGF expression and suppression of TNF-α, IL-1β production - Wei Hu; Li-Juan Xia; Fei-Hu Chen; Fan-Rong Wu; Jie Tang; Cun-Zhi Chen; Sheng Jiang; Hui-Hui Chen (Inflammation Research, 2012)

Gene expression profile of campylobacter jejuni-induced GBS in bama miniature pigs - Feng Xue; Dexin Zeng; Fei Xu; Rui Zhang; Yang Chen; Yuefei Yang; Xiaobo Wang; Zhenzhong Li; Xiaorong Zhang; Yuan Jiang (Cell and Tissue Research, 2012)

Exocytosis of SH-SY5Y single cell with different shapes cultured on ITO micro-pore electrode - Hui Zhao; Ling Li; Hua-Jun Fan; Fei Wang; Li-Ming Jiang; Pin-Gang He; Yu-Zhi Fang (Molecular and Cellular Biochemistry, 2012)

Vancomycin-loaded nano-hydroxyapatite pellets to treat MRSA-induced chronic osteomyelitis with bone defect in rabbits - Ji-Le Jiang; Yun-Fei Li; Tao-Lin Fang; Jian Zhou; Xi-Lei Li; Yi-Chao Wang; Jian Dong (Inflammation Research, 2012)

Molecular mapping of Arabidopsis thaliana lipid-related orthologous genes in Brassica napus - Jianyi Zhao; Jixiang Huang; Fei Chen; Fei Xu; Xiyuan Ni; Haiming Xu; Yilong Wang; Chonchon Jiang; Hao Wang; Aixia Xu; Ruizhi Huang; Dianrong Li; et al. (Theoretical and Applied Genetics, 2012)

Molecular Cloning and Expression Analysis of 13 MADS-Box Genes in Betula platyphylla - Hui-yu Li; Fei-fei Liu; Gui-feng Liu; Shan Wang; Xiao-hong Guo; Jiang Jing (Plant Molecular Biology Reporter, 2012)

PCSK9 siRNA inhibits HUVEC apoptosis induced by ox-LDL via Bcl/Bax–caspase9–caspase3 pathway - Chun-Yan Wu; Zhi-Han Tang; Lu Jiang; Xue-Fei Li; Zhi-Sheng Jiang; Lu-Shan Liu (Molecular and Cellular Biochemistry, 2012)

Sphingosine-1-phosphate: a potential therapeutic target for rheumatoid arthritis - Peng-fei Hu; Yi Chen; Peng-fei Cai; Li-feng Jiang; Li-dong Wu (Molecular Biology Reports, 2011)

Investigation on the direct radiative effect of fossil fuel black-carbon aerosol over China - Bingliang Zhuang; Fei Jiang; Tijian Wang; Shu Li; Bin Zhu (Theoretical and Applied Climatology, 2011)

Effect of atmospheric aerosol on surface ozone variation over the Pearl River Delta region - XueJiao Deng; XiuJi Zhou; Dui Wu; XueXi Tie; HaoBo Tan; Fei Li; XueYan Bi; Tao Deng; DeHai Jiang (Science China Earth Sciences, 2011)

Paclitaxel-Loaded Poly(n-butylcyanoacrylate) Nanoparticle Delivery System to Overcome Multidrug Resistance in Ovarian Cancer - Fei Ren; Ruda Chen; Ying Wang; Yabin Sun; Yaodong Jiang; Guofeng Li (Pharmaceutical Research, 2011)

Cloning, characterization, expression, and copper sensitivity of the metallothionein-1 gene in the Chinese mitten crab, Eriocheir sinensis - Fei Ren; Hui Jiang; Jiangling Sun; Lin He; Weiwei Li; Ying Wang; Qun Wang (Molecular Biology Reports, 2011)

Pseudonocardia sichuanensis sp. nov., a novel endophytic actinomycete isolated from the root of Jatropha curcas L. - Sheng Qin; Ke Xing; Shi-Min Fei; Qiang Lin; Xiu-Min Chen; Cheng-Liang Cao; Yong Sun; Yun Wang; Wen-Jun Li; Ji-Hong Jiang (Antonie van Leeuwenhoek, 2011)

Fulminant type 1 diabetes in China: a case report and review of the literature - Yun-fei Feng; Mei-fen Yao; Qi Li; Yan Sun; Cheng-jiang Li; Jian-guo Shen (Journal of Zhejiang University-SCIENCE B, 2010)

Effect of glycyrrhizin on the activity of CYP3A enzyme in humans - Jiang-Hua Tu; Yi-Jing He; Yao Chen; Lan Fan; Wei Zhang; Zhi-Rong Tan; Yuan-Fei Huang; Dong Guo; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2010)

Spontaneous Rhythmic Inward Currents Recorded in Interstitial Cells of Rabbit Portal Vein - Xu Huang; Dan Zhao; Zuo-Yu Wang; Ming-Liang Zhang; Zhi-Qiang Yan; Yan-Fei Han; Hong-Li Lu; Wen-Xie Xu; Zong-Lai Jiang (Cell Biochemistry and Biophysics, 2010)

Magma mixing origin for the post-collisional adakitic monzogranite of the Triassic Yangba pluton, Northwestern margin of the South China block: geochemistry, Sr–Nd isotopic, zircon U–Pb dating and Hf isotopic evidences - Jiang-Feng Qin; Shao-Cong Lai; Chun-Rong Diwu; Yin-Juan Ju; Yong-Fei Li (Contributions to Mineralogy and Petrology, 2010)

Risk to humans of consuming metals in anchovy (Coilia sp.) from the Yangtze River Delta - Fengyan Liu; Jiachun Ge; Xin Hu; Teng Fei; Yuehua Li; Yuan Jiang; Zhiqiang Xu; Shuyan Ding; John P. Giesy; Jianlin Pan (Environmental Geochemistry and Health, 2009)

Hydraulic pressure inducing renal tubular epithelial-myofibroblast transdifferentiation in vitro - Fei-yan Li; Xi-sheng Xie; Jun-ming Fan; Zi Li; Jiang Wu; Rong Zheng (Journal of Zhejiang University-SCIENCE B, 2009)

Levels and Chiral Signatures of Organochlorine Pesticides in Urban Soils of Yinchuan, China - Wei Wang; Xing-Hong Li; Xiao-Fei Wang; Xi-Zhi Wang; Hai Lu; Xiang-Ning Jiang; Xiao-Bai Xu (Bulletin of Environmental Contamination and Toxicology, 2009)

Stock enhancement of the edible jellyfish (Rhopilema esculentum Kishinouye) in Liaodong Bay, China: a review - Jing Dong; Lian-xin Jiang; Ke-fei Tan; Hai-ying Liu; Jennifer E. Purcell; Pei-jun Li; Chang-chen Ye (Hydrobiologia, 2009)

Hypertonic stimulation induces synthesis and release of glutamate in cultured rat hypothalamic astrocytes and C6 cells - Rong Cao; Shan Jiang; Li Duan; Ying-Fei Xiong; Bei Gao; Zhi-Ren Rao (Neuroscience Bulletin, 2008)

Characterization of chitinase secreted by Bacillus cereus strain CH2 and evaluation of its efficacy against Verticillium wilt of eggplant - Jian-Gang Li; Zhi-Qiang Jiang; Liu-Ping Xu; Fei-Fei Sun; Jian-Hua Guo (BioControl, 2008)

Enhanced Agrobacterium-mediated Transformation of Embryogenic Calli of Upland Cotton via Efficient Selection and Timely Subculture of Somatic Embryos - Shen-Jie Wu; Hai-Hai Wang; Fei-Fei Li; Tian-Zi Chen; Jie Zhang; Yan-Jie Jiang; Yezhang Ding; Wang-Zhen Guo; Tian-Zhen Zhang (Plant Molecular Biology Reporter, 2008)

Relationships between O isotope equilibrium, mineral alteration and Rb–Sr chronometric validity in granitoids: implications for determination of cooling rate - Jiang Feng Chen; Yong-Fei Zheng; Zi-Fu Zhao; Bo Li; Zhi Xie; Bing Gong; Hui Qian (Contributions to Mineralogy and Petrology, 2007)

An application of the RAMS/FLUENT system on the multi-scale numerical simulation of the urban surface layer—A preliminary study - Lei Li; Fei Hu; Jinhua Jiang; Xueling Cheng (Advances in Atmospheric Sciences, 2007)